Fusion of near-infrared and mid-infrared spectroscopy for the analysis of typical microplastic contaminants in powdered camel milk - Runxian Li; Wenxin Zheng; Yuchao Feng; Decheng Suo; Zhiming Xiao; Xia Fan (Food Control, 2027)

Stathmin-mediated autophagy drives the differentiation of dermal fibroblast into myofibroblast under TGFβ1 stimulation - Hui Tang; Luqi Yang; Yanhai Feng; Jianxin Wu; Yi Liang; Zhenglin Li; Lingbo Li; Wan Zhao; Xiaolin Deng; Dan Luo; Xia Lei; Lingfei Li (Molecular Biology Reports, 2026)

Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

Molecular epidemiology and antimicrobial resistance of Vibrio parahaemolyticus isolates from aquatic products in the Southern Fujian coast, China - Qiao-Hua Zheng; Yang Chen; Yu-Fang Tian; Turmidzi Fath; Jun-Chao Zheng; Dan-Feng Zhang; Yi-Hong Wang; Qing-Sen Chen; Feng-Xia Li; Xiu-Min Chen; Yuan-Qing Hu (Brazilian Journal of Microbiology, 2026)

Comparative analysis of multiple health risks from different air pollution events - Feixue Zheng; Jinwen Li; Chenjie Hua; Tingyu Liu; Jiali Xie; Zemin Feng; Yusheng Zhang; Chao Yan; Men Xia; Qi Yuan; Federico Bianchi; Tuukka Petäjä; et al. (Journal of Environmental Sciences, 2026)

Targeting cancer cell–Staphylococcus aureus symbiosis with multilayered nanoparticles for enhanced melanoma therapy - Li Zhang; Yiyi Qian; Yifan Chen; Yun Zhang; Min Chen; Danna Feng; Qianqian Sun; Jiani Shen; Jiang Xia; Jianhao Wang (Chemical Engineering Journal, 2026)

Structure-evolving bioadhesive for temporally programmed osteoimmune modulation in osteoporotic bone regeneration - Qingda Li; Yurong Chen; Yining Gong; Yuan He; Bin Zhu; Senyu Xue; Luyao Feng; Yiming Ren; Xiaoyu Wu; Lu Dang; Bo Zhang; Dali He; et al. (Chemical Engineering Journal, 2026)

Dual exposure disparity: Age-specific and diurnal-nocturnal heat exposure inequity in a subtropical metropolis - Feng Gao; Tingyan Shi; Shunyi Liao; Ye Wang; Lei Feng; Yafeng Ni; Chang Liu; Peng Zeng; Xia Li (Sustainable Cities and Society, 2026)

PpPRE1 and PpPRE2 mediate gibberellin-induced internode elongation by regulating brassinosteroid biosynthesis in peach - Huanbing Lu; Mengmeng Zhang; Ning Liu; Bo Zhao; Jun Cheng; Bin Tan; Xianbo Zheng; Wei Wang; Xia Ye; Haipeng Zhang; Xiaobei Wang; Zhiqian Li; et al. (Plant Science, 2026)

Experimental design and adsorption mechanism research of risedronate nanofunctionalized hydroxyapatite for efficient removal of Co2+ and Pb2+ - Jianzhe Ma; Juying Li; Mingxing Shi; Yuting Chu; Yueqing Zhang; Feng Ge; Mingzhu Xia; Fengyun Wang; Deyang Kong (Journal of Environmental Chemical Engineering, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Addressing fruit allergen detection gaps: A validated LC-MS/MS method for eight allergenic fruits in foods - Yingnan Shencheng; Meizhen Zhou; Yumeng Zhao; Siyi Li; Yutong Xu; Yanan Gao; Xiaoxue Jia; Min Gao; Rong Zhang; Shuyan Liu; Feng Ye; Ya Zhang; et al. (Food Chemistry, 2026)

Comparative genomics and metabolomic profiling of Lactiplantibacillus plantarum LP104 reveal its potential in co-fermented yogurt - Yue Zhang; Yin Feng; Mingxue Sun; Yamei He; Qianhui Liu; Bo Nan; Xia Li; Jingsheng Liu; Yu Wang; Yuhua Wang (Food Chemistry, 2026)

Heterogeneous dual-enzyme cascade platform based on COF and MOF for targeted valorization of rice protein - Li-Xia Yan; Liu-Feng Yu; Jie Zhou; Li-Zhi Xu; Yu-Han Sun; Yu-Han Jin; Yi Zhang; Hui-Hui Liu (Food Chemistry, 2026)

Hollow kapok fiber-enabled photothermal aerogel with water supply and salt back-diffusion for solar desalination and thermoelectric generation - Shuyue Feng; Yao Wang; Bingyan Wang; Li Wang; Mohan Yang; Lixin Feng; Heng Li; Shaotian Qi; Ankang Jia; Yanfang Zhao; Kun Chen; Wei Xia (Chemical Engineering Journal, 2026)

Temperature-regulated surfactant interfacial behavior influences shell formation and mechanical susceptibility of pesticide microcapsules - Xuewen Jian; Xin Liu; Quanbin Liu; Haixiu Bai; Xiangyang Li; Yunyu Tang; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2026)

Highly selective NO2 sensing for mobile on-site monitoring enabled by a dual-sensitization mechanism in palladium sulfide-based nanocomposites - Yongjing Guo; Hangshuo Feng; Qiuni Zhao; Shenghui Guo; Renminxi Ou; Shunping Zhang; Zaihua Duan; Yi Xia; Zhen Yuan; Ming Hou; Li Yang; Huiling Tai (Chemical Engineering Journal, 2026)

Quantitative shear-window engineering enables scalable biomanufacturing of functional mesenchymal stem cell-derived exosomes - Wei-feng Li; Kai-jie Xia; Yan Xin; Jay Liu; Yu-ting Sun; Kamran Ashraf; Yu-wen Hu; Touseef Ur Rehman; Fan Gao; Shao-yong Zhuang; Mei-jin Guo; Ali Mohsin (Chemical Engineering Journal, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

exaPD: A highly parallelizable workflow for multi-element phase diagram (PD) construction - Feng Zhang; Zhuo Ye; Maxim Moraru; Ying Wai Li; Weiyi Xia; Yongxin Yao; Cai-Zhuang Wang (Computer Physics Communications, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Influence of cutterhead cooling water on microwave-induced fracturing of hard rocks during microwave-TBM synchronous operation - Tianyang Tong; Xia-Ting Feng; Chengxiang Yang; Feng Lin; Shiping Li; Xiangxin Su (Tunnelling and Underground Space Technology, 2026)

Mortality risks of co-exposure to extreme heat and ozone in urban populations: Synergy, vulnerability, and implications for public health - Xing Bi; Xiaojia Chen; Shan Jin; Yong Wang; Michelle L Bell; Caiyan Wu; Conghe Song; Qi Li; Chunfang Wang; Tian Xia; Dagmar Haase; Feng Mao; et al. (Sustainable Cities and Society, 2026)

MASt3R-Fusion: Integrating feed-forward visual model with IMU, GNSS for high-functionality SLAM - Yuxuan Zhou; Xingxing Li; Shengyu Li; Zhuohao Yan; Chunxi Xia; Shaoquan Feng (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Epsilon-polylysine inhibits plasmid RP4-mediated conjugative transfer of antibiotic resistance genes from E. coli DH5α to P. putida KT2440 - Liu-Feng Yu; Yang Weng; Yi Zhang; Li-Xia Yan (Food Bioscience, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Dual-functional nanotherapeutics: A novel approach to siRNA-mediated TNF-α silencing in inflammatory bowel disease - Li Qiao; Xue-Tian Qian; Yi-Gang Zhang; Xia-Feng Peng; Qi Liu; Shi-Qi Chang; Chang Cui; Feng Zhang; Shu-Kui Wang; Ning-Ping Huang (Chemical Engineering Journal, 2026)

Integrated multi-omics analysis reveals mechanism of metabolic reprogramming enabling bacterial selenite detoxification and selenium nanoparticles biogenesis by Serratia marcescens HBQT - Yidong Zhang; Jin Lin; Mingyang He; Shiyao Li; Yan Liu; Hao Feng; Yawen Geng; Tao Li; Li Zhang; Jintao Xia; Taohong Zhou (Bioresource Technology, 2026)

Species Diversity, Parasitism Rates, Longevity, and Population Dynamics of the Parasitoid Complex Attacking Ophelimus bipolaris in China - Jin Hu; Yuan-Hao Li; Jing-Hui Su; Jin-Bo Sun; Guo-Bao Qin; Yan Qin; Lai-Feng Luo; Lin-Xia Feng; Kai-Jian Han; Zoya Yefremova; Jun Li; Xia-Lin Zheng (Neotropical Entomology, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Precision omic portrait deciphers the epigenetic variable during cellular identity reshaping of metastatic head and neck squamous cell carcinoma - Qiushi Feng; Xiaofeng Shan; Yangyang Xia; Lingzi Liao; Yifan Kang; Zimeng Li; Ziwei Dai; Yingyue Chai; Xinyuan Zhang; Luming Wang; Shang Xie; Zhigang Cai (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Travel-driven carbon emissions: Evidence from winter travel flow from Northeast to Hainan in China - Yuanxing Xia; Ke Wang; Qi Wang; Alexis Pengfei Zhao; Zhengmao Li; Feng Wu (Journal of Cleaner Production, 2026)

Dielectric barrier discharge pretreatment combined with magnetic field-assisted partial freezing: A novel strategy for enhancing the preservation quality of tuna - Qingxin Guo; Meihui Zhao; Li Liu; Jiamei Wang; Haohao Shi; Aiguo Feng; Liming Zhang; Guanghua Xia; Shiyuan Dong (Food Research International, 2026)

Loss of foxp3a drives sex-specific immune-metabolic remodeling across the gut-liver-gonad axis in zebrafish - Yuhang Hu; Deinyefa Godfree Igbiriki; Nan Wu; Jialin Li; Junheng Liu; Jiuwu Yin; Jinping Duan; Xianmei Li; Zhixian Qiao; Feng Xiong; Yingyin Cheng; Wanting Zhang; et al. (Fish & Shellfish Immunology, 2026)

China could simultaneously increase wheat yield and nitrogen use efficiency under the temperature rise of 1 ℃ through optimal crop managements - Kaiyuan Gong; Shuoqiu Ding; Yadong Luo; Yinghua Zhang; Xiao Wang; Fengying Duan; Xia Li; Liangbing Rong; Zhihao He; Hao Feng; Qiang Yu; Wenbin Zhou; et al. (European Journal of Agronomy, 2026)

Charge-shielding assembly enables biointerface engineering of polyhexamethylene biguanide for selective and resistance-resilient antibacterial therapy - Xinyun Zeng; Min Wang; Pan Mao; Lei Zhang; Yongyi Yao; Ziqi Yin; Peiren Chen; Lei Wan; Wei Su; Xia Li; Xin Li; Pei Tang; et al. (Chemical Engineering Journal, 2026)

Exploration and identification of antifungal antibiotics from Streptomyces TRM 68022 based on OSMAC strategy - Yi-Huang Chen; Chun-Yang Zhang; Feng Zhang; Fei Yin; Yu-Xin Si; Ying-Ying Xia; Jia-Xin Zhang; Yi-Fei Li; Xiao-Xia Luo (Biocatalysis and Agricultural Biotechnology, 2026)

Impact of ammonia slip on particle emissions of industrial flue gases: A case study in Jiangsu Province, China - Sijia Xia; Jinrun Yi; Qiuyue Zhao; Qing Li; Feng Miao; Wentai He; Peilin Chen; Qian Liu (Atmospheric Pollution Research, 2026)

Effects of N-carbamylglutamate supplementation on growth, serum biochemistry, antioxidant capacity, immune function, hormonal profile, and reproductive performance in rabbits under chronic heat stress conditions - Pin Zhai; Jie Yang; Feng Qin; Yao Yao; Le Shao; Jian Li; Xia Zhang (Animal Reproduction Science, 2026)

Stable isotope labeling LC–MS for profiling the amine submetabolome in a D-lactate treated cell model - Yue-Qiang Chen; Xiao-Xia Dong; Li Liu; Xiu-Ping Chen; Chen-Guo Feng; Li-Xing Zhan; Yue Su; Fang Zhang; Yin-Long Guo (Analytica Chimica Acta, 2026)

Synergistic foliar application of zinc and manganese reduces Cd accumulation in rice by enhancing leaf sequestration and modulating Cd transporter gene expression - Chang Li; Hang Zhou; Xia Zhou; Peng Zeng; Lin Song; Lan-Xin Ma; Jiao-Feng Gu (Plant and Soil, 2026)

Chemical constituents from the roots of Illigera celebica - Si-Feng Yang; Lin-Wen Yi; Qiu-Xia Huang; Xing-Meng Luo; Xiao-Bing Su; Lin Hu; Wen-Ting Li; Xiang-Zhong Huang; Meng-Yuan Jiang (Natural Product Research, 2026)

Rockburst mitigation by microwave destressing in a deep drill-and-blast tunnel: thermal–damage–stress evolution with a slotted-wall coaxial applicator - Yuntan Ao; Xia-Ting Feng; Shiping Li; Xiaojun Zhang; Juan He; Tianyang Tong; Yifan Zhang; Feng Lin (Tunnelling and Underground Space Technology, 2026)

Curcumol induces autophagy-dependent hepatic stellate cell death through methionine metabolism disruption - Yi-jie Gao; Ya Zhou; Yi-ning Li; Kai-yao Yang; Si-wei Xia; Meng-ru Hu; Yang Li; Li Chen; Fei-xia Wang; Shuai Lu; Na-qi Lian; Shi-zhong Zheng; et al. (Toxicology and Applied Pharmacology, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Unveiling small-scale tropical forest loss and post-loss recovery in the Congo Basin - Yihang Zhang; Xiaodong Li; Feng Ling; Xia Wang; Yun Du; Peter M. Atkinson (Global Environmental Change, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

Rice-crab co-culture mitigates reactive gaseous N losses and increases economic benefits - Feng Zhang; Guimin Xia; Yuanze Qiu; Hongwei Han; Haixia Liu; Benji Yi; Bohao Li; Daocai Chi; Taotao Chen (Field Crops Research, 2026)

Synergistic mechanisms of bacteria and fungi in the biodegradation of Benzo[a]pyrene: Insights from metagenomic and metabolomic analyses - Yeliang Dai; Jibing Li; Xiyu Wang; Feng Xia; Ji Zheng; Chaofeng Shen (Environmental Research, 2026)

A diatom-inspired tissue adhesive for wound sealing and hemostasis under extreme physiological conditions - Furui Qu; Xiaojie Sun; Mingxia Feng; Xiaoye Wang; Yan Zhang; Zicheng Xia; Yang Yang; Xiguang Chen; Na Li; Chao Feng (Chemical Engineering Journal, 2026)

Trace iron-induced electron delocalization metallization on the BN surface for hyper integrated C-band wideband absorber - Hui Gao; Chunyan Ding; Junyu Shen; Guohao Wu; Mingyang Fan; Zhuoyang Li; Long Xia; Guangwu Wen; Feng Xu; Xiaoxiao Huang (Chemical Engineering Journal, 2026)

Mechanism of toxicity of TiO2 nanoparticles exposure on restraining bone growth of young rats: acting on HDAC9 nucleocytoplasmic translocation-mediated p53 deacetylation involving in growth plate chondrocyte differentiation and ferroptosis - Lihua Feng; Jinghua Luo; Xiangxiang Chen; Yanan Xia; Yunping Xu; Yange Li; Yang Liu (Chemico-Biological Interactions, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Deformation and Reconstruction of Coastal Typhoon Wind Fields in Hangzhou Bay - Li Li; Jiayi Guo; Zhiguo He; Tao Feng; Yuezhang Xia; Honghua Zou; Yaping Zha; Rong Zhou; Ye Zhu; Wenjun Zhu (Journal of Marine Science and Engineering, 2026)
Coastal typhoon deformation plays a critical role in determining typhoon tracks, intensity changes, precipitation and related flooding, storm surges, and typhoon waves, and thus is highly associated with coastal disaster patterns. This study proposes a three-level framework for typhoon wind field modeling through the integration of geometric characterization with physical-informed reconstruction. At its core, an elliptical fitting method is developed based on second-order moments to quantify the structural asymmetries. This geometric fitting method is incorporated into the reconstruction method of Holland–Miyazaki, creating a physically consistent model capable of simulating typhoon deformation processes during landfall. Validation through high-resolution Weather Research and Forecasting (WRF) simulations of Typhoon Chan-hom (2015) demonstrates the framework’s effectiveness, capturing elliptical eyewall deformation with aspect ratios exceeding 1.5, primarily driven by coastal topography and surface friction interactions. The method is further validated through Typhoon Mitag (2019), with mean wind component errors below 1 m/s, the average correlation coefficients surpassing 0.9, and wind direction mean absolute errors largely below 10°. This research provides a practical framework for quantifying and characterizing the wind field deformation during typhoon landfall in coastal regions, thereby supporting ther operational forecasting and disaster reduction in vulnerable coastal regions.

Effects of urban forest structure on land surface temperature: Subtropical versus temperate cities - Xuefeng Kang; Jun Yang; Yuqing Zhang; Qiyue Zou; Zhe Li; Yanchu Feng; Xiangming Xiao; Jianhong (Cecilia) Xia (Urban Forestry & Urban Greening, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

PpZAT10 inhibits PpTST1 expression to regulate sugar accumulation in peach (Prunus persica) fruit - Qinqi Liu; Beibei Feng; Liuqing Han; Dongsheng Wang; Kexin Liu; Xiaobei Wang; Nan Hou; Lei Wang; Xianbo Zheng; Xiaodong Lian; Jun Cheng; Wei Wang; et al. (Plant Science, 2026)

Seven undescribed metabolites from Ganoderma lucidum-derived endophytic Talaromyces sp. GLQ04 and their anti-DLBCL (diffuse large B-cell lymphoma) activities - Shan Liu; Hao Sun; Pei-Ting Li; Pei-Shan Li; Xia Cheng; Feng Wang; Qi Luo (Phytochemistry, 2026)

Enhanced peracetic acid activation by phosphorylated zero-valent iron-copper foam for levofloxacin removal from sewage sludge: Electron transfer regulation and functional synergy - Zixuan Zhao; Can Xu; Xing Huang; Dan Li; Likui Feng; Yujia Du; Xinhui Xia; Daxin Zhao; Mika Sillanpää; Liangliang Wei (Journal of Hazardous Materials, 2026)

Continuous production of multiple high-value bioactive compounds using mixotrophic Auxenochlorella pyrenoidosa in chemostat: Insights from photosynthetic performance - Jing Xia; Xiu Gao; Feng Chen; Haojie Hu; Ji Li; Jinlin Liu (Journal of Environmental Chemical Engineering, 2026)

An experimental study on the effect of the length-to-diameter ratio on the post-peak behaviour of rock - Charlie C. Li; Lei Shi; Yanchun Yin; Tongbin Zhao; Xia-Ting Feng (International Journal of Rock Mechanics and Mining Sciences, 2026)

Multi-task prediction framework for microseismic time series data based on hybrid signal decomposition and adaptive loss function - Wenhao Xia; Yang Li; Weidong Song; Cuifeng Du; Chao Zhang; Chi Zhang; Zhuozhi Xiang; Jianxin Feng (International Journal of Rock Mechanics and Mining Sciences, 2026)

In situ performance of wicking geotextile in seasonally frozen railway embankment - Hongguang Jiang; Pengju Tang; Taifeng Li; Shun Liu; Yiyi Liu; Haojie Feng; Xia Liu; Zhanyong Yao (Geotextiles and Geomembranes, 2026)

Structure-guided discovery of neutralizing epitopes enables rational design of a multi-epitope nanoparticle vaccine against SVCV - Yu-Ya Li; Liang Zhao; Xue-Feng Wei; Xiao-Hang Ren; Jun-Yao Xia; Zhao Zhao; Bin Zhu (Fish & Shellfish Immunology, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

The health threat of wild animals by Rank I ARGs from habitat soils: Metagenomic and metabolomic evidence - Jiaying Ma; Han Zhang; Sumei Liang; Xinxin Feng; Zhaoyang Xia; Hong Li; Shuzhen Zou; Dayong Li (Environmental Pollution, 2026)

A LINE-1 retrotransposon promotes SEMA3C expression as a cis-regulatory enhancer to sustain breast cancer stem cell survival - Qidong Xia; Jingwei Feng; Jiayao Pan; Wen Deng; Xiaoqi Weng; Jianhui Jiang; Lin Wang; Wenqian Xie; Yi Chen; Aiwei Bi; Jiang Li; Yiwen Lu; et al. (Science China Life Sciences, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

PpBRC1 negatively regulates branching via modulating GA signal transduction gene PpGID1b in peach (Prunus persica) - Yulu Wu; Yajia Zhang; Junjie Zhang; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Nan Hou; Xianbo Zheng; Jun Cheng; Wei Wang; Langlang Zhang; Xia Ye; et al. (Plant Cell Reports, 2026)

Sequence Stratigraphy, Sedimentary Evolution and Controlling Factors of the Shan-1 Member in Permian Shanxi Formation, Qingyang Gas Field, Ordos Basin, Central China - Qian-qian Fan; Shi-qiang Xia; Hui Xia; Wei Wang; Long Wang; Yan Wang; Shi-cheng Wang; Shuai-shuai Feng; Wei Zhang; Ya Li; Ping Liu; Qian-yun Dong (Applied Geophysics, 2026)

Development and Verification of a True Triaxial Apparatus for Simulating Complex Stress Paths, Long-Term Loading, and Conventional Testing in Hard Rock - Jun Zhao; Junhao Li; Xia-Ting Feng; Tianyu Chen (Rock Mechanics and Rock Engineering, 2026)

Clinical study on the interaction between iron metabolism and neuroinflammation and iron deposition in the substantia nigra of Parkinson’s disease - Yani Yao; Jiayi Li; Jiaoyang Yan; Qian Cai; Yuling Wang; Huan Xia; Tingting Feng; Peishan Li; Xinling Yang (Brain Imaging and Behavior, 2026)

Red Sea bream iridovirus (RSIV) infection elicits cell death modes—Apoptosis and ferroptosis in silver Pomfret (Pampus argenteus) - Yuanbo Li; Youyi Zhang; Wuqiang Xia; Ting Chen; Zukang Feng; Denggui Chen; Fangjun Xu; Man Zhang; Yajun Wang; Xiaojun Yan; Jiabao Hu (Aquaculture, 2026)

Integrating metabolomics, proteomics, transcriptomics, and genomics to enhance the flavor-modulating capacity of lactic acid bacteria in fermented beverages - Yue Zhang; Mingxue Sun; Yin Feng; Wei Wang; Yamei He; Haihua Shi; Yanxin Zhu; Bo Nan; Xia Li; Jingsheng Liu; Yu Wang; Yuhua Wang (Trends in Food Science & Technology, 2026)

A novel dynamic pollution risk assessment method for potential pollution areas in industrial parks: Integrating long-time-series remote sensing imagery and driver analysis - Siying Wang; Qi Han; Tianxiang Xia; Liqiu Zhang; Li Feng (Journal of Hazardous Materials, 2026)

Experimental study on microwave-assisted mechanical fragmentation of simulated vesicular mare basalt - Liang-Xiao Chen; Zheng-Wei Li; Xia-Ting Feng; De-Tian Li; Cheng-Dan He; Xian-Qiang Li; Yong-Jun Wang; Wen-Feng Guo; Jian Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Characterization of volatile flavor compounds and sensory profiles in braised thigh meat and soup between fast- and slow-growing chickens at marketable age - Li Liu; Xiaoming Wang; Shengyuan Guo; Yongjian Xia; Lin Zhang; Liang Zhao; Tong Xing; Feng Gao (Food Chemistry, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

Synergistic coupling of micellar confinement and interfacial adsorption for fabricating high-density spherical nickel (II) tricarbohydrazide perchlorate - Jie-xin He; Dong-xu Zhang; Feng-yi Xia; Ri-lige Su; Bo-bo Lu; Jia-ni Xie; Zi-jie Bi; Qian-you Wang; Li Yang (Chemical Engineering Journal, 2026)

Tris(2,4-di-tert-butylphenyl) phosphate induces cardiac injury in juvenile mice by disrupting energy homeostasis: Focus on mitochondrial impairment - Xiangxiang Chen; Yanan Xia; Lihua Feng; Haoneng Li; Yang'e Li; Shixiang Huang; Hengyi Xu; Yang Liu (Chemico-Biological Interactions, 2026)

Proangiogenic effect and molecular mechanism of a new cytosporin derivative from the marine fungus Eutypella sp. D-1 - Xiaoyue Sun; Ranran Zhu; Qijia Feng; Peihai Li; Yun Zhang; Qing Xia; Kechun Liu; Xuehui Jian; Yuanshuai YU; Xue Wang; Chen Sun; Haobing YU (Medicinal Chemistry Research, 2026)

Lightning characteristics and genesis analysis during a bohai sea-effect snow event - Guili Feng; Yu Wang; Rufeng Xing; Fan Xia; Zhuling Sun; Tianji Su; Fengquan Li (Meteorology and Atmospheric Physics, 2026)

MRI In Vivo Detection of Amyloid-β Protein Deposition in Different Brain Regions of Patients with AD and MCI - Qingning Yang; Zhongrui Wang; Tie Deng; Yuwei Xia; Feng Shi; Junbang Feng; Chuanming Li (Brain Topography, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Seasonal shifts in phytoplankton community assembly mediated by hydrological connectivity in a sluice-regulated distributary estuarine network—as a case in the Pearl River Estuary - Yanzi Cai; Xia Li; Guogui Chen; Yiliang Xie; Yujia Zhai; Tian Xie; Mingyu Wang; Fang Gao; Meili Feng; Ying Man; Baoshan Cui (Journal of Hydrology, 2026)

Microwave melting of lunar regolith simulant in an unchambered environment: Insights from physical model experiments - Jia-Qi Lu; Zheng-Wei Li; Xia-Ting Feng; Cheng-Dan He; Yong-Jun Wang; Yang Zuo; Jin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Quality improvement of minced pork during glassy-state frozen storage with high glass transition temperature induced by tara gum - Xiufang Xia; Youling Feng; Tingting Zhang; Wuyun Chen; Weiwei Liang; Fangfei Li (Food Research International, 2026)

Effect of magnetic field-assisted freeze–thaw processing on the protein oxidation and muscle structure of yellowfin tuna - Xue He; Meihui Zhao; Li Liu; Haohao Shi; Zhongyuan Liu; Aiguo Feng; Guanghua Xia (Food Chemistry, 2026)

A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

Integrated metallurgical process for direct preparation of high-entropy-doped LiMn Fe1-PO4 cathode materials from iron-rich manganese slag - Ding-hao Le; Qing Wen; Chao Sun; Yu-jin Chen; Pei-yao Li; Jie-xi Wang; Jia-feng Zhang; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2026)

Development of Polyethylene Glycol-Modified Liposomes of Phenolic Glycoside 1 for Enhanced Anti-Aging Effect - Qilong Wang; Mingjie Gong; Jiaying Li; Tingyuan Li; Xia Jiang; Xiaowen Wang; Qinyang Hua; Elmurat Toreniyazov; Feng Shi; Jiangnan Yu; Xia Cao; Ximing Xu; et al. (Journal of Pharmaceutical Innovation, 2026)

Large-Scale Signal Detection and Personalized Risk Prediction for Cardiovascular Drug Adverse Reactions in Elderly Patients: Real-World Evidence from Western China - Zimeng Li; Shuzhi Lin; Yifang Shen; Lin Yin; Qian Liu; Tian Sun; Xingfang Xia; Bianling Feng (Cardiovascular Toxicology, 2026)

Neural dynamics in tinnitus: differential effects of hearing status on temporal brain activity variability - Haoliang Du; Xiaoyun Qian; Xia Gao; Chenjie Yu; Junguo Wang; Ao Li; Yajun Gu; Xu Feng (Brain Imaging and Behavior, 2026)

The effect of intranasal oxytocin on the neuropsychological substrates of intergroup categorization - Yuhe Wang; Xia Tian; Yuqing Zhou; Zixin Zheng; Xiaoqing Li; Ruida Zhu; Jiaxin Shi; Ruolei Gu; Wenbo Luo; Chunliang Feng (Brain Imaging and Behavior, 2026)

Dual-functional FeMgAl-LDH/peroxydisulfate system for simultaneous carbon and phosphorus recovery from sludge anaerobic fermentation - Dan Li; Yuxin Li; Wei Xia; Weixin Zhao; Xinhui Xia; Zixuan Zhao; Likui Feng; Heng Liang; Haijiao Xie; Liangliang Wei (Water Research, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Unveiling a macrophage-driven inflammatory dysregulation: NF-κB-mediated hyperinflammation links 6PPD-Q exposure to viral immunopathology - Xia-Wen Qiu; Jiajun Chen; Jiayan Wang; Yujie Li; Xiaoyan Qi; Xianchang Zeng; Huajun Feng; Xianghui Kong (Journal of Hazardous Materials, 2026)

A machine learning framework bridging heavy metal contamination and human health risks in agricultural soils of the Yangtze River Delta (2001–2030) - Luming Xiao; Pu Feng; Yuehong Liang; Bing Xia; Yang Ye; Huijun Liu; Wenlu Zhao; Zhiheng Li; Kaiming Cheng; Jie Chen (Journal of Hazardous Materials, 2026)

Depositional environments of a mixed siliciclastic-carbonate system: A case study of the late Ediacaran sedimentary succession in the northern Sichuan Basin (SW China) - Junxin Shang; Mingyou Feng; Xingzhi Wang; Maolong Xia; Yong Li; Junlang Chen; Chao Zhang; Xiaohong Liu (Journal of Asian Earth Sciences, 2026)

Dynamic distribution patterns and release behavior of adsorbed gas/free gas during deep coalbed methane production - Cunlei Li; Zhaobiao Yang; Xia Yan; Geoff Wang; Daojun Huang; Benju Lu; Baoxin Zhang; Shuailong Feng; Jianan Wang; Changqing Liu; Xiaolei Liu (Fuel, 2026)

Synergistic technology of liquid nitrogen condensation integrated with pressure swing adsorption for CH4/VOCs recovery: modeling, experiment, and optimization - Suiyang Han; Weiqiu Huang; Xufei Li; Yankang Zhou; Xinchen Tian; Zhanyou He; Fangrui Feng; Ping Xia; Wenlong Xu (Fuel, 2026)

Twenty-year field evidence reveals crop-specific impacts of conservation tillage on yield in a rice-wheat system - Yalin Yu; Menghan Dong; Yuanchang Xia; Bin Sun; Yanling Li; Ahmad Latif Virk; Haishui Yang; Feng-Min Li; Shiping Liu; Zheng-Rong Kan (Field Crops Research, 2026)

Formaldehyde detoxification by the moss Racomitrium japonicum - Tiefeng Chai; Feng Lu; Xin Deng; Ningyuan Fei; Xia Hu; Hongxia Xia; Wanting Li; Ke Chen; Ying Dai; Muhammad Ibrar; Yanbao Lei (Environmental Research, 2026)

Polysaccharides from Syzygium aromaticum binding to 3CLpro contain glycoproteins interacting with RdRp against SARS-CoV-2 - Can Jin; Bo Feng; Pengfei Dou; Yuan Zhou; Tingting Guo; Yuxuan Liu; Yaqi Ding; Meixia Li; Xia Chen; Zhenyun Du; Chunfan Huang; Xuan Li; et al. (Carbohydrate Polymers, 2026)

Enhanced Chaetoceros muelleri growth using optimized fermented agricultural waste - Yong Feng; Keyi Li; Yutong Xia; Ping Wu; Zhen Wang; Shuhao Huo; Guoqiang Guan; Huayou Chen (Systems Microbiology and Biomanufacturing, 2026)

A Comprehensive Study of AAV Tropism in the Marmoset Brain - Kailun Fang; Hailin Liu; Yuting Yao; Zhen Xu; Xinyu Liu; Canbin Feng; Yuanhua Liu; Tong Li; Guannan Geng; Ruoxi Wu; Junhui Xia; Fan Yang; et al. (Neuroscience Bulletin, 2026)

D-amino acids enhance the biocidal effect of free nitrous acid to realize sulfide control in sewers - Weiqi Zhang; Runze Li; Juntao Xia; Jianliang Sun; Zhensheng Liang; Feng Jiang (Water Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Global, regional, and national burden of hepatocellular carcinoma and contribution of nine modifiable risk factors across 185 countries/territories in 2022 - Ping Li; Zhan Ding; Yuqi Feng; Xiangyu Ren; Yongyue Wei; Changfa Xia; Yitao Yang; Quanbo Yang; Zhe Wang; Xuehong Zhang; L.G. van der Geest; Herbert Yu; et al. (Science Bulletin, 2026)

Bell-shaped response of mercury methylation to sulfate loading in urban sewer systems: Implications for source-level control - Juntao Xia; Cheng Li; Yuming Zhen; Ming Liu; Jiahua Guo; Feng Jiang (Journal of Hazardous Materials, 2026)

Association of phthalate and substitute exposure with gestational liver function: A longitudinal cohort study - Xingxing Feng; Yuming Wang; Qi Chen; Hongbo Xu; Yanjian Wan; Yuanyuan Li; Hongxiu Liu; Shunqing Xu; Yan Zhou; Wei Xia (Environmental Research, 2026)

Multiple resonance thermally activated delayed fluorescence emitters containing novel S-based acceptor with narrowed FWHM and enhanced EQE - Xiao-Xue Xia; Guo Yuan; Feng-Ming Xie; Qiang Zhang; Yan-Qing Li; Ze Hua; Jian-Xin Tang; Xin Zhao (Chemical Engineering Journal, 2026)

Dual-functional tandem luminescent solar concentrators with photovoltaics and linear ultraviolet response for self-powered ultraviolet monitoring - Kaijie Chen; Haotian Guo; Shichao Huang; Kaitian Zhao; Yuge Feng; Fan Liu; Shuhong Xu; Pengfei Xia; Chongwen Li; Chunlei Wang (Chemical Engineering Journal, 2026)

Dual-modal antioxidant nanozyme hydrogel for protection against noise-induced hearing loss via attenuation of oxidative stress and NF-κB/MAPK signaling - Liang Xia; Ru Tang; Yi Chen; Ning Ma; Lili Xiao; Xiaoyan Chen; Xiaoyin Mao; Keyi Li; Yanmei Feng; Jingjing Liu; Amin Zhang (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

A R2R3-MYB transcription factor SmMYB88 of Solanum melongena regulates cold tolerance by activating antioxidant system - Yanhong Lan; Fangyi Gong; Rongjiang Dong; Chun Li; Feng Xia; Yifan Li; Xiaojun Liu; Duchen Liu; Genyun Liang; Chao Fang; Peng Cai (Plant Cell Reports, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Development of a Novel Experimental System for Simulating the Whole Grouting Process of Diffusion–Filling–Splitting in Deep Rock Engineering - Xia-Ting Feng; Xi-Fan Li; Yang-Yi Zhou; Cheng-Xiang Yang; Tian-Xiang Song (Rock Mechanics and Rock Engineering, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Trade-offs and synergies of ecosystem services in the water conservation area in the upper reaches of the Yangtze River based on Bayesian network: Identification and diagnosis of driving factors and spatial optimization - Li Yue; Feng Xia; Tian Yichao; Qiu Lin; Liu Jinglan (Process Safety and Environmental Protection, 2026)

Cyproflanilide, a novel meta-diamide insecticide, overcomes multiple insecticide resistance in Cnaphalocrocis medinalis: Evidence from comparative toxicity assays and genome-edited Drosophila - Wen-Chao Ge; Guang-Hang Chen; Bei-Bei Dong; Hong-Shuang Li; Meng-Zhen Wang; Feng-Xia Yang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Quantification and visualization of micro- and nano-plastics transfer from maternal to fetal: A rat model study - Yudong Feng; Di Wu; Quanquan Guan; Qing Wang; Qing Xu; Ruijie Li; Chen Tu; Xiangliang Pan; Jamie L. Inman; Antoine M. Snijders; Bo Hang; Willie J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2026)

Method for predicting the microwave heating sensitivity of hard rocks: Application to microwave-mechanical excavation and microwave stress release in tunnels - Shiping Li; Xia-ting Feng; Chengxiang Yang; Feng Lin; Xiangxin Su; Tianyang Tong; Jiuyu Zhang (Journal of Applied Geophysics, 2026)

Phosphatase-like Ce4+@UiO-66-NH2 nanozyme-based dual-mode hydrogel nanosensor for visual detection of paraoxon - Wenjing Li; Mengqing Xu; Zhuoyun Xia; Zheng Wang; Yingying Feng; Hui Li; Chuang Jiang; Yingnan Liu (Food Chemistry, 2026)

RETRACTED: “Enhanced heavy oil recovery and CO2 geological sequestration by dimethyl ether-assisted CO2 flooding” - Haojie Xia; Shaoqi Kong; Ruixue Feng; Kunjie Li; Yueliang Liu (Chemical Engineering Journal, 2026)

Mitigating the thermal environment in built-up local climate zones: Expanding from internal to surrounding greenspace - Xuefeng Kang; Jun Yang; Yuqing Zhang; Zhe Li; Yanchu Feng; Xiangming Xiao; Jianhong (Cecilia) Xia (Building and Environment, 2026)

TMC6 Protects Against Ischemic Neuronal Injury by Activating Rap1/Rac1 Signaling to Restore Mitochondrial Dynamics and Mitophagy - Xuemei Quan; Huo Liang; Haiyin Long; Xiawei Wang; Liling Feng; Xia Zhou; Yuan Chen; Yanhua Li; Xiaofeng Li (Molecular Neurobiology, 2026)

HM568 Enhances NAD+ Biosynthesis to Ameliorate Mitochondrial Dysfunction and Neurotoxicity in Parkinson's Disease Models: A Putative Link to PARP1 Modulation - Minpeng Li; Wei Li; Yingjie Liu; Tingyuan Fu; Kaiye Peng; Changmei Wang; Jing Zhang; Yifan Feng; Xia Wu (Molecular Neurobiology, 2026)

Verbascoside (VB) Inhibits Ischemic Stroke Progression via Suppression of Cell Damage and Ferroptosis By Targeting LCN2/ALOX5/SLC7A11/GPX4 Expression - Cheng Zhang; Jian You; Xia Zhou; Jiaxing Feng; Qiang Li; Hongwei Zhou (Molecular Neurobiology, 2026)

Impact of dendrobium nobile supplementation on antioxidant activity and egg-laying performance in late-laying hens - Gang Feng; Yushi Shi; Depeng Zhao; Xia Long; Qisong Tan; Jinlin Yang; BeiDa Zhou; Hui Li (Animal Reproduction Science, 2026)

Structural characteristics of polysaccharides from Neolitsea cassia (L.) Kosterm. residue extracted by alkali and their immunomodulatory effects on RAW 264.7 cells - Lu Yu; Rongbing Huang; Jixiao Zhang; Xiuli Wang; Feng Xiong; Mingguo Jiang; Hock Eng Khoo; Xia Li (Natural Product Research, 2025)

Impacts of intermittent electrical stimulation on continuous electro-anaerobic digestion from wastewater: performance and multi-omics insights - Chao Wang; Ao Xia; Dong Feng; Lei Li; Jingmiao Zhang; Yun Huang; Xianqing Zhu; Xun Zhu; Eric Trably; Qiang Liao (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

ABC transporter BmWh2 enhances antiviral defense against baculovirus in silkworm via ATG upregulation - Dandan Feng; Huizhen Guo; Jie Li; Jiayi Liu; Dan Zhao; Hui Zhao; Xinyi He; Qingyou Xia; Liang Jiang (Pesticide Biochemistry and Physiology, 2025)

LVIMOT: Accurate and robust LiDAR-visual-inertial localization and multi-object tracking in dynamic environments via tightly coupled integration - Shaoquan Feng; Xingxing Li; Zhuohao Yan; Yuxuan Zhou; Chunxi Xia (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Analysis of volatile metabolites and differences in aroma quality of green tea, black tea and oolong tea prepared from highly aromatic tea variety (Dancong) - Suwan Zhang; Hongling Xia; Shili Sun; Chenying Ma; Feng Li; Shunshun Pan; Zhenbiao Zhang; Xingfei Lai; Qiuhua Li; Mengjiao Hao; Lingli Sun; Ruohong Chen (Food Research International, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Identification of polyester oligomers in laminated steel and their migration into food simulants - Jiaqi Li; Jianing Feng; Changjun Wang; Yifan Cheng; Chunfeng Lv; Canming Li; Kai Qiu; Gang Wu; Yining Xia (Food Packaging and Shelf Life, 2025)

Associations between PM2.5 components, temperature, and semen quality: Insights from seminal plasma metabolome - Jun-feng Tan; Li-li Huang; Zhong-Hua Lu; Hang-Yu Xiang; Hong Yang; Hai-Xia Zhou; Tian-qing Meng; Cheng-liang Xiong; Yi-Xin Wang; Jie Zhang (Environmental Research, 2025)

Three-dimensional elastoplastic constitutive modeling of green sandstone within ductile domain - Jiacun Liu; Lei Zhu; Han Gao; Jie Feng; Xing Li; Kaiwen Xia (Computers and Geotechnics, 2025)

Environmental chromium and cadmium co-exposure induces GADD45A-mediated rDNA instability in human cohorts and cell models - Yongxin Li; Yao Qin; Chuyan Zhang; Chan Ding; Minqian Feng; Yifan Dou; Xinran Wang; Xia Rao; Xiaoxue Gong; Zhaoqiang Jiang; Jianlin Lou; Huadong Xu (Chemico-Biological Interactions, 2025)

Top-down inversion of urban-scale sectoral methane (CH4) emissions and their response to environmental drivers - Wenxin Zhao; Zhiye Xia; Yanqing Xu; Kenan Li; Ziheng Huang; Feng Xie; Yuchen Li; Chao Li (Atmospheric Environment, 2025)

Mechanism of Axial Chain Rockbursts in Deep Tunnels: Structural Plane-Induced Stress Concentration Triggered by Drilling and Blasting - Hong-Pu Li; Ben-Guo He; Xia-Ting Feng; Wen-Jing Niu; Tao Ma (Rock Mechanics and Rock Engineering, 2025)

Botany, traditional uses, phytochemistry, pharmacological activities, and toxicity of the mangrove plant Avicennia marina: a comprehensive review - Pan Zhou; Huihui Hu; Xia Wu; Zhenhui Feng; Xingyan Li; Samad Tavakoli; Kefeng Wu; Luming Deng; Hui Luo (Phytochemistry Reviews, 2025)

Geodynamic Simulation of the Pulang Porphyry Deposit in Southwest China: Implications for Ore Genesis and Exploration - Shuai Leng; Qinglin Xia; Tongfei Li; Xiaocheng Wang; Mengyu Zhao; Feng Zhang (Journal of Earth Science, 2025)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Light-based improvement technology for postharvest fruits and vegetables flavor and regulation mechanism: a review - Yafei Wang; Yunting Li; Yao Feng; Zhenshan Hou; Rongrong Xia; Zijian Wang; Naizhu Liu; Aijuan Pan; Xina Cong; Guanlin Qian; Miao Yan; Heran Xu; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Bioactive secondary metabolites from an endophytic fungus Chloridium virescens GLQ05 and structural revision of alteamide - Shan Liu; Pei-Ting Li; Peishan Li; Xinhuan Qiu; Xia Cheng; Qi Luo; Feng Wang (Natural Product Research, 2025)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Evolution of water-carrying capacity and response law of land space pattern in the Three Gorges Reservoir Area - Feng Zhou; Wanshun Zhang; Xin Liu; Hong Peng; Han Xia; Ao Li; Gang Chen; Hao Wang (Land Use Policy, 2025)

Transformation of landfill leachate into in-situ iron-carbon galvanic stabilizer for effective remediation of mercury-contaminated soils: a sustainable solution - Dongping Song; Tao Huang; Chenglong Wang; Yun Xia; Xiaolong Sun; Chong Luo; Weihua Liu; Shihong Xie; Yuxuan Feng; Kai Chen; Jialin Cui; Shouze Li (Environmental Research, 2025)

Photocatalytic chitosan/hydroxypropyl methylcellulose-based multifunctional film incorporated with chlorophyll-TiO2@carbon sphere dual heterojunction and L-arginine for banana preservation - Haoran Wang; Wei Ji; Feng Xiao; Yewen Xiao; Linlin Li; Xia Shu; Hualin Wang; Jun Yin (Chemical Engineering Journal, 2025)

Electrolyte design for highly reversible zinc anodes via prismatic plane growth and nucleation kinetics regulation - Mingyu Shao; Xinrui Ma; Yiming Jiang; Yu Tian; Wenquan Ding; Jin Liu; Feng Qiao; Junyu Zhu; Yaning Li; Xiaocun Liu; Jian Liu; Bo Li; et al. (Chemical Engineering Journal, 2025)

High performance moist-electric generator based on supramolecular hydrogel and optimized ion regulation strategy - Ning Wei; Jiacheng Feng; Zhuangzhuang Zhou; Mengmeng Ren; Hao Liu; Mengmeng Li; Chao Lv; Hong Xia (Chemical Engineering Journal, 2025)

Integrating methane conversion with multi-pathway nitrogen removal for wastewater in membrane-enabled stratified biofilm: System development and microbial dynamics - Chun-Yan Yuan; Yu-Xia; Jia-Hao Huo; Cai-Long Nie; Ke-Xin Zhang; Liang-Feng; Xiao-Li Su; Zi Song; Gen-Ping Yi; Fei-Yun Sun (Bioresource Technology, 2025)

Association between ambient air pollution and ischemic stroke hospitalization: A multicenter case-crossover study in Tianjin, China - Fuyin Wang; Kun Hua; Yingze Tian; Miaomiao Wei; Xiaoshuang Xia; Lin Wang; Yinchang Feng; Xin Li (Atmospheric Environment, 2025)

Root-specific CsATs enhances acylated flavonol-glycoside accumulation to promote aluminum tolerance in tea roots - Qiankun Pan; Dexu Kong; Xiu Li; Yi Cao; Xiangcheng Kong; Ting Feng; Wenzhuo Wang; Caifeng Yu; Tao Xia; Xiaolan Jiang (Plant Science, 2025)

A formula for quantifying the overflow discharge capacity of street inlet in a surcharged urban drainage system - Zheng Xu; Junqiang Xia; Qijie Li; Jiheng Feng; Boliang Dong (Journal of Hydrology, 2025)

Prospective associations of in utero exposure to multiple insecticides with cord blood mitochondria DNA copy number and longitudinal offspring telomere length shortening - Feng Qiu; Yanjian Wan; Aizhen Wang; Gaga Mahai; Yujie He; Wensi Zhou; Ying Zhu; Wei Xia; Shunqing Xu; Yuanyuan Li (Journal of Hazardous Materials, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Evolution of global O3-NOx-VOCs sensitivity before and after the COVID-19 from the ratio of formaldehyde to NO2 from satellite observations - Dakang Wang; Dongchuan Pu; Isabelle De Smedt; Lei Zhu; Xiankun Yang; Wenfu Sun; Hui Xia; Zhaolong Song; Xicheng Li; Juan Li; Aoxing Zhang; Xu Feng; et al. (Journal of Environmental Sciences, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Development and evaluation of a novel sensor for noninvasively investigating corn ear dehydration - Yang Xiang; Liu-Deng Zhang; Hai-Ying Zheng; Ao-Wen Wang; Ke-Lei Xia; Zhong-Yi Wang; Lan Huang; Li-Feng Fan (Computers and Electronics in Agriculture, 2025)

Chronic low-level exposure to Pb, Hg, and Cd mixture triggers brain premature aging in rat - Jie Xie; Lu Ouyang; Jiajun Li; Shuo Yang; Qi Li; Yue Li; Lingyu Yan; Yihong Fu; Qijun Li; Yuting Xia; Xinling Chen; Ziyang Fu; et al. (Toxicology, 2025)

Ambient air pollution, dietary patterns, and the risk of incident cerebrovascular diseases: A prospective cohort study - Bolun Cheng; Wenming Wei; Chuyu Pan; Li Liu; Shiqiang Cheng; Xuena Yang; Peilin Meng; Boyue Zhao; Jinyu Xia; Yan Wen; Feng Zhang (Science of The Total Environment, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Recent advances in tailings waste as geopolymers for construction: Current challenges and prospects - Zheyuan Feng; Zhibo Zhang; Weixin Li; Guodong Hao; Xiaoning Xia; Pengwei Li; Kai Zhu (Minerals Engineering, 2025)

Spatial-temporal distribution of resources and the relationship between environmental factors of Portulus trituberculus in the Yangtze River Estuary - Zuchang Yang; Guangpeng Feng; Jian Shao; Gang Yang; Tao Zhang; Feng Zhao; Zhi Geng; Xia Li; Qingyuan Tan (Marine Environmental Research, 2025)

Adsorption and coarsening of gold nanoparticles in iron (oxyhydr)oxides lead to high-grade gold mineralization - Feng-Xia Huang; Ya-Fei Wu; Katy Evans; Anthony E. Williams-Jones; Xin-Fu Zhao; Yong Wei; Wei Feng; Jian-Wei Li (Geochimica et Cosmochimica Acta, 2025)

Chitosan/PEO@Eu-MOF nanofiber membrane-based test strip for visual detection of tetracycline with smartphone-assisted analysis - Wei Pan; Zi-Han Zhu; Yan-Shen Zhao; Jie-Liu; Zhi-Guang Zhang; Gui-Xia Li; Tao Yu; Zhong-Zhi Han; Yun-Ze Long; Gui-Feng Yu (Chemical Engineering Journal, 2025)

Dynamic-environment-adaptive triboelectric nanogenerator utilizing wind-water energy synergy - Xiao Xia; Hengyu Li; Xin Guo; Shuaicheng Guo; Yanrui Zhao; Yang Yu; Jinzhi Zhu; Yuqi Wang; Yunlong Zha; Yuming Feng; Xiaohui Lu; Tinghai Cheng (Chemical Engineering Journal, 2025)

Field Tests Using High-Power Microwaves to Crack Iron Ore of Different Grades - Feng Lin; Xia-Ting Feng; Shi-Ping Li; Tian-Yang Tong; Yun-Tan Ao; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2025)

Sexually Dimorphic Cellular Architecture and Neural Circuity of ovBNST Proenkephalin Neurons - Limei Song; Yuqing Zhang; Mengqi Feng; Wenwen Su; Riming Zhu; Bin Zhang; Xia Zhang; Jie Li (Neuroscience Bulletin, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Global warming changes patterns of runoff and sediment flux in Tibetan Yangtze River headwater - Yinjun Zhou; Junfeng Han; Feng Wang; Xisheng Liu; Yujiao Liu; Xia Yan; Guoshuai Zhang; Junxiao Ma; Tong Wei; Zhongwu Jin; Zhijing Li; Dongfeng Li; et al. (Journal of Hydrology, 2025)

Association between nitrogen dioxide exposure and out-of-hospital cardiac arrest onset in China: A multicenter, time-stratified, case-crossover study - Chang Pan; Xinyue Li; Xuan Zhang; Jiaqi Zheng; Ruixue Song; Ziyang Zhang; Renjie Chen; Haidong Kan; Feng Xu; Yuguo Chen; Xia Meng (Journal of Hazardous Materials, 2025)

Acclimatization of salt-tolerant bacteria in a pilot-scale biological treatment system for actual high-salinity wastewater from a chemical industrial park - Yifan Feng; Chunlei Yang; Jun Li; Xinchun Ding; Ruize Xia; Min Hu; Yechao Tian; Yang Pan; Quanxing Zhang; Aimin Li (Journal of Environmental Chemical Engineering, 2025)

Nature-inspired silicone-polythiourethane coatings based on capsaicin analogue for marine biofouling control - Kang Feng; Sheng Li; Najla AlMasoud; Jiaying Li; Yue Ma; Congying Yin; Zeyu Jie; Yiding Wang; Taghrid S. Alomar; Xia Li; Haoyi Qiu; Zeinhom M. El-Bahy; et al. (Chemical Engineering Journal, 2025)

Bisulfite-free whole-genome mapping of 5-methylcytosine at single-base resolution by NTD-seq - Min Wang; Neng-Bin Xie; Fang-Yin Gang; Shan Zhang; Li Zeng; Tong-Tong Ji; Jun Xiong; Xia Guo; Ying Hao; Yu Liu; Bi-Feng Yuan (Science China Life Sciences, 2025)

Green manuring with balanced fertilization improves soil ecosystem multifunctionality by enhancing soil quality and enzyme activities in a smooth vetch-maize rotation system - Long Jia; Huijuan Zhang; Jiyu Lu; Yan Liang; Yueda Li; Luyao Xu; Jiale Ye; Ruiyun Yang; Peng Li; Jiaguo Jiao; Xia Wang; Feng Hu (Agriculture, Ecosystems & Environment, 2025)

Elucidating the anti-aging bioactive compounds and mechanisms of Jingfang Granules formula based on network pharmacology and Caenorhabditis elegans - Rui Zhao; Taili Zhao; Tingting Shi; Chuanjiao Feng; Honghua Li; Ying Xu; Qingqing Zhang; Xin Yin; Jingchun Yao; Guimin Zhang; Xuekui Xia (Biogerontology, 2025)

Hysteresis model of metal rubber bridge bearings - Xiushen Xia; Yaobin Huang; Dawei Li; Feng Xu (Soil Dynamics and Earthquake Engineering, 2025)

Carbon and reactive nitrogen footprint of greenhouse versus open-field vegetable production in China - Weili Li; Minghao Zhuang; Lei Feng; Wei Wei; Longlong Xia; Yi Yang (Resources, Conservation and Recycling, 2025)

APPLE-MASNUM: Accelerating parallel processing for lightweight expansion of MASNUM on a single multi-GPU node - Qi Lou; Changmao Wu; Changming Dong; Xingru Feng; Yuanyuan Xia; Li Liu; Zhengwei Xu; Xu Gao; Meng Sun; Xunqiang Yin (Ocean Modelling, 2025)

The influence of Ca2+/Mg2+ concentration on the rheological properties of kaolinite slurry: An experiment and DLVO calculation study - Yijiang Li; Xiaoxia Yang; Zhaohua Wang; Wencheng Xia; Feng Wu; Yujin Sun; Xiangyun Sun; Shiqi Liu (Minerals Engineering, 2025)

Companion animals as sources of hazardous critically important antimicrobial-resistant Escherichia coli: Genomic surveillance in Shanghai - Yiwen Chen; Min Li; Bingqing Sun; Luming Xia; Yifei Zhang; Jun Feng; Min Chen; Zile Cheng; Chao Lv; Weiye Chen; Jiewen Huang; Qingtian Li; et al. (Journal of Hazardous Materials, 2025)

Corrosion fatigue degradation of FRP tendon after acidic corrosion coupling with sustaining/fatigue loading - Xia Liu; Xin Wang; Jingyang Zhou; Feng Li; Jiazhan Xie; Zhishen Wu (Engineering Structures, 2025)

Salinity and hydrology reconstructions using B/Ga proxy records in the Pearl River Estuary (China) - Jingyu Zhang; Wei Wei; Yi Zhong; Xing Wei; Wout Krijgsman; Yingci Feng; Yuanjie Li; Wei Cao; Yiquan Ma; Hu Yang; Yanan Zhang; Hai Li; et al. (Chemical Geology, 2025)

QTL mapping and transcriptome analysis identified BnaA03.XTH4 as a novel negative regulator of plant height in Brassica napus L. - Yu Xu; Ning Ma; Zhiting Guo; Xia Liu; Bingbing Zhang; Xiang Liu; Yiji Shi; Mengfan Qin; Yunlin Zhu; Yan Zhang; Yiming Feng; Aixia Xu; et al. (Theoretical and Applied Genetics, 2025)

Deformation and Cracking Evolution Mechanism of Surrounding Rock in Deep Clastic Rock Tunnels: A Scaled-Down Excavation Experimental Study - Feiyan Wang; Xia-Ting Feng; Yangyi Zhou; Xiaojun Yu; Chengxiang Yang; Bentong Sun; Fudong Li; Honglin Luo (Rock Mechanics and Rock Engineering, 2025)

Different Expression Patterns and Interactions with Time Recorder DAL1 Revealed the Gene Expansion and Functional Differentiation of Flowering Integrator SOC1 During Larch Aging - Zha-Long Ye; Xiang-Yi Li; Dong-Xia Cheng; Wan-Feng Li (Journal of Plant Growth Regulation, 2025)

Utilization of UV/VUV irradiation for removal of human body fluids related pollutants in swimming pool water - Dan Li; Liangchen Long; Wei Xia; Weixin Zhao; Likui Feng; Xinhui Xia; Shufei He; Yu Liu; Shijie You; Liangliang Wei (Journal of Hazardous Materials, 2025)

Synergistic lattice matching and architectural modulation in ZnO/BN heterostructures for enhanced photocatalytic properties - Fuxiong Ren; Zitian Liu; YuJia Lu; Yuan Gao; Shuai Zhang; Xia Feng; Li Chen; Yiping Zhao (Journal of Environmental Chemical Engineering, 2025)

Static magnetic field-enhanced cathodic electrocatalysis of Fe3O4-based nitrogen-doped carbon for improving the performance of microbial fuel cells - Hai-Xia Liao; Dong-Ni Ou; Xiao-Feng Zhou; Ying-Qi Ouyang; Hui-Huan Jiang; Nan Li; Zhao-Qing Liu (Bioresource Technology, 2025)

Statistical characteristics, circulation patterns, and environmental features of severe convective wind events in Beijing - Huixin Yang; Rudi Xia; Feng Li; Bo Yu (Atmospheric Research, 2025)

Pore Structure and Its Controlling Factors of Cambrian Highly Over-Mature Marine Shales in the Upper Yangtze Block, SW China - Dadong Liu; Mingyang Xu; Hui Chen; Yi Chen; Xia Feng; Zhenxue Jiang; Qingqing Fan; Li Liu; Wei Du (Journal of Marine Science and Engineering, 2025)
Highly over-mature marine shales are distributed worldwide with substantial resource potential, yet their pore structure characteristics and controlling mechanisms remain poorly understood, hindering accurate shale gas resource prediction and efficient development. This study focuses on the Cambrian Niutitang Formation shales in the Upper Yangtze region of South China. To decipher the multiscale pore network architecture and its genetic constraints, we employ scanning electron microscopy (SEM) pore extraction and fluid intrusion methods (CO2 and N2 adsorption, and high-pressure mercury intrusion porosimetry) to systematically characterize pore structures in these reservoirs. The results demonstrate that the shales exhibit high TOC contents (average 4.78%) and high thermal maturity (average Ro 3.64%). Three dominant pore types were identified: organic pores, intragranular pores, and intergranular pores. Organic pores are sparsely developed with diameters predominantly below 50 nm, displaying honeycomb, slit-like, or linear morphologies. Intragranular pores are primarily feldspar dissolution voids, while intergranular pores exhibit triangular or polygonal shapes with larger particle sizes. CO2 adsorption isotherms (Type I) and low-temperature N2 adsorption curves (H3-H4 hysteresis) indicate wedge-shaped and slit-like pores, with pore size distributions concentrated in the 0.5–50 nm range, showing strong heterogeneity. Pore structure shows weak correlations with TOC and quartz content but a strong correlation with feldspar abundance. This pattern arises from hydrocarbon generation exhaustion and graphitization-enhanced organic pore collapse under high compaction stress, which reduces pore preservation capacity. The aulacogen tectonic setting engenders proximal sediment provenance regimes that preferentially preserve labile minerals such as feldspars. This geological configuration establishes optimal diagenetic conditions for the subsequent development of meso- and macro-scale of dissolution pores. Our findings demonstrate that feldspar-rich shales, formed in a proximal depositional system with well-developed inorganic pores, serve as favorable reservoirs for the exploration of highly over-mature marine shale gas.

Isolation and identification of a novel bisacodyl analogue, bisacodyl dicycloproyl carboxylate, as a potential illegal additive in a dried plum product advertised for weight loss - Xian-Xian Li; Feng Jiang; Hong Yu; Xiao-Jing Huang; Jing-Xian Zhang; Jin-Tao Xia; Ying-ying Ran; Fan Huang; Jian Sun; Qing Hu (Food Additives & Contaminants: Part A, 2025)

Proline betaine facilitates angiogenesis in bronchopulmonary dysplasia - Wangdui Cili; Zhiye Qi; Qinghua Zhong; Yin Li; Xia Huang; Ruoting Yang; Si Tang; Qingyuan Li; Li Yang; Yue Ning; Yunbo Xie; Yanli Feng; et al. (Toxicology and Applied Pharmacology, 2025)

Pronounced advance on typhoon track forecast with global convection-permitting model - Jun Gu; Chun Zhao; Gudongze Li; Jiawang Feng; Mingyue Xu; Qiuyan Du; Zihan Xia; Yubin Li; Guanghua Chen; Xiaoyu Hao; Junshi Chen; Hong An (Science Bulletin, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Highly stable anode-free solid-state sodium batteries enabled by electrostatic shielding and nitrogenated interphase - Wuliang Feng; Caixia Li; Peiyao Wang; Jiaming Hu; Xuan Yu; Ying Zhang; Xingbao Zhu; Dengsong Zhang; Yongyao Xia; Yufeng Zhao (Chemical Engineering Journal, 2025)

Multifunctional Sr/Zn-doped TiO2 micro/nanoporous coating enhances osseointegration by modulating signaling crosstalk of bone-related cells - Tian-Xia Zheng; Nuo-Ya Yang; Jiu-Peng Deng; Wei Dong; Li-Fang Feng; Yuanyuan-Ding; Jin-Ping Yang; Xin-Jia Cai; Yan Liu; Meng-Chun Qi (Chemical Engineering Journal, 2025)

Contrasting roles of abundant and rare root-associated fungi in wheat: Community assembly, heritability and agronomic impacts - Xia Kang; Yuyin Zheng; Zhihan Feng; Minjie Yao; Xiangzhen Li; Dejun Han; Qingdong Zeng; Hao Tan; Yumin Yang; Jiabao Li (Applied Soil Ecology, 2025)

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

Intensified excessive wastage of key raw metals with expansion of global wind and solar photovoltaic energy development - Li He; Yun-Long Liu; Zhen-Jie Tang; Tong Sun; Yi-Ming Yan; Yong-Feng Xia; Hu-Shen Feng; Wei Ye (Resources, Conservation and Recycling, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

VvABF5 promotes ABA-mediated chlorophyll degradation by transcriptional activation of VvSGR during rachis browning of grape - Zhiqian Li; Dongfang Zou; Changjiang Nie; Xing Chen; Chang He; Xianbo Zheng; Bin Tan; Jun Cheng; Wei Wang; Pedro Martínez Gómez; Xia Ye; Jiancan Feng (Postharvest Biology and Technology, 2025)

Albaillellarian (radiolaria) assemblages across the Guadalupian–Lopingian boundary (Permian) and their environmental implications - Lei Zhang; Shan Chang; Xia Wang; Marie-Béatrice Forel; Qing-Lai Feng; Wei-Hong He; Taniel Danelian; Martial Caridroit; Qian Liu; Xing-Lin Li (Palaeoworld, 2025)

A functional slurry additive for robust interphase and stabilized high-voltage nickel-rich cathodes in lithium-ion batteries - Xuanting Wu; Junwei Feng; Said Amzil; Meilan Peng; Wenlu Zhai; Min Li; Xingchen Liu; Ya-Jun Cheng; Yonggao Xia (Chemical Engineering Journal, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

PpSPL1 and PpSPL15 inhibit peach branching by increasing strigolactone synthesis - Wan Pei; Jie Zhang; Ruixian Shen; Hefang Xie; Yajia Zhang; Junjie Zhang; Xiaodong Lian; Haipeng Zhang; Nan Hou; Lei Wang; Xianbo Zheng; Jun Cheng; et al. (Planta, 2025)

Exploring the anti-NSCLC mechanism of phillyrin targeting inhibition of the HSP90-AKT pathway - Qiong Duan; Ruochen Li; Mingxiao Wang; Zhenting Cui; Xia Zhu; Fanghong Chen; Feng Han; Jianxin Ma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Distinct Mechanisms Governing Two Types of Extreme Hourly Rainfall Rates in the Mountain Foothills of North China During the Passage of a Typhoon Remnant Vortex from 30 July to 1 August 2023 - Rudi Xia; Yuqing Ruan; Jisong Sun; Xudong Liang; Chong Wu; Feng Li; Ju Li; Jinfang Yin; Xinghua Bao; Mingxin Li; Xiaoyu Gao (Advances in Atmospheric Sciences, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Nanoparticle-mediated light-driven LAMP combined with test strips for sensitive and rapid visual detection of antibiotic resistance genes - Yu-E. Gao; Qing Huang; Yue Huang; Li-Xia Yan; Wen-Long Wang; WenFeng Zhao; Yong-Wei Feng; Xiao-Dong Huang; Yi Zhang (Journal of Hazardous Materials, 2025)

Modified gluten by extrusion can significantly improve the amounts of flavor compounds during the fermentation of umami condiment - Li-Hao Wang; Wen-Hui Qu; Hui Jiang; Song-Gang Xia; Xue Feng; Chang-Hu Xue; Yun-Qi Wen (Innovative Food Science & Emerging Technologies, 2025)

Association between short-term exposure to ambient PM2.5 and its components with hospital admissions for patients with coronary heart disease and comorbid diabetes mellitus in Beijing, China - Hammad Zaheer; Shiyun Lv; Zhiwei Li; Zhiyuan Wu; Feng Lu; Moning Guo; Lixin Tao; Bo Gao; Xiaonan Wang; Xia Li; Wei Wang; Xiangtong Liu; et al. (Environmental Research, 2025)

Regulation of whey protein emulsion gel's structure with pullulan to enhance astaxanthin bioaccessibility - Qianxi Zhao; Yankai Liu; Jiale Feng; Jiahua Zhang; Xinzhu Wang; Xun Li; Wantang Ji; Yu Wang; Bo Nan; Jingsheng Liu; Xia Li; Yuhua Wang (Carbohydrate Polymers, 2025)

The Influences of Mineral Components and Pore Structure on Hydraulic Fracture Propagation in Shale - Tianjiao Li; Mingyu Yao; Yingjie Xia; Xianhui Feng; Wenyu Cong; Yaoli Shi; Chun’an Tang (Rock Mechanics and Rock Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Structural and dynamic characteristics of horseshoe vortex systems in front of rigid vegetation inclined upstream under conditions of overland flow - Feng Li; Huilan Zhang; Fangzheng Gu; Shaoqin Xia; Yuan He; Linghan Wang; Di Zhang (Journal of Hydrology, 2025)

Exploring the therapeutic potential of lupeol: A review of its mechanisms, clinical applications, and advances in bioavailability enhancement - Xia Luo; Ji Li; Zhifeng Cen; Gang Feng; Meiqi Hong; Lizhen Huang; Qinqiang Long (Food and Chemical Toxicology, 2025)

Mantle induced hydration and oxidation of intracontinental granite sources in the North China Craton - Chuan-Mao Yang; Yi-Gang Xu; Xiao-Ping Xia; Jin-Hui Yang; Xiao-Long Huang; Christopher J. Spencer; Jin-Feng Sun; Ze-Xian Cui; Meng-Jing Li; Wan-Feng Zhang; Qing Yang (Earth and Planetary Science Letters, 2025)

Scaling law for correcting the gravel content effect due to scalping techniques by DEM investigations - Peng Xia; Dai-Guang Yu; Hai-Dong Luo; Zhuo-Feng Li; Qiang Ma; Yu-Feng Gao (Computers and Geotechnics, 2025)

Power regulative triboelectric-electromagnetic hybrid generator for light air harvesting - Yuqi Wang; Yang Yu; Xinghu Xue; Jinzhi Zhu; Xiao Xia; Hengyu Li; Yuming Feng; Xiaojun Cheng; Tinghai Cheng (Chemical Engineering Journal, 2025)

Lactobacillus acidophilus JYLA-126 Ameliorates Obesity-Associated Metabolic Disorders by Positively Regulating the AMPK Signaling Pathway Through the Gut-Liver Axis - Ping Li; Xia He; Enxu Feng; Jing Wei; Huaijun Tu; Tingtao Chen (Probiotics and Antimicrobial Proteins, 2025)

The mapping for plate-type PWR core pin-by-pin wise coupling calculation system - Zhigang Li; Junjie Pan; Bangyang Xia; Shenglong Qiang; Wei Zeng; Wei Lu; Ziliang Feng (Annals of Nuclear Energy, 2025)

Multi-omics Analysis Reveals Key Gut Microbiota and Metabolites Closely Associated with Huntington’s Disease - Shu-Xia Qian; Yu-Feng Bao; Xiao-Yan Li; Yi Dong; Xiao-Ling Zhang; Zhi-Ying Wu (Molecular Neurobiology, 2025)

Dust event identification and characterization with one-year online observations in Beijing - Feixue Zheng; Jinwen Li; Chenjie Hua; Jiali Xie; Yusheng Zhang; Liye Li; Sunan Shen; Simo Hakala; Chao Yan; Zemin Feng; Xiaolong Fan; Federico Bianchi; et al. (Science of The Total Environment, 2024)

Enhanced mite control and agricultural safety with etoxazole-loaded chitin nanocrystals: Synthesis, characterization, and ecological impacts - Xu Zhifeng; Feng Guo; Zhang Chenghao; Xia Wei; Li Maoyan; Qian Kun; Zhang Yongqiang (Pesticide Biochemistry and Physiology, 2024)

Evolution of hydrochemistry and water quality of karst groundwater under the effects of intense anthropogenic activities - Yawei Feng; Fengxin Kang; Yongli Guo; Zhifeng Li; Bintao Liu; Hongzhi Bu; Chunying Xia; Qingcheng He (Journal of Environmental Management, 2024)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

High stability and reactivity of porous calcium tartrate supported nano zero-valent iron in aerobic environment and alkaline wastewater - Fei Li; Xia Zhang; Feng Liang; Chen Wang; Pingning Jin; Jing Fan (Journal of Environmental Chemical Engineering, 2024)

The combination of HSI and NMR techniques with deep learning for identification of geographical origin and GI markers of Lycium barbarum L. - Chengcheng He; Xin Shi; Haifeng Lin; Quanquan Li; Feng Xia; Guiping Shen; Jianghua Feng (Food Chemistry, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Silver nanoparticles alter planktonic community structure and promote ecosystem respiration in freshwater mesocosms - Peng Wang; Zhiying Chen; Ende Guo; Qianqian Xiang; Chengjing Li; Xia Feng; Lihong Lian; Xia Luo; Liqiang Chen (Environmental Research, 2024)

Integrated DNA methylation analysis of peripheral blood from asbestos exposed populations and patients with malignant mesothelioma reveals novel methylation driver genes of diagnostic and prognostic relevance - Lingfang Feng; Tao Li; Biao Xu; Jing Huang; Hailing Xia; Zhaoqiang Jiang; Junfei Chen; Simiao Pan; Xing Zhang; Hua Jiang; Jianlin Lou (Environmental Pollution, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

How do heat waves affect the relationship between built environment patches of different compactness and land surface temperature? - Yifeng Ji; You Peng; Hongyu Tang; Zhitao Li; Yiting Xia; Tao Feng (Building and Environment, 2024)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

Notes on two new species of Russula subsect. Cyanoxanthinae (Russulaceae, Russulales) from southern China - Yan-Liu Chen; Jun-Feng Liang; Sheng-Kun Wang; Bin Chen; Jin-Hua Zhang; Meng-Ya An; Xing Li; Xue-Lian Gao; Xia Chen; Jin-Peng Liao (Mycological Progress, 2024)

Deciphering odontogenic myxoma: the role of copy number variations as diagnostic signatures - Aobo Zhang; Jianyun Zhang; Xuefen Li; Xia Zhou; Yanrui Feng; Lijing Zhu; Heyu Zhang; Lisha Sun; Tiejun Li (Journal of Zhejiang University-SCIENCE B, 2024)

A fruit tree feature matching algorithm based on an improved AKAZE method - Ponian Li; Jiajun Feng; Lingmin Chen; Haixiang Deng; Xia Wang (Environment, Development and Sustainability, 2024)

The spatiotemporal changes of crab community in the Yangtze River Estuary after the fishing ban - Zuchang Yang; Guangpeng Feng; Gang Yang; Tao Zhang; Feng Zhao; Zhi Geng; Xia Li; Qingyuan Tan (Frontiers in Marine Science, 2024)
The Yangtze River Estuary is the traditional habitat of fishery resources in China and also one of the crab fishing sites, but nowadays the crab resources have been seriously affected by high-intensity anthropogenic disturbance. To understand the composition and diversity of crab community following the fishing ban, six surveys were conducted from August 2022 to November 2023 using the single-bag trawl method. This study examined the crab community composition, biodiversity, resource density, spatiotemporal distribution patterns, and main influencing factors. Results indicated that a total of 14 crab species lived in the Yangtze River Estuary. Matuta planipes and Portunus trituberculatus were dominant crabs in summer 2022. P . trituberculatus , Eriochier leptognathus , and Charybdis japonica were dominant crabs in autumn 2022. Then, E. leptognathus and Eriocheir sinensis were dominant crabs in winter 2023. Notably, the largest numbers of dominant crabs appeared in spring 2023, including M. planipes , P. trituberculatus , E. leptognathus , C. japonica , and E. sinensis . Three same dominant crabs ( M. planipes , P. trituberculatus , C. japonica ) were identified in the summer and autumn of 2023. Thereinto, P. trituberculatus was the most dominant crab. The abundance and biomass trends of estuary crabs were winter< spring< autumn< summer. The community diversity index, evenness index, and richness index were winter< summer< autumn< spring, indicating the seasonal changes in abundance, biomass, and biodiversity. Correlation and redundancy analysis revealed that dissolved oxygen and salinity were the most critical environmental factors, which affect the changes in crab community in the estuary. This study revealed the changing characteristics of crab resources in the Yangtze River Estuary after the fishing ban, and provided the essential data and scientific basis for resource conservation and management decisions.

Air pollutants and the risk of incident hepatobiliary diseases: A large prospective cohort study in the UK Biobank - Bolun Cheng; Wenming Wei; Chuyu Pan; Li Liu; Shiqiang Cheng; Xuena Yang; Peilin Meng; Boyue Zhao; Jinyu Xia; Huan Liu; Yumeng Jia; Yan Wen; et al. (Science of The Total Environment, 2024)

Fetal weight growth trajectories and childhood development: A population-based cohort study - Xinmei Chen; Hongxiu Liu; Aifen Zhou; Feng Jin; Chufeng Jing; Yuanyuan Li; Wei Xia; Linda G. Kahn; Ya Xie; Xingliang Xiang; Shuting Cao; Wenxin Zhang; et al. (Science Bulletin, 2024)

The effect of lambda-cyhalothrin nanocapsules on the gut microbial communities and immune response of the bee elucidates the potential environmental impact of emerging nanopesticides - Dezheng Guo; Zhongyu Li; Yiwen Zhang; Wei Zhang; Chen Wang; Da-xia Zhang; Feng Liu; Zheng Gao; Baohua Xu; Ningxin Wang (Journal of Hazardous Materials, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Driving-sensing integrated magnetic soft robots via laser thermal printing - Yunfan Li; Ruiyuan Wang; Peilong Li; Xiao Chen; Yilin Zhao; Longju Yi; Zhe Liu; Re Xia; Feng Liu (Chemical Engineering Journal, 2024)

Valence electronic engineering of hollow-nanocube-structured CoFeNi-layered double hydroxides for highly efficient oxygen evolution - Lu Liu; Lingxing Zan; Yunchuan Tu; Hongling Zhang; Dan Zhu; Zhe Li; Jiawen Zheng; Zhuangzhuang Zhang; Yu Sun; Qiang Weng; Jian Li; Qingbo Wei; et al. (Chemical Engineering Journal, 2024)

Dual-continuous microneedle patch integrating transdermal delivery of pH-sensitive licorzinc MOFs and Zn2+ hydrogel sensors for treating alopecia areata - Hang Ruan; Yuwen Zhong; Huining Ding; Zehui He; Jiaqi Li; Meng Long; Zhi Wang; Qing Xia; Teng Guo; Chunyun Zhu; Tao Yang; Nianping Feng; et al. (Chemical Engineering Journal, 2024)

A derivative of honokiol HM568 has an anti-neuroinflammatory effect in Parkinson's disease - Changfeng Zhong; Changmei Wang; Wei Li; Wenyuan Li; Xuemei Chen; Jieqing Guo; Yifan Feng; Xia Wu (Chemico-Biological Interactions, 2024)

Salinomycin, a potent inhibitor of XOD and URAT1, ameliorates hyperuricemic nephropathy by activating NRF2, modulating the gut microbiota, and promoting SCFA production - Yong-jun Chen; Zi-tao Guo; Hai-qiao Chen; Shi-fan Zhang; Ying-xia Bao; Zhoufan Xie; Jia-le Ke; Wen-jie Ye; Jia-cheng Liang; Jia-chen Chen; Ning Li; Feng-xin Zheng; et al. (Chemico-Biological Interactions, 2024)

ALKBH5 facilitates the progression of infantile hemangioma by increasing FOXF1 expression in a m6A-YTHDF2 dependent manner to activate HK-2 signaling - Kun Peng; Ren-Peng Xia; Fan Zhao; Yong Xiao; Ti-Dong Ma; Ming Li; Yong Feng; Chong-Gao Zhou (Molecular and Cellular Biochemistry, 2024)

Development and application of turbulent heat flux model for lead-bismuth eutectic based on deep learning - Li-Xia Chen; Chao Yuan; Jun-Long Zhao; Hong-Na Zhang; Xiao-Bin Li; Feng-Chen Li (Annals of Nuclear Energy, 2024)

Effects of varied inundation characteristics on early life stages of a salt marsh plant - Qing Wang; Meng Luo; Baoshan Cui; Cong Chen; Tian Xie; Xia Li; Feng Lu (Frontiers in Marine Science, 2024)
Tidal inundation is a major stress in salt marshes that regulates the patterns of plant distribution and the associated functions provided by vegetation communities. Usually, frequency is used to represent inundation intensity and can be estimated using elevation. However, frequency is only a statistical indicator of tidal inundation conditions during a given period, which ignores many details of tidal inundation characteristics based on a single tidal event. On the scale of a single tidal event, duration and water depth are important characteristics for describing inundation conditions, which vary along the elevation gradient. The frequency of tidal events of a specific duration and water depth also varied. To unravel the impact of varied inundation characteristics on the key life stages of a foundation plant, we designed an experiment with varied inundation treatments of different frequencies, durations, and depths. Our results showed that the frequency, duration, and depth of inundation events significantly influenced seed emergence, seedling survival, and growth. Stress can be strengthened by a higher frequency with a longer duration and larger depth. Among these factors, frequency had a dominant impact, followed by duration and water depth. Specifically, there is a trade-off between frequency, duration, and depth, suggesting that an inundation event with shallower depth and/or shorter duration would reduce the stress from higher frequency. The findings fill a gap in the loss of details of varied inundation characteristics on plant establishment on a fine scale. Further, it will help explicit inundation stress more accurately and clearly and provide important implications for stress relief solutions in coastal ecological restoration.

Uncovering the role of free lanthanum (La3+) ions and La oligomer on the surface of La (oxy)hydroxide particles for phosphate removal - Feng Xiao; Yongqi Li; Yuanchen Xia; Jianing Zhang; Changyu Wang; Zihan Li; Shaoxia Yang; Shuoxun Dong; Yili Wang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Waste control by waste: A new approach for antibiotic removal and metal reuse from livestock wastewater using ascorbic acid-enhanced CaO2/Cu(II) system - Rongfa Zhang; Song Xia; Wenyue Yu; Guanglan Di; Jifei Hou; Xuede Li; Mingbao Feng (Journal of Hazardous Materials, 2024)

Machine learning-assisted optimization of food-grade spirulina cultivation in seawater-based media: From laboratory to large-scale production - Huankai Li; Lei Guo; Leijian Chen; Feng Zhang; Wei Wang; Thomas Ka-Yam Lam; Yongjun Xia; Zongwei Cai (Journal of Environmental Management, 2024)

Dihydroartemisinin regulates the apoptosis and growth of colorectal cancer by suppressing DPYSL2 and increasing TF and ACHE - Xiao Zhang; Jun-Feng Cao; Dunshui Liao; Zengliang Xia; Li Xiong; Mei Wu; Chaochao Wang; Xingyu Yang; Yixin Qiu; Lixin Zhang; Ningbo Chen; Ming Zhang; et al. (Food Bioscience, 2024)

Effects of cold plasma and ultra-high-pressure sterilization on the quality, flavor, and safety of semi-dried golden pompano - Dan Qiu; Jingxuan Zhou; Qiaohui Feng; Chuan Li; Guanghua Xia; Yongcheng Li; Wenting Shang; Yanfu He (Food Bioscience, 2024)

Epoxy resin gel particles with adjustable stickiness and deformability for pesticide delivery - Jiang Du; Da-Xia Zhang; Li-Jian Hao; Kun Zhuang; Feng Liu; Chao-Bin Xue (Chemical Engineering Journal, 2024)

Strong electronic coupling between Ni-based MOF and Ni2P enables high-efficiency oxygen evolution reaction for various application scenarios - Yirong Wang; Xuan Yu; Zhonghong Xia; Xuanrong Li; Ya Gao; Jing Zhang; Wuliang Feng; Xingli Zou; Yufeng Zhao (Chemical Engineering Journal, 2024)

The Neurocomputational Mechanism Underlying Decision-Making on Unfairness to Self and Others - Lanxin Luo; Han Xu; Xia Tian; Yue Zhao; Ruoling Xiong; Huafeng Dong; Xiaoqing Li; Yuhe Wang; Yue‑Jia Luo; Chunliang Feng (Neuroscience Bulletin, 2024)

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

What Caused the Differences between the July 2023 and August 1996 Extreme Rainfall Events in North China under Similar Synoptic Background? - Xinghua Bao; Jisong Sun; Jinfang Yin; Xiaoyu Gao; Feng Li; Xudong Liang; Haodong Gu; Rudi Xia; Mingxin Li; Chong Wu; Jianing Feng (Journal of Meteorological Research, 2024)

Cellulose-based yellow-green emitting carbon dots with large Stokes shift as effective “turn off-on” fluorescence platforms for Cr (VI) and AA dual efficacy detection - Yan-feng Li; Xian Zhang; Qian Lu; Jing-zhen Cao; Sheng Gao; Qin-ze Liu; Xiao-xia Cai; Hui Zhao (Analytica Chimica Acta, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Bifunctional materials based on poly(3-aminocarbazole) for efficient and highly selective detection and adsorption of Hg2+ in water - Dongkui Zhang; Feng Xu; Jianing Li; Rui Zhang; Jiangbin Xia (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Numerical simulation of fault activity in the Qilian tectonic belt and dynamic background of Menyuan earthquake series - Yuan Li; Xia Liu; Anfu Niu; Wei Zhan; Long Feng; Zheng Tang (Journal of Geodynamics, 2024)

Highly efficient recovery of phosphate and fluoride from phosphogypsum leachate: Selective precipitation and adsorption - Mengxuan Zhao; Xiaodi Li; Jun-xia Yu; Fei Li; Li Guo; Guoping Song; Chunqiao Xiao; Fang Zhou; Ruan Chi; Guoqing Feng (Journal of Environmental Management, 2024)

Geomechanical perspectives and reviews on the development and evolution of cross-scale discontinuities in the Earth's crust: Patterns, mechanisms and models - Sanbai Li; Zhijiang Kang; Moran Wang; Xi Zhang; Junliang Zhao; Xi-bing Li; Pengzhi Pan; Xin Luo; Hui Wu; Diyuan Li; Fengshou Zhang; Shunda Yuan; et al. (Gas Science and Engineering, 2024)

Exosomal proteomics and cytokine analysis distinguish silicosis cases from controls - Jiahui Yao; Yongxin Li; Shujuan Wang; Xiaowen Dong; Lingfang Feng; Xiaoxue Gong; Tiancheng Chen; Luqiao Lai; Huadong Xu; Zhaoqiang Jiang; Junfei Chen; Hailing Xia; et al. (Environmental Pollution, 2024)

La-doped O3-type layered oxide cathode with enhanced cycle stability for sodium-ion batteries - Lihua Feng; Yufan Xia; Jinze Guo; Huiling Liu; Youchen Hao; Ziqi Tian; Xin Xiao; Lijie Feng; Chujun Sun; Shunmian Qi; Kuoqin Li; Yong Li; et al. (Chemical Engineering Journal, 2024)

Gel biopolymer electrolyte for high-voltage, durable, and flexible Zn/K dual-ion pouch cells - Dawid Kasprzak; Li Tao; Zhenrui Wu; Jia Xu; Xia Sun; Feng Jiang; Jian Liu (Chemical Engineering Journal, 2024)

Rapidly reversible superwettability on textured metallic surfaces - Xianrui Zou; Yongguang Zhang; Wei Fang; Hui Jiang; Zhilu Yang; Qunyang Li; Shuilin Wu; Hongshui Wang; Donghui Wang; Huan Zhou; Tai Yang; Dan Xia; et al. (Chemical Engineering Journal, 2024)

Electrocatalytic hydrogen evolution coupled with dye hydrogenation reactions for sustainable wastewater treatment using transition-metal (Fe, Co, Ni, Cu) nanoparticles with ZnO nanowire supports - Anlin Feng; Mingtao Yang; Zheng Zhang; Hongjin Xia; Weihong Jin; Boxiong Shen; Yidong Hu; Qingyang Li (Chemical Engineering Journal, 2024)

Plasma Deoxycholic Acid Levels are Associated with Hemodynamic and Clinical Outcomes in Acute Pulmonary Embolism Patients - Na Sun; Yi-Qiang Chen; Yan-Sheng Chen; Lei Gao; Run-Wei Deng; Jing Huang; You-Li Fan; Xuan Gao; Bin-Feng Sun; Na-Na Dong; Bo Yu; Xia Gu; et al. (Cardiovascular Toxicology, 2024)

Anisotropy measurements and characterization of the Qingshankou shale - Qing-feng Li; Xue-hong Yan; Wei-lin Yan; Li Ren; Peng Wang; Jian-qiang Han; Xue Xia; Hao Chen (Applied Geophysics, 2024)

Isolation, Purification of Phenolic Glycoside 1 from Moringa oleifera Seeds and Formulation of Its Liposome Delivery System - Feng Shi; Mingjie Gong; Michael Adu-Frimpong; Xia Jiang; Xiaowen Wang; Qinyang Hua; Tingyuan Li; Jiaying Li; Jiangnan Yu; Elmurat Toreniyazov; Xia Cao; Qilong Wang; et al. (AAPS PharmSciTech, 2024)

Transparent and open-source aluminum life cycle inventory dataset for China - Jinliang Xie; Yuzhen Feng; Huimin Chang; Changqing Xu; Ruoxi Xiong; Zimeng Cai; Chenling Fu; Ziqian Xia; Jing Guo; Nan Li (Resources, Conservation and Recycling, 2024)

3D printed emulsion based on arginine-myofibrillar protein - Zilan Feng; Dongxue He; Chuan Li; Changfeng Xue; Xiangzhou Yi; Xia Gao; Zhisheng Pei; Xuanri Shen (Journal of Food Engineering, 2024)

Mapping agricultural soil water content using multi-feature ensemble learning of GPR data - Haoqiu Zhou; Qi Lu; Zejun Dong; Zhaofa Zeng; Risheng Li; Longfei Xia; Kexin Liu; Minghe Zhang; Xuan Feng (Journal of Applied Geophysics, 2024)

Enhancing the sodium-ion storage performance of two-dimensional layered Ti3CN with a molecular riveting strategy - Dong-Ting Zhang; Hong-Yan Li; Wen-Jie Shi; Yu-Xia Hu; Ling-Bin Kong; Xue-Feng Lu; Zi-Zhou Yuan; Mao-Cheng Liu (Chemical Engineering Journal, 2024)

Lithium salt regulation enabling 3D printed solid-state electrolytes to achieve ultra-long cycle performance of LiNi0.8Mn0.1Co0.1O2 - Changgang Li; Shuolei Deng; Wenhao Feng; Yaowen Cao; Jiaxuan Bai; Qianqian Dou; Xiaocong Tian; Yifan Dong; Fan Xia (Chemical Engineering Journal, 2024)

Sensitivity of atmospheric peroxyacetyl nitrate (PAN) formation and its impact on ozone pollution in a coastal city - Nan Fu; Li-Ming Cao; Shi-Yong Xia; Le-Wei Zeng; Li He; Ling-Yan He; Xiao-Feng Huang (Atmospheric Environment, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

The influence of proxy selection on global annual mean temperature reconstructions during the Common Era - Bao Yang; Xia Li; Minhui He; Feng Wang; Yesi Zhao; Peng Zhang; Jianglin Wang (Science China Earth Sciences, 2024)

The Untargeted Metabolomics Reveals Differences in Energy Metabolism in Patients with Different Subtypes of Ischemic Stroke - Xi Li; Jiaxin Li; Fang Yu; Xianjing Feng; Yunfang Luo; Zeyu Liu; Tingting Zhao; Jian Xia (Molecular Neurobiology, 2024)

Precipitation Evolution from Plain to Mountains during the July 2023 Extreme Heavy Rainfall Event in North China - Mingxin Li; Jisong Sun; Feng Li; Chong Wu; Rudi Xia; Xinghua Bao; Jinfang Yin; Xudong Liang (Journal of Meteorological Research, 2024)

Isophorone-based crystallization-induced-emission sensors detect proteome aggregation in live cells and tissues with breast cancer - Xiaomeng Jia; Di Shen; Jintai Deng; Kainan Wang; Xueqing Wang; Yijin Guo; Lu Sun; Hao Jin; Qiuxuan Xia; Huan Feng; Biao Jing; Jialu Sun; et al. (Analytica Chimica Acta, 2024)

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Overexpression of the grape β-galactosidase gene VvBGAL3 delays the softening and extends the shelf life of tomato fruits - Shanshan He; Hongli Wei; Zhirui Xue; Meng Li; Jiannan Xie; Jiakang Qian; Xing Chen; Zhiqian Li; Chang He; Bin Tan; Xianbo Zheng; Jun Cheng; et al. (Postharvest Biology and Technology, 2024)

Combined toxicity of polyvinyl chloride microplastics and copper to marine jacopever (Sebastes schlegelii) - Zike Li; Meijing Zhao; Zhihua Feng; Lin Zhu; Qi Sui; Xuemei Sun; Bin Xia (Marine Environmental Research, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

A rapid and efficient Agrobacterium-mediated transient transformation system in grape berries - Jiannan Xie; Chang He; Zhiqian Li; Meng Li; Shanshan He; Jiakang Qian; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Jidong Li; Jiancan Feng; et al. (Protoplasma, 2024)

Effects of abamectin nanocapsules on bees through host physiology, immune function, and gut microbiome - Dezheng Guo; Ying Wang; Zhongyu Li; Da-xia Zhang; Chen Wang; Hongfang Wang; Zhenguo Liu; Feng Liu; Xingqi Guo; Ningxin Wang; Baohua Xu; Zheng Gao (Science of The Total Environment, 2024)

Silybin mitigated liver and brain damage after difenoconazole exposure: Crosstalk between oxidative stress, inflammation, ferroptosis and apoptosis - Xinyu Wu; Jiawei Chen; Kaixin Ping; Yan Xia; Mengxin Li; Yannan Xiang; Huimao Feng; Jingquan Dong (Pesticide Biochemistry and Physiology, 2024)

New formula of vegetation roughness height and Darcy–Weisbach friction factor in channel flow - Da-Qian Feng; Jing-Jing Fan; Wei-Jie Wang; Cheng-Xing Xia; Ang Li (Journal of Hydrology, 2024)

Absorption characteristics and molecular mechanism of a low viscosity iron-based ionic liquid for removing H2S - Zhonghao Li; Zhou Feng; Hongwei Jin; Kangkang Li; Hongzhi Xia; Shiqi Qu; Sujuan Ye; Huanong Cheng; Qingli Wei; Yugang Li; Xinshun Tan; Shiqing Zheng (Journal of Environmental Chemical Engineering, 2024)

Comparative study and screening of Single-Atom and homonuclear Dual-Atom catalysts for NO reduction via electrocatalysis - Xiuxia Zhang; Lianxin Xia; Yanze Li; Hongqing Feng; Xinwei Wang; Jie Yu (Fuel, 2024)

Antimicrobial photodynamic inactivation pH-responsive films based on gelatin/chitosan incorporated with aloe-emodin - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Wei Ji; Baocai Xu; Hualin Wang (Food Chemistry, 2024)

Energy metabolism analysis of exogenous glutamate on promoting co-accumulation of astaxanthin yield and biomass in Phaffia rhodozyma D3 - Chunyu Cai; Na Xu; Jiale Feng; Jiahua Zhang; Qianxi Zhao; Huimin Liu; Bo Nan; Xia Li; Yuhua Wang (Bioresource Technology, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

Variations in Column Concentration of Greenhouse Gases in China and Their Response to the 2015–2016 El Niño Event - Ningwei Liu; Lingjun Xia; Youjun Dou; Shaorou Dong; Jing Wen; Ying Wang; Rui Feng; Ruonan Wang; Yuhe Li (Journal of Meteorological Research, 2024)

Soil physicochemical properties and plant functional traits regulate ecosystem multifunctionality of alpine grassland under different livestock grazing assemblies - Bin Feng; Yu-Zhen Liu; Wen-Ting Liu; Wei-Dong Lv; Cai-Cai Sun; Zeng-Zeng Yang; Cai-Di Li; Qin-Yuan Zhou; Fang-Cao Wang; Xiao-Xia Yang; Quan-Min Dong (Agriculture, Ecosystems & Environment, 2024)

Prenatal arsenic metabolite exposure is associated with increased newborn mitochondrial DNA copy number: evidence from a birth cohort study - Feng Qiu; Hongling Zhang; Xin Wang; Zhenxian Jia; Yujie He; Yi Wu; Zhangpeng Li; Tongzhang Zheng; Wei Xia; Shunqing Xu; Yuanyuan Li (Environmental Science and Pollution Research, 2024)

Two new cytochalasins from the endophytic fungus Xylaria sp. GDGJ-77B - Zhao-Long Xu; Ben-Chao Li; Li-Li Huang; Liu-Xia Lv; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2024)

Carboxymethyl cellulose stabilization induced changes in particle characteristics and dechlorination efficiency of sulfidated nanoscale zero-valent iron - Li Gong; Shuaixuan Ying; Chenyun Xia; Ke Pan; Feng He (Chemosphere, 2024)

A novel sulfidogenic process via sulfur reduction to remove arsenate in acid mine drainage: Insights into the performance and microbial mechanisms - Jiahua Gou; Juntao Xia; Yu Li; Yanying Qiu; Feng Jiang (Water Research, 2024)

Overexpressing peach PpePAO1 gene improves the nutrient value of tomato and enhances resistance against Botrytis cinerea - Zhenguo Cui; Yabo Jiang; Yang Chen; Xin Cheng; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Zhiqian Li; Xianbo Zheng; Jiancan Feng; et al. (Postharvest Biology and Technology, 2024)

FERONIA-mediated TIR1/AFB2 oxidation stimulates auxin signaling in Arabidopsis - Baiyan Lu; Shengnan Wang; Hanqian Feng; Jing Wang; Kaixing Zhang; Yilin Li; Ping Wu; Minmin Zhang; Yanshu Xia; Chao Peng; Chao Li (Molecular Plant, 2024)

Macrophage membrane-modified reactive oxygen species-responsive prodrug self-assembled nanoparticles for the targeted treatment of traumatic spinal cord injury - Jinyu An; Zhanshan Gao; Yingqiao Li; Nan Xia; Xiaobang Liu; Huicong Feng; Chao Wu; Xifan Mei; He Tian (Chemical Engineering Journal, 2024)

Cell-free chitosan/silk fibroin/bioactive glass scaffolds with radial pore for in situ inductive regeneration of critical-size bone defects - Xinsong Zhang; Yijing Xia; Jie Xu; Jie Kang; Xiujuan Li; Yuanjiao Li; Wenpeng Yan; Feng Tian; Bin Zhao; Bing Li; ChunFang Wang; Lu Wang (Carbohydrate Polymers, 2024)

Enzymolytic lignin derived Fe–N codoped porous carbon materials as catalysts for oxygen reduction reactions - Xia Qu; Yantao Yang; Lili Dong; Zheng Li; Yuwei Feng; Tingzhou Lei; Suxia Ren (Biomass and Bioenergy, 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

Contrasting fate and binding behavior of Mn and Cu with dissolved organic matter during in situ remediation using multicomponent capping in malodorous black water - Xuan Chang; Tingting Duan; Jiashen Feng; Ying-Xia Li (Water Research, 2024)

Occurrence of dark septate endophytes in Phragmites australis in the Baiyang Lake and their resistance to Cd stress - Minghui XU; Xia LI; Qiannan YE; Feng GONG; Xueli HE (Pedosphere, 2024)

Analytical evaluation of stress–strain behavior of rubberized concrete incorporating waste tire crumb rubber - Xiaoyan Han; Shanshan Zhou; Aijiu Chen; Lingyun Feng; Yanting Ji; Zhihao Wang; Sheng Sun; Keliang Li; Xiaozhou Xia; Qing Zhang (Journal of Cleaner Production, 2024)

Theoretical analysis on applying steam reforming to the primary combustion of the boron-based fuel-rich propellant - Chaolong Li; Zhixun Xia; Likun Ma; Binbin Chen; Yunchao Feng; Jiarui Zhang; Pengnian Yang (Fuel, 2024)

Key components, formation pathways, affecting factors, and emerging analytical strategies for edible mushrooms aroma: A review - Zhenshan Hou; Rongrong Xia; Yunting Li; Heran Xu; Yafei Wang; Yao Feng; Song Pan; Zijian Wang; Hongli Ren; Guanlin Qian; Huanyu Wang; Jiayi Zhu; et al. (Food Chemistry, 2024)

Inhibiting advanced glycation end products (AGEs) of high-performance hemodialysis membranes self-assembled by gallic acid and Ti3C2Tx MXene - Qiqi Wang; Changjun Mu; Ya'nan Yu; Xia Feng; Yang He; Li Chen (Chemical Engineering Journal, 2024)

Elimination of methylmercury production potential in excessive sludge in wastewater treatment plants by sulfur addition - Shenyu OuYang; Yu Li; Ming Liu; Qingxia Zhao; Jinting Wang; Juntao Xia; Junfeng He; Feng Jiang (Science of The Total Environment, 2024)

Effect and potential mechanisms of sludge-derived chromium, nickel, and lead on soil nitrification: Implications for sustainable land utilization of digested sludge - Jianju Li; Hao Ma; Hang Yu; Likui Feng; Xinhui Xia; Shufei He; Xinwei Chen; Qingliang Zhao; Liangliang Wei (Journal of Hazardous Materials, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Alterations in sperm DNA methylation may as a mediator of paternal air pollution exposure and offspring birth outcomes: Insight from a birth cohort study - Yuting Cheng; Jialin Feng; Jing Wang; Yijie Zhou; Shengjun Bai; Qiuqin Tang; Jinhui Li; Feng Pan; Qiaoqiao Xu; Chuncheng Lu; Wei Wu; Yankai Xia (Environmental Research, 2024)

Atmospheric ozone destruction and the end-Permian crisis: Evidence from multiple sulfur isotopes - Rucao Li; Shu-Zhong Shen; Xiao-Ping Xia; Bing Xiao; Yuzhou Feng; Huayong Chen (Chemical Geology, 2024)

Optimization of Microwave Presplitting Iron Ore to Improve Mechanical Mining Efficiency - Feng Lin; Xia-ting Feng; Shi-ping Li; Jiu-yu Zhang; Xiang-xin Su; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)

Therapeutic potential of dietary flavonoid hyperoside against non-communicable diseases: targeting underlying properties of diseases - Jia Xia; Yan Wan; Jiao-jiao Wu; Yu Yang; Jin-Feng Xu; Li Zhang; Dong Liu; Lu Chen; Fei Tang; Hui Ao; Cheng Peng (Critical Reviews in Food Science and Nutrition, 2024)

Brain white matter microstructural alterations in patients with systemic lupus erythematosus: an automated fiber quantification study - Peng Zhang; Yanhong Feng; Tianye Xu; Yifan LI; Jianguo Xia; Hongxia Zhang; Zhongru Sun; Weizhong Tian; Ji Zhang (Brain Imaging and Behavior, 2024)

Environmental quality assessment of heavy metals in the Rongcheng offshore area, Shandong Peninsula, China - Nana Yue; Congbo Xiong; Yongqiang Zhang; Wanjun Zhang; Yongcai Feng; Xia Li; Longzhi Han (Marine Pollution Bulletin, 2024)

Adaptability of sulfur-disproportionating bacteria for mine water remediation under the pressures of heavy metal ions and high sulfate content - Yan-Ying Qiu; Jiahui Zou; Juntao Xia; Hao Li; Yuming Zhen; Yanduo Yang; Jiahua Guo; Liang Zhang; Rongliang Qiu; Feng Jiang (Water Research, 2024)

Physiological and transcriptomic analysis reveals the toxic and protective mechanisms of marine microalga Chlorella pyrenoidosa in response to TiO2 nanoparticles and UV-B radiation - Lin Zhu; Sulan Feng; Yu Li; Xuemei Sun; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Covalently linked MOF@COF direct Z-scheme heterojunction for visible light-driven photocatalytic degradation of flotation agents - Hong-Xia Zhang; Sheng-Hua Ma; Hai-Xian Wang; Shao-Cong Li; Hai-Yun Shen; De-Ming Kong; Feng-Ying Wang; Li-Na Zhu (Journal of Environmental Chemical Engineering, 2024)

Antimony isotopic fractionation during intensive chemical weathering of basalt in the tropics - Yunjie Wu; Guangyi Sun; Jen-How Huang; Haifeng Fan; Xinyu Li; Mengying Zhou; Yi Xia; Xinbin Feng (Geochimica et Cosmochimica Acta, 2024)

Water-ultrastable perovskite CsPbBr3 nanocrystals tailored by surface-confined strategy for amaranth sensing in food samples - Lei Hu; Kai-Qi Liu; Feng Li; Heng-Ye Li; Wei Wang; Hai-Lin Fang; Hang Gao; Zhong-Xia Wang (Food Chemistry, 2024)

Associations of maternal urinary rare earth elements individually and in mixtures with neonatal size at birth - Feng Qiu; Hongling Zhang; Yuan Cui; Liping Zhang; Wensi Zhou; Min Huang; Wei Xia; Shunqing Xu; Yuanyuan Li (Environmental Pollution, 2024)

Zinc sulfide quantum dots modified 3D Nitrogen-Doped framework carbon enhances the ion transport rate of potassium ion hybrid capacitors - Shuolei Deng; Yifan Dong; Changgang Li; Wenhao Feng; Yaowen Cao; Qianqian Dou; Ziting Ma; Fan Xia (Chemical Engineering Journal, 2024)

C-methylated homoisoflavanones from the rhizomes of polygonatum cyrtonema and their chemotaxonomic significance - Jiang Wan; Guangyao Mei; Jun-Xia Ma; Ze-Yu Zhao; Can Wang; Ziping Zhu; Junmin Li; Jin-Feng Hu (Biochemical Systematics and Ecology, 2024)

Cycloaspeptide H, a cyclopentapeptide from the endophytic fungus Penicillium virgatum - Ben-Chao Li; Liu-Xia Lv; Li-Li Huang; Jia-Tong Zhou; Xi-Shan Huang; Jun Li; Rui-Yun Yang; Wei-Feng Xu (Natural Product Research, 2024)

Humic Substances-Induced Changes in the Properties of Sb-Contaminated Soil and Effects on Sb Forms - Xuegang Yu; Yuhang Feng; Aijiang Yang; Xia Hu; Qing Li; Xia Song; Yun He (Water, Air, & Soil Pollution, 2024)

Genome-wide identification and evolutionary analysis of WOX gene family in cucurbit crops - Chun Li; Zhen He; Genyun Liang; Nan Yang; Peng Cai; Ying Liang; Yuejian Li; Chao Fang; Duchen Liu; Feng Xia; Xiaojun Liu (Horticulture, Environment, and Biotechnology, 2024)

Antifungal activity and mechanism of oxanthromicin against Verticillium dahliae - Li-Jun Wang; Feng Wen; Li-Xia Li; Zhan-Feng Xia (Archives of Microbiology, 2024)

Exposure to particulate matter may affect semen quality via trace metals: Evidence from a retrospective cohort study on fertile males - Yuting Cheng; Jiaqi Zhu; Qiuqin Tang; Jing Wang; Jialin Feng; Yijie Zhou; Jinhui Li; Feng Pan; Xiumei Han; Chuncheng Lu; Xinru Wang; Marvin E. Langston; et al. (Chemosphere, 2024)

Meroterpenoids with divers' rings systems from Phyllosticta capitalensis and their anti-inflammatory activity - Xiao-xia Zhu; Wan-qiu Liu; Zhao-xia Shi; Huang-yao Zhu; Si-qi Fan; Jie Zhang; Wen-yuan Liu; Li-Jun Xu; Qing-Jia Ren; Feng Feng; Jian Xu (Phytochemistry, 2024)

NGO/ZnO2/ZnO heterojunctions with self-accelerating photocatalysis for efficient degradation of organic dyes - Yujia Lu; Yuan Gao; Fuxiong Ren; Yingying Xue; Kezhuo Feng; Yiping Zhao; Xia Feng; Li Chen (Journal of Water Process Engineering, 2024)

Efficient propane mineralization over unsaturated Pd cluster/CeO2 with prominent C-C cleavage capacity driven by inherent oxygen activation ability - Lianghui Xia; Shuai Xu; Yanfei Jian; Xiangbo Feng; Zeyu Jiang; Jingjing Wang; Yuliang Li; Yao Wang; Shouning Chai; Yujie Liu; Honggeng Peng; Reem Albilali; et al. (Journal of Hazardous Materials, 2024)

Economy and carbon emissions optimization of different provinces or regions in China using an improved temporal attention mechanism based on gate recurrent unit - Lian Cao; Yongming Han; Mingfei Feng; Zhiqiang Geng; Yi Lu; Liangchao Chen; Weiying Ping; Tao Xia; Shaobo Li (Journal of Cleaner Production, 2024)

Pressure–temperature–time path of ultrahigh-pressure metamorphic terranes constrained by zircon petrochronology: A case study of orthogneisses from the northern Sulu belt, China - Peng Feng; Hao Deng; Yang Zhang; Qing-Lin Sui; Hai-Yang He; Yan-Shi Xie; Liang Chen; Xian-Zhe Duan; Wen-Zhou Xiao; Xia-Wen Li; Nan Li (Journal of Asian Earth Sciences, 2024)

Process optimization, energy consumption analysis, and environmental assessment of total CO2 capture from syngas based on [NEMH][Ac] protic ionic liquid - Zhou Feng; Ning Wang; Xiaohan Li; Zhonghao Li; Kangkang Li; Hongwei Jin; Shiqi Qu; Hongzhi Xia; Huanong Cheng; Xinshun Tan; Shiqing Zheng (International Journal of Greenhouse Gas Control, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

Identification and fine-mapping of QYrAS286-2BL conferring adult-plant resistance to stripe rust in cultivated emmer wheat - Yuqin Li; Yanling Hu; Yun Jiang; Qiang Zhou; Yu He; Jingshu He; Xuejiao Chen; Xue Chen; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; et al. (Theoretical and Applied Genetics, 2024)

Spatiotemporal simulation, early warning, and driving factors of soil heavy metal pollution in a typical industrial city in southeast China - Jiayi Ma; Kaige Lei; Yi Li; Yanbin Zhang; Feng Li; Fang Xia; Yan Li (Stochastic Environmental Research and Risk Assessment, 2024)

Impairment of Autophagic Flux After Hypobaric Hypoxia Potentiates Oxidative Stress and Cognitive Function Disturbances in Mice - Shuhui Dai; Yuan Feng; Chuanhao Lu; Hongchen Zhang; Wenke Ma; Wenyu Xie; Xiuquan Wu; Peng Luo; Lei Zhang; Fei Fei; Zhou Fei; Xia Li (Neuroscience Bulletin, 2024)
Acute hypobaric hypoxic brain damage is a potentially fatal high-altitude sickness. Autophagy plays a critical role in ischemic brain injury, but its role in hypobaric hypoxia (HH) remains unknown. Here we used an HH chamber to demonstrate that acute HH exposure impairs autophagic activity in both the early and late stages of the mouse brain, and is partially responsible for HH-induced oxidative stress, neuronal loss, and brain damage. The autophagic agonist rapamycin only promotes the initiation of autophagy. By proteome analysis, a screen showed that protein dynamin2 (DNM2) potentially regulates autophagic flux. Overexpression of DNM2 significantly increased the formation of autolysosomes, thus maintaining autophagic flux in combination with rapamycin. Furthermore, the enhancement of autophagic activity attenuated oxidative stress and neurological deficits after HH exposure. These results contribute to evidence supporting the conclusion that DNM2-mediated autophagic flux represents a new therapeutic target in HH-induced brain damage.

Isolation, identification, and induced differentiation of satellite cells from skeletal muscle of adult tree shrews - Shenghui Ke; Yiwei Feng; Liying Luo; Wanzhao Qin; Huayu Liu; Jingchong Nie; Beijiang Liang; Hongjie Ma; Mao Xie; Jingyu Li; Zhijie Niu; Guojian Li; et al. (In Vitro Cellular & Developmental Biology - Animal, 2024)

The influence of pulse-like ground motion caused by the directivity effect on landslide triggering - Zhiyuan Li; Guangqi Chen; Zishuang Han; Hemanta Hazarika; Mingyao Xia; Chaofan Feng (Bulletin of Engineering Geology and the Environment, 2024)

Estimating the complete in-situ stress tensor along deep tunnels with frequent rockbursts near a steep valley - Ben-Guo He; Hong-Pu Li; Xia-Ting Feng; Xiang-Rui Meng (Bulletin of Engineering Geology and the Environment, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Distinct effects of chemical- and bio- flocculants on the sludge acidogenic fermentation for volatile fatty acids production by affecting the acidogenic steps, microbial community structure and metabolic functions - Jingyang Luo; Xue Xia; Yuxiao Li; Shiyu Fang; Feng Wang; Xiaoshi Cheng; Leiyu Feng; Wenxuan Huang; Yang Wu (Science of The Total Environment, 2023)

Development of a new method framework to estimate the nonlinear and interaction relationship between environmental factors and soil heavy metals - Kaige Lei; Yan Li; Yanbin Zhang; Shiyi Wang; Er Yu; Feng Li; Fen Xiao; Fang Xia (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Nonthermal plasma-activated polyvalent cerium-manganese bimetallic (hydro)oxide-functionalized nanographene for the removal of thallium(I) contaminants and mechanism exploration - Dongping Song; Tao Huang; Yinglan Luo; Di Wu; Shouze Li; Yujie Yan; Chaojun Yang; Qi Fang; Yuxing Wang; Yuxuan Feng; Nan Shang; Ming Xia; et al. (Journal of Cleaner Production, 2023)

Organic-inorganic photocatalyst with S-scheme heterojunction based proton shuttle strategy for efficient dye degradation - Fuxiong Ren; Yujia Lu; Yuan Gao; YanZe Xu; Yingying Xue; Xia Feng; Li Chen; Yiping Zhao (Journal of Environmental Chemical Engineering, 2023)

Degradation of norfloxacin by sulfur-doped iron-cobalt oxides activated perodisulfate: Synergism between free radicals and singlet oxygen - Luwei Zhai; Fengchun Li; Yuhai He; Xia Chen; Xuan Zhang; Yawei Gu; Chongqing Xu; Guihuan Yan; Xiaojing Feng; Wenqiang Jiang (Chemical Engineering Journal, 2023)

A single-site porphyrin (Cu)-based COF electrocatalyst for the electrochemical detection of gallic acid sensitively - Mei-Jie Wei; Jing Li; Ze-Qi Wei; Sheng-Feng Zhang; Zhong-Xia Wang; Heng-Ye Li; Rui Zhang; Fen-Ying Kong; Wei Wang (Analytica Chimica Acta, 2023)

Machine learning combined with Geodetector quantifies the synergistic effect of environmental factors on soil heavy metal pollution - Kaige Lei; Yan Li; Yanbin Zhang; Shiyi Wang; Er Yu; Feng Li; Fen Xiao; Zhou Shi; Fang Xia (Environmental Science and Pollution Research, 2023)

How weather impacts the citizens' activity patterns in southern China? Enlightenment from large-scale mobile phone signaling data of Guangzhou - Yukai Zou; Weien Xie; Siwei Lou; Lei Zhang; Yu Huang; Dawei Xia; Xiaolin Yang; Chao Feng; Yilin Li (Urban Climate, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Effects of different over-fired drying methods on the aroma of Lu’an Guapian tea - Jixin Zhang; Dongzhou Xia; Tiehan Li; Yuming Wei; Wanzhen Feng; Zhichao Xiong; Junlan Huang; Wei-Wei Deng; Jingming Ning (Food Research International, 2023)

Hydrophobic electrospun membrane of peppermint oil loaded zein with coating of methyltriethoxysilane for active packaging - Li Xia; Linlin Li; Yewen Xiao; Feng Xiao; Wei Ji; Min Pang; Hualin Wang (Food Hydrocolloids, 2023)

Tempo-spacial variation and source apportionment of atmospheric formaldehyde in the Pearl River Delta, China - Cheng-Bo Wei; Guang-He Yu; Li-Ming Cao; Heng-Xiao Han; Shi-Yong Xia; Xiao-Feng Huang (Atmospheric Environment, 2023)

A Novel Large-Scale Three-Dimensional Physical Model Experimental System for Deep Underground Engineering - Xia-Ting Feng; Zheng-Wei Li; Shi-Ming Mei; Jun Tian; Cheng-Xiang Yang; Zhi-Bin Yao; Ji-Kai Gao (Rock Mechanics and Rock Engineering, 2023)

Failure Modes of Jointed Granite Subjected to Weak Dynamic Disturbance Under True-Triaxial Compression - Ben-Guo He; Lei Wang; Xia-Ting Feng; Rong-Li Zhen (Rock Mechanics and Rock Engineering, 2023)

Effect of iron-loaded sludge biochar amendments on phytoremediation potential of Cr-contaminated soils by Leersia hexandra swartz - Jin-Chao Wang; Ji-Rong Zhao; Qing-Xia Huang; Li-Jiao Yang; Guo Yu; Yu-Feng Xu; Li-Heng Liu (Chemosphere, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Configured quantum reservoir computing for multi-task machine learning - Wei Xia; Jie Zou; Xingze Qiu; Feng Chen; Bing Zhu; Chunhe Li; Dong-Ling Deng; Xiaopeng Li (Science Bulletin, 2023)

PpeERF115 regulates peach fruit ripening by increasing polyamine turnover through up-regulation of genes involved in polyamine synthesis and catabolism - Xin Cheng; Zhenguo Cui; Yabo Jiang; Yang Chen; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Jidong Li; et al. (Postharvest Biology and Technology, 2023)

Hydrothermal fabrication of phytic acid decorated chitosan-graphene oxide composites for efficient and selective adsorption of uranium (VI) - Hongtao Xia; Qi Ren; Jianqi Lv; Yang Wang; Zihao Feng; Yang Li; Changfu Wang; Yan Liu; Yun Wang (Journal of Environmental Chemical Engineering, 2023)

Continuous hydrocarbon fuels production by photoenzymatic decarboxylation of free fatty acids from waste oils - Feng Li; Ao Xia; Xiaobo Guo; Wuyuan Zhang; Yun Huang; Xianqing Zhu; Xun Zhu; Qiang Liao (Journal of Environmental Chemical Engineering, 2023)

Effect of a co-fermentation system with high-GABA-yielding strains on soymilk properties: microbiological, physicochemical, and aromatic characterisations - Yanan Xia; Musu Zha; Chenchen Feng; Yankai Li; Yongfu Chen; Quan Shuang (Food Chemistry, 2023)

Flexible fabrication chitosan-polyamidoamine aerogels by one-step method for efficient adsorption and separation of anionic dyes - Jiang Zhan; Heyu Sun; Li Chen; Xia Feng; Yiping Zhao (Environmental Research, 2023)

In-situ grown a zeolitic imidazolate framework for boosting sensitivity of breathable wearable electronics - Guang Li; Han Zhang; Sai Yan; Hengxue Xiang; Huidan Wei; Yuhan Xia; Xunda Feng; Ran Cao; Meifang Zhu (Chemical Engineering Journal, 2023)

Immobilization of fatty acid photodecarboxylase in magnetic nickel ferrite nanoparticle - Feng Li; Ao Xia; Xiaobo Guo; Yun Huang; Xianqing Zhu; Xun Zhu; Qiang Liao (Bioresource Technology, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Effect of light on quality of preharvest and postharvest edible mushrooms and its action mechanism: A review - Yao Feng; Heran Xu; Yong Sun; Rongrong Xia; Zhenshan Hou; Yunting Li; Yafei Wang; Song Pan; Li Li; Chunyan Zhao; Hongli Ren; Guang Xin (Trends in Food Science & Technology, 2023)

Seasonal variation characteristics of atmospheric peroxyacetyl nitrate (PAN) and its source apportionment in a megacity in southern China - Shi-Yong Xia; Xiao-Feng Huang; Zhi-Jie Li; Nan Fu; Zhen Jiang; Li-Ming Cao; Le-Wei Zeng; Guang-He Yu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

Molecular assembly of extracellular polymeric substances regulating aggregation of differently charged nanoplastics and subsequent interactions with bacterial membrane - Yingjie Liu; Tongtao Yue; Lu Liu; Bowen Zhang; Hao Feng; Shixin Li; Xia Liu; Yanhui Dai; Jian Zhao (Journal of Hazardous Materials, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Landscape pattern exhibits threshold-driven effect on nitrogen export of typical land use in subtropical hilly watershed under specific hydrological regimes - Cen Meng; Huanyao Liu; Yi Wang; Jianlin Shen; Feng Liu; Yongqiu Xia; Yuyuan Li; Jinshui Wu (Journal of Cleaner Production, 2023)

Ferrocene-conjugated polymeric platform via amide bond formation facilitates enhanced in situ fenton reaction and robust immune responses in combination with toll-like receptor 7/8 agonist - Yanyun Hao; Hui Li; Fangfang Ren; Ruihua Feng; Yang Liu; Xia Li; Hongfei Chen; Jing Zou; Lingling Huang; Shiying Zhang; Gang Shan; Zhijie Yang; et al. (Chemical Engineering Journal, 2023)

Over-expression of miR-3584-5p Represses Nav1.8 Channel Aggravating Neuropathic Pain caused by Chronic Constriction Injury - Ran Yang; Qian-qian Wang; Yuan Feng; Xue-hao Li; Gui-xia Li; Feng-lin She; Xi-jin Zhu; Chun-li Li (Molecular Neurobiology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

New insights into the protection of dietary components on anxiety, depression, and other mental disorders caused by contaminants and food additives - Ruo-Gu Xiong; Jiahui Li; Jin Cheng; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan; Yibin Feng (Trends in Food Science & Technology, 2023)

Quantum computer-aided design for advanced superconducting qubit: Plasmonium - Feng-Ming Liu; Can Wang; Ming-Cheng Chen; He Chen; Shao-Wei Li; Zhong-Xia Shang; Chong Ying; Jian-Wen Wang; Yong-Heng Huo; Cheng-Zhi Peng; Xiaobo Zhu; Chao-Yang Lu; et al. (Science Bulletin, 2023)

Antimicrobial mechanisms of ZnO nanoparticles to phytopathogen Pseudomonas syringae: Damage of cell envelope, suppression of metabolism, biofilm and motility, and stimulation of stomatal immunity on host plant - Guangjin Fan; Qingli Xiao; Qian Li; Yinling Xia; Hui Feng; Xiaozhou Ma; Lin Cai; Xianchao Sun (Pesticide Biochemistry and Physiology, 2023)

Visual tracking of label-free microplastics in wheat seedlings and their effects on crop growth and physiology - Ruijie Li; Chen Tu; Lianzhen Li; Xinyao Wang; Jie Yang; Yudong Feng; Xia Zhu; Qiaohui Fan; Yongming Luo (Journal of Hazardous Materials, 2023)

The biochemical characteristics of viable but nonculturable state Yersinia enterocolitica induced by lactic acid stress and its presence in food systems - Shuai Cheng; Zhenye Li; Xiangyang Bai; Jingqi Feng; Ruiying Su; Luyi Song; Hui Yang; Xiangjun Zhan; Xiaodong Xia; Xin Lü; Chao Shi (Food Research International, 2023)

Hexavalent chromium [Cr(VI)]-induced ribosomal DNA copy number variation and DNA damage responses and their associations with nucleolar protein HRAS in humans and cells - Huadong Xu; Li Shi; Lingfang Feng; Fan Wu; Junfei Chen; Yao Qin; Xiaowen Dong; Zhaoqiang Jiang; Yongxin Li; Hailing Xia; Jianlin Lou (Environmental Pollution, 2023)

Advances in molten-salt-assisted synthesis of 2D MXenes and their applications in electrochemical energy storage and conversion - Fei Wang; Shujuan Wang; Feng Tian; Fuqian Wang; Xuewen Xia; Qi Zhang; Zhongya Pang; Xing Yu; Guangshi Li; Hsien-Yi Hsu; Shen Hu; Li Ji; et al. (Chemical Engineering Journal, 2023)

Investigating the tourism image of mountain scenic spots in China through the lens of tourist perception - Feng-jiao Li; Xia Liao; Jia-ming Liu; Li-li Jiang; Meng-di Wang; Jin-feng Liu (Journal of Mountain Science, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

Phosphate adsorption on LDHs-biochar composite: Double-layer model for quantifying the contribution of ion exchange and ligand exchange - Shangkai Qiu; Mingyao Yuan; Mengmeng Li; Wenjia Han; Lisheng Zhang; Di Zhao; Xia Li; Keqiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Coupling of underground coal mining and mine reclamation for farmland protection and sustainable mining - Zhenqi Hu; Gensheng Li; Jianan Xia; Zhanjie Feng; Jiazheng Han; Zanxu Chen; Wenjuan Wang; Guodong Li (Resources Policy, 2023)

Santalane-type sesquiterpenoids and isobenzofuranones from cultures of Paraconiothyrium sporulosum YK-03 - Li-Hua Zhang; Wen-Ke Gao; Shi-Wei Li; Xiao-Yan Song; Hong-Hua Wu; Hai-Feng Wang; Gang Chen; Shao-Xia Wang; Yue-Hu Pei (Phytochemistry, 2023)

Enrichment strategies of heavy metals in the O/H/O process composed of biological fluidized bed for wastewater treatment: A case study of Cu and Zn - Cong Wei; Xiaoqian Cheng; Wei Sun; Xia Tang; Tuo Wei; Zijun Pang; Xiong Ke; Zhi Qin; Jiamin Pan; Gengrui Wei; Guanglei Qiu; Chunhua Feng; et al. (Journal of Cleaner Production, 2023)

Correction to: Chromatin Remodeling Factor SMARCA5 is Essential for Hippocampal Memory Maintenance via Metabolic Pathways in Mice - Yu Qu; Nan Zhou; Xia Zhang; Yan Li; Xu-Feng Xu (Neuroscience Bulletin, 2023)

Chromatin Remodeling Factor SMARCA5 is Essential for Hippocampal Memory Maintenance via Metabolic Pathways in Mice - Yu Qu; Nan Zhou; Xia Zhang; Yan Li; Xu-Feng Xu (Neuroscience Bulletin, 2023)

Studies on competitive adsorption characteristics of bisphenol A and 17α-ethinylestradiol on thermoplastic polyurethane by site energy distribution theory - Hui Jiang; Qiao-ying Li; Jiao-xia Sun; Yuan-yuan Huang; Peng Zhang; Yu-feng Mao; Ying-fang Qu; Xiu-li Liu (Environmental Geochemistry and Health, 2023)

RNA-seq reveals the role of miR-223 in alleviating inflammation of bovine mammary epithelial cells - Yan-Xia Li; Peng Jiao; Xing-Ping Wang; Jin-Peng Wang; Fen Feng; Bin-Wu Bao; Yi-Wen Dong; Zhuo-Ma Luoreng; Da-Wei Wei (Research in Veterinary Science, 2023)

Crustal thickening and uplift of the northwestern Lhasa Terrane, central Tibetan Plateau: Insights from Mid-Eocene volcanic rocks in the Gerze Region - Xin-Hang Chai; Yun-Chuan Zeng; Ji-Feng Xu; Ming-Jian Li; Feng Huang; Xi-Jun Liu; Qin Chen; Hong-Xia Yu; Shu-Hui Ren (Lithos, 2023)

Ag@Bi5O7I nanoparticles deposited on Bi(OH)3 nanosheets for boosting photocatalytic antibacterial activity under visible light irradiation - Qinghan Chen; Li Wang; Dehui He; Bo Xiao; Xia Ran; Rong Li; Hong Xu; Jian Feng (Journal of Environmental Chemical Engineering, 2023)

Bioactive compounds and health benefits of pomegranate: An updated narrative review - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Yibin Feng; Ren-You Gan; Hua-Bin Li (Food Bioscience, 2023)

Tofu by-product soy whey substitutes urea: Reduced ammonia volatilization, enhanced soil fertility and improved fruit quality in cherry tomato production - Yiqiang Dai; Zhe Wang; Jing Li; Zhuang Xu; Cong Qian; Xiudong Xia; Yang Liu; Yanfang Feng (Environmental Research, 2023)

Effects of adsorption characteristics of carbocatalysts on persulfate-based advanced oxidation processes: Organic removal mechanisms and optimization strategies - Xiang-Feng Huang; Jing-Xi Yuan; Xia Zhao; Shuang-Qiang Li; Li-Heng Yang; Wen-Yan Li; Kai-Ming Peng; Chen Cai; Jia Liu (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Inhibition of Toll-Like Receptor 4 Signaling Pathway Accelerates the Repair of Avascular Necrosis of Femoral Epiphysis through Regulating Macrophage Polarization in Perthes Disease - Ronghui Yu; Cong Ma; Guoyong Li; Jianyun Xu; Dan Feng; Xia Lan (Tissue Engineering and Regenerative Medicine, 2023)

Improved 31P NMR analysis of phosphorus in highly mineralized lake water using a modified pretreatment procedure with H resin - Wanchang Ding; Guoxi Wang; Weiwei Lü; He Li; Haoyu Ren; Feng Jiang; Abdul Qadeer; Xia Jiang (Chemosphere, 2023)

PpIBH1-1 limits internode elongation of peach shoot in a dose-dependent manner - Mengmeng Zhang; Beibei Feng; Yun Chen; Mingxi Geng; Ming Li; Xianbo Zheng; Haipeng Zhang; Langlang Zhang; Bin Tan; Xia Ye; Wei Wang; Jidong Li; et al. (Plant Science, 2023)

Impacts of suspended sediment on oil spill in macro-tidal turbid waters: An example in Zhoushan Archipelago - Li Li; Yixuan Feng; Xin Chen; Zhiguo He; Huiqun Wang; Yuezhang Xia (Journal of Marine Systems, 2023)

Preparation of high-quality alkylated gasoline with low alkane-to-alkene ratio catalyzed by polyether-based Brønsted-Lewis acidic deep eutectic solvent - Ying-Bin Jiang; Feng-Li Yu; Bing Yuan; Cong-Xia Xie; Shi-Tao Yu (Fuel, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Whey protein concentrate/pullulan gel as a novel microencapsulated wall material for astaxanthin with improving stability and bioaccessibility - Yankai Liu; Xia Li; Haiyue Sun; Jing Zhang; Chunyu Cai; Na Xu; Jiale Feng; Bo Nan; Yuhua Wang; Jingsheng Liu (Food Hydrocolloids, 2023)

Association of arsenic exposure and clinical hematological changes during pregnancy: Findings from a prospective Wuhan birth cohort study - Feng Qiu; Hongling Zhang; Hongxiu Liu; Tongzhang Zheng; Wei Xia; Shunqing Xu; Han Xiao; Yuanyuan Li (Environmental Research, 2023)

Identifying the airport as a key urban VOC source in the Pearl River Delta, China - Bo Zhu; Li-Ming Cao; Shi-Yong Xia; Ying-Bo Niu; Han-Yang Man; Ke Du; Kuangyou Yu; Xiao-Feng Huang (Atmospheric Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Endoplasmic reticulum stress regulates autophagic response that is involved in Saikosaponin a-induced liver cell damage - Ye-Feng Wang; Rui-Xia Ma; Bin Zou; Jia Li; Yao Yao; Juan Li (Toxicology in Vitro, 2023)

Geochemical characteristics of shales from the first member of Qingshankou Formation in Gulong Sag, Songliao Basin, China: Implication for mechanism of organic matter enrichment - Yongchao Wang; Pengpeng Li; Zihui Feng; Hongmei Shao; Zhongwei Jia; Yanqing Xia; Jing Li; Zhen Wang (Marine and Petroleum Geology, 2023)

Localized photo-Fenton reaction boosted by spontaneous generation of H2O2 from thin water membrane - Juan Li; Yu Xia; Jingxing Li; Kaixiang Long; Fengjie Chen; Min Feng; ShiShang Guo; Bolei Chen (Journal of Water Process Engineering, 2023)

Oral vaccination with recombinant Lactobacillus casei with surface displayed OmpK fused to CTB as an adjuvant against Vibrio mimicus infection in Carassius auratus - Hong-Jin Li; Bin-Tong Yang; Yu-Feng Sun; Tong Zhao; Zhi-Peng Hao; Wei Gu; Meng-Xia Sun; Wei Cong; Yuan-Huan Kang (Fish & Shellfish Immunology, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Sedimentary and tectonic evolution of the Banquan pull-apart basin and implications for late Cenozoic dextral strike-slip movement of the Tanlu Fault Zone - Peng Shu; Xiwei Xu; Shaoying Feng; Baojin Liu; Kang Li; Paul Tapponnier; Xiaojuan Deng; Guihua Chen; Nuan Xia; Hongtai Xu; Jingjing Qin; Fubing He; et al. (Science China Earth Sciences, 2023)

Brittle failure modes of underground powerhouses: an insight based on true triaxial compression tests - Ben-Guo He; Qiang Tong; Xia-Ting Feng; Qiang Jiang; Hui Li; Yonghong Li; Zhiguo Li (Bulletin of Engineering Geology and the Environment, 2023)

Experimental verification of the intrinsic strainburst proneness of various rock types - Lei Shi; Charlie C. Li; Xiwei Zhang; Xia-Ting Feng (Bulletin of Engineering Geology and the Environment, 2023)
A portion of excess strain energy is converted into kinetic energy after the peak load in Class II rock. That is the intrinsic potential energy for strainburst. Therefore, the intrinsic strainburst proneness of the rock can be quantitatively assessed by the excess energy released from the rock, which can also be expressed by an intrinsic ejection velocity. This study aims to validate the idea of using the intrinsic ejection velocity as an index for the strainburst proneness of rock. Servo-controlled uniaxial compression tests were first conducted on 13 types of rocks. The intrinsic ejection velocities of rock specimens were assessed on the stress–strain curves. It was showed that the ejection velocity was greater than zero in twelve of the thirteen rock types, indicating that the twelve rock types were intrinsically prone to strainburst. The intrinsic ejection velocity was less than 5 m/s in eleven rock types, while up to 7.2 m/s in one. True triaxial tests were then conducted to examine the intensity of the bursting in six of the burst-prone rock types. The mass of the ejected rock fragments and the bursting sounds were recorded and analyzed afterward. The results showed that the orders of both the mass of the ejected rock fragments and the intensity of the bursting sounds were consistent with the order of the intrinsic ejection velocities of the rocks. It seems that the intrinsic ejection velocity is an appropriate index for the strainburst proneness of rock.

Plant regeneration via callus-mediated organogenesis in commercial variety of Chuanbeichai No. 1 in Bupleurum chinense DC - Yuchan Li; Jun Zhao; Hua Chen; Xia Yu; Hui Li; Yu Zhang; Liang Feng; Zhe Wu; Wenlin Xie; Dabin Hou; Ma Yu (Plant Biotechnology Reports, 2023)

A novel Halbach array electromagnetic pump for liquid metal flow: Design proposal and performance analysis - Liang Yao; Xiao-Bin Li; Hong-Na Zhang; Li-Xia Chen; Feng-Chen Li (Annals of Nuclear Energy, 2023)

Quercetin Mediated TET1 Expression Through MicroRNA-17 Induced Cell Apoptosis in Melanoma Cells - Yongjian Gao; Chengshun Li; Tianyi Xue; Chao Lin; Ruizhi Hou; Qianyun Xia; Dayong Ding; Jiaqi Li; Dongxu Wang; Ye Feng (Biochemical Genetics, 2023)

Creation of intermuscular bone-free mutants in amphitriploid gibel carp by editing two duplicated runx2b homeologs - Rui-Hai Gan; Zhi Li; Zhong-Wei Wang; Xi-Yin Li; Yang Wang; Xiao-Juan Zhang; Jin-Feng Tong; Yue Wu; Ling-Yun Xia; Ze-Xia Gao; Li Zhou; Jian-Fang Gui (Aquaculture, 2023)

Flexible sensing enabled agri-food cold chain quality control: A review of mechanism analysis, emerging applications, and system integration - Wentao Huang; Xuepei Wang; Jie Xia; Yuliang Li; Luwei Zhang; Huanhuan Feng; Xiaoshuan Zhang (Trends in Food Science & Technology, 2023)

Colorimetric active carboxymethyl chitosan/oxidized sodium alginate-Oxalis triangularis ssp. papilionacea anthocyanins film@gelatin/zein-linalool membrane for milk freshness monitoring and preservation - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Lanhua Liu; Shaotong Jiang; Hualin Wang (Food Chemistry, 2023)

Effects of different monochromatic lights on umami and aroma of dried Suillus granulatus - Yao Feng; Heran Xu; Yiming Fan; Fengming Ma; Bin Du; Yunting Li; Rongrong Xia; Zhenshan Hou; Guang Xin (Food Chemistry, 2023)

Initial water rights allocation of Industry in the Yellow River basin driven by high-quality development - Xiang-nan Chen; Fang Li; Feng-ping Wu; Xia Xu; Yue Zhao (Ecological Modelling, 2023)

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

Resource utilization of hazardous solid waste blast furnace dust: Efficient wet desulfurization and metal recovery - Xuejin Yang; Binghua Xie; Fang Wang; Ping Ning; Kai Li; Lijuan Jia; Jiayu Feng; Futing Xia (Chemosphere, 2023)

Advanced nitrogen and phosphorus removal by the symbiosis of PAOs, DPAOs and DGAOs in a pilot-scale A2O/A+MBR process with a low C/N ratio of influent - Siqi Li; Yu Guo; Xuan Zhang; Liang Feng; Xiaolei Yong; Jing Xu; Yanchen Liu; Xia Huang (Water Research, 2023)

The conserved L1089 in the S2 subunit of avian infectious bronchitis virus determines viral kidney tropism by disrupting virus-cell fusion - Shu-Yun Li; Yu-Xi Shen; Xue-Lian Xiang; Yong-Xin Li; Nian-Ling Li; An-Dong Wang; Min Cui; Xin-Feng Han; Yong Huang; Jing Xia (Veterinary Microbiology, 2023)

Disruption of the lung-gut-brain axis is responsible for cortex damage induced by pulmonary exposure to zinc oxide nanoparticles - Lingbing Zhang; Yandan Zhang; Xuejun Jiang; Lejiao Mao; Yinyin Xia; Yinzhen Fan; Na Li; Ziqi Jiang; Xia Qin; Yu Jiang; Gang Liu; Feng Qiu; et al. (Toxicology, 2023)

Treatment and remediation of metal-contaminated water and groundwater in mining areas by biological sulfidogenic processes: A review - Yu Li; Qingxia Zhao; Ming Liu; Jiahua Guo; Juntao Xia; Jinting Wang; Yanying Qiu; Jiahui Zou; Weiting He; Feng Jiang (Journal of Hazardous Materials, 2023)

Joint effects of per- and polyfluoroalkyl substance alternatives and heavy metals on renal health: A community-based population study in China - Li-Xia Liang; Pengxin Dong; Yang Zhou; Lin Zhang; Zhengmin Qian; Sarah Dee Geiger; Elizabeth Bingheim; Xiaojiang Tang; Yan Wu; Jiayun Lv; Li-Zi Lin; Mohammed Zeeshan; et al. (Environmental Research, 2023)

Absence of water content contrast between lithosphere and asthenosphere in subduction zone - Yuto Sato; Eiichi Takahashi; Chang-Ming Xing; Li Li; Ze-Xian Cui; Wan-Feng Zhang; Xiao-Ping Xia (Earth and Planetary Science Letters, 2023)

Humic acid nature and compound structure together determine the capacity of soil to sorb Avermectin B1a and its derivatives - Tong-fang Jing; Da-xia Zhang; Yan Jin; Guo-dong Si; Bei-xing Li; Wei Mu; Feng Liu (Chemical Engineering Journal, 2023)

The Adsorption and Desorption Behavior of Bisphenol A on Five Microplastics Under Simulated Gastrointestinal Conditions - Hui Jiang; Qiao-ying Li; Jiao-xia Sun; Yu-feng Mao; Xin Liu; Sisi Que; Weiwei Yu; Yi-sen Kan (Water, Air, & Soil Pollution, 2023)

USH2A mutation and specific driver mutation subtypes are associated with clinical efficacy of immune checkpoint inhibitors in lung cancer - Dexin Yang; Yuqin Feng; Haohua Lu; Kelie Chen; Jinming Xu; Peiwei Li; Tianru Wang; Dajing Xia; Yihua Wu (Journal of Zhejiang University-SCIENCE B, 2023)

Roles of Multisourced Fluids in the Formation of Sandstone-Hosted Uranium Deposits in the SW Songliao Basin, NE China - Zhibing Feng; Fengjun Nie; Li Jiang; Fei Xia; Jianfang Cai; Bocheng Zhang; Yayun Lu; Liangliang Zhang (Journal of Earth Science, 2023)

Effects of nitric acid rain stress on soil nitrogen fractions and fungal communities in a northern subtropical forest, China - Meijia Zhou; Haibo Hu; Jinlong Wang; Xia Wang; Ziwei Tian; Wenbing Deng; Chaoming Wu; Li Zhu; Qianwen Lu; Yuanyuan Feng (Science of The Total Environment, 2023)

Phylogeny, character evolution, and biogeography of the fern genus Bolbitis (Dryopteridaceae) - Li-Yun Nie; Liang Zhang; Zhen-Long Liang; Rossarin Pollawatn; Yue-Hong Yan; Ngan Thi Lu; Ralf Knapp; Xia Wan; Daniele Cicuzza; Xin-Xin Cheng; Hong-Feng Chen; Ai-Hua Wang; et al. (Molecular Phylogenetics and Evolution, 2023)

Enhancing flotation removal of unburned carbon from fly ash by coal tar-based collector: Experiment and simulation - Kanghao Zheng; Wenjun Zhang; Yijiang Li; An Ping; Feng Wu; Guangyuan Xie; Wencheng Xia (Fuel, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Causal effect of PM1 on morbidity of cause-specific respiratory diseases based on a negative control exposure - Shiyun Lv; Xiangtong Liu; Zhiwei Li; Feng Lu; Moning Guo; Mengmeng Liu; Jing Wei; Zhiyuan Wu; Siqi Yu; Shihong Li; Xia Li; Wenkang Gao; et al. (Environmental Research, 2023)

Mechanism of excavation-induced cracking of the protective layer of a rock bench in a large underground powerhouse under high tectonic stress - Yuelin Xia; Xia-Ting Feng; Chengxiang Yang; Shaojun Li; Dingping Xu; Quan Jiang; Rui Kong; Yonghong Li; Zhiguo Li (Engineering Geology, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Ethylene-vinyl alcohol copolymer/gelatin/cellulose acetate bionic trilayer fibrous membrane for moisture-adjusting - Li Xia; Linlin Li; Yewen Xiao; Feng Xiao; Wei Ji; Shaotong Jiang; Hualin Wang (Carbohydrate Polymers, 2023)

Retraction Note: Knockdown of long non‑coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA‑15a and repressing ROCK1 expression - Xia Li; Sheng‑Wu Wang; Xi‑Ling LI; Feng‑Yuan Yu; Hai‑Ming Cong (Inflammation Research, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Evolution of Meteorological Conditions during a Heavy Air Pollution Event under the Influence of Shallow Foehn in Urumqi, China - Xia Li; Keming Zhao; Shiyuan Zhong; Xiaojing Yu; Zhimin Feng; Yuting Zhong; Ayitken Maulen; Shuting Li (Advances in Atmospheric Sciences, 2023)

Bearing performance of steel pipe pile in multilayered marine soil using fiber optic technique: A case study - Sheng-Hua Xu; Zheng-Wu Li; Yong-Feng Deng; Xia Bian; Hong-Hu Zhu; Feng Zhou; Qi Feng (Marine Georesources & Geotechnology, 2022)

A Novel 3D Printing Technology for Synthetic Hard Rock and the Fabrication of Jinping Marble - Shiming Mei; Xia-Ting Feng; Zhengwei Li; Chengxiang Yang; Jikai Gao (Rock Mechanics and Rock Engineering, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Development of diagnostic molecular markers to differentiate sharp eyespot and Fusarium crown rot isolates collected from common wheat fields in China - Yan Ren; Yue Wang; Li-yan Wang; Xia-Lei Lv; Ti Liu; Jing-yun Nie; Peng Guo; Lin Ma; Xiao-nan Sun; Feng Chen (Phytoparasitica, 2022)

Ecological Benefit Analysis of Urban Green Space Based on Three-Dimensional Green Quantity - Feng-xia Li; Meng Li; Xiao-gang Feng (Journal of the Indian Society of Remote Sensing, 2022)

Preparation of Pinocembrin-Loaded F127/MPEG-PDLLA Polymer Micelles and Anti-Osteoporotic Activity - Xia Cao; Qing He; Michael Adu-Frimpong; Xinyi Shen; Wanjing Rong; Xiaoxiao Li; Jian Zhang; Xiaoli Xia; Feng Shi; Hao Ji; Elmurat Toreniyazov; Qilong Wang; et al. (AAPS PharmSciTech, 2022)

The Location Reliability of the Resting-State fMRI FC of Emotional Regions Towards rTMS Therapy - Na Zhao; Juan Yue; Zi-Jian Feng; Yang Qiao; Qiu Ge; Li-Xia Yuan; Jue Wang; Yu-Tao Xiang; Yu-Feng Zang (Neuroinformatics, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

New oxindole alkaloids with selective osteoclast inhibitory activity from Gelsemium elegans - Xin Wei; Xiao-Teng Huang; Li-Yan Zhang; Xin-Yue Hu; Wei Zhang; Yong-Qiang Zhou; Hao-Fei Yu; Cai-Feng Ding; Lan-Chun Zhang; Xia Liu; Ying Zhou (Natural Product Research, 2022)

Multiple indeterminate domain (IDD)–DELLA1 complexes participate in gibberellin feedback regulation in peach - Yajun Jiang; Jiajia Chen; Xianbo Zheng; Bin Tan; Xia Ye; Wei Wang; Langlang Zhang; Jidong Li; Zhiqian Li; Jun Cheng; Jiancan Feng (Plant Molecular Biology, 2022)

ALKBH5 promotes the progression of infantile hemangioma through regulating the NEAT1/miR-378b/FOSL1 axis - Kun Peng; Ren-Peng Xia; Fan Zhao; Yong Xiao; Ti-Dong Ma; Ming Li; Yong Feng; Chong-Gao Zhou (Molecular and Cellular Biochemistry, 2022)

Geochemical characteristics and growth suitability assessment of Scutellaria baicalensis Georgi in the Earth’s critical zone of North China - Xia Li; Xiao-feng Wei; Jin Wu; Zhi-qiang Yin; Li-qin Wan; Hou-yun Sun; Yong-long An (Journal of Mountain Science, 2022)

Streptomyces griseicoloratus sp. nov., isolated from soil in cotton fields in Xinjiang, China - Li Xing; Ying-ying Xia; Qiao-Yan Zhang; Zhan-Feng Xia; Chuan-xing Wan; Li-li Zhang; Xiao-Xia Luo (Archives of Microbiology, 2022)

Genome-wide CRISPR activation screen identifies candidate receptors for SARS-CoV-2 entry - Shiyou Zhu; Ying Liu; Zhuo Zhou; Zhiying Zhang; Xia Xiao; Zhiheng Liu; Ang Chen; Xiaojing Dong; Feng Tian; Shihua Chen; Yiyuan Xu; Chunhui Wang; et al. (Science China Life Sciences, 2022)

Characterization of Photorhabdus Virulence Cassette as a causative agent in the emerging pathogen Photorhabdus asymbiotica - Xia Wang; Jiaxuan Cheng; Jiawei Shen; Liguo Liu; Ningning Li; Ning Gao; Feng Jiang; Qi Jin (Science China Life Sciences, 2022)

Genome-wide identification and expression of the lipoxygenase gene family in jujube (Ziziphus jujuba) in response to phytoplasma infection - Jidong Li; Lichuan Chen; Peng Chen; Qicheng Li; Qiqi Yang; Yu Zhang; Bin Tan; Xia Ye; Xianbo Zheng; Jiancan Feng (Journal of Plant Biochemistry and Biotechnology, 2022)

Same total normal forms sperm counts of males from Lhasa and Shanghai, China - Benhong Gu; Shangren Wang; Feng Liu; Yuxuan Song; Jun Li; Yongtao Ni; Min Chen; Jianlin Hu; Luobu Ouzhu; Zheng Li; Li Liu; Xia Li; et al. (Environmental Science and Pollution Research, 2022)

Identification and bioinformatics analysis of differentially expressed milk exosomal microRNAs in milk exosomes of heat-stressed Holstein cows - Yue Wang; Jian Fang; Han-Fang Zeng; Ji-Feng Zhong; Hui-Xia Li; Kun-Lin Chen (Functional & Integrative Genomics, 2022)

AgMYB12, a novel R2R3-MYB transcription factor, regulates apigenin biosynthesis by interacting with the AgFNS gene in celery - Hao Wang; Jie-Xia Liu; Kai Feng; Tong Li; Ao-Qi Duan; Yan-Hua Liu; Hui Liu; Ai-Sheng Xiong (Plant Cell Reports, 2022)

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

miR-21 Exerts Anti-proliferative and Pro-apoptotic Effects in LPS-induced WI-38 Cells via Directly Targeting TIMP3 - Jin-Xiu Li; You Li; Tian Xia; Feng-Yan Rong (Cell Biochemistry and Biophysics, 2021)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Anticancer activity of oleiferoside B involving autophagy and apoptosis through increasing ROS release in MCF-7 cells and SMMC-7721 cells - Suxiang Feng; Zhengxia Zha; Zhe Wang; Ping Yang; Jiangping Wu; Xia Li; Qiongming Xu; Yanli Liu (Natural Product Research, 2021)

Alkaloids with acetylcholinesterase inhibitory activity from Corydalis racemosa (Thunb.) Pers - Hui-Na Yao; Zhi-Tian Peng; Yun-Feng Zhang; Di-Fa Liu; Bing-Feng Huang; Peng-Fei Tu; Yun-Fang Zhao; Hui-Xia Huo; Jun Li (Natural Product Research, 2021)

Reduced acetylcholine and elevated muscarinic receptor 2 in duodenal mucosa contribute to the impairment of mucus secretion in 6-hydroxydopamine-induced Parkinson’s disease rats - Jing-Ting Yan; Xiao-Yu Liu; Jing-Hua Liu; Guang-Wen Li; Li-Fei Zheng; Xiao-Li Zhang; Yue Zhang; Xiao-Yan Feng; Jin-Xia Zhu (Cell and Tissue Research, 2021)

Pharmacological Activation of RXR-α Promotes Hematoma Absorption via a PPAR-γ-dependent Pathway After Intracerebral Hemorrhage - Chaoran Xu; Huaijun Chen; Shengjun Zhou; Chenjun Sun; Xiaolong Xia; Yucong Peng; Jianfeng Zhuang; Xiongjie Fu; Hanhai Zeng; Hang Zhou; Yang Cao; Qian Yu; et al. (Neuroscience Bulletin, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

The glutathione S-transferase (PxGST2L) may contribute to the detoxification metabolism of chlorantraniliprole in Plutella xylostella(L.) - Fei Yin; Qingsheng Lin; Xiaoxiang Wang; Zhenyu Li; Xia Feng; Muhammad Zeeshan Shabbir (Ecotoxicology, 2021)
The diamondback moth ( Plutella xylostella L.), is an economic pest of cruciferous plants worldwide, which causes great economic loss to cruciferous plants production. However, the pest has developed resistance to insecticides. One of such insecticides is chlorantraniliprole. The study of the mechanisms underlying resistance is key for the effective management of resistance. In this study, a comparative proteomics approach was used to isolate and identify various proteins that differed between chlorantraniliprole-susceptible and -resistant strains of P. xylostella . Eleven proteins were significantly different and were successfully identified by MALDI-TOF-MS. Metabolism-related proteins accounted for the highest proportion among the eleven different proteins. The function of the PxGST2L protein was validated by RNAi. Knockdown of PxGST2L reduced the GST activity and increased the toxicity of chlorantraniliprole to the diamondback moth. The resistance ratio of diamondback moth to chlorantraniliprole was reduced from 1029 to 505. The results indicated that PxGST2L is partly responsible for chlorantraniliprole insecticide resistance in DBM. Our finding contributes to the understanding of the mechanism underlying resistance to chlorantraniliprole in the DBM, to develop effective resistance management tactics.

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

High-Precision Method for Estimating the Three-Dimensional Green Quantity of an Urban Forest - Feng-xia Li; Meng Li; Xiao-gang Feng (Journal of the Indian Society of Remote Sensing, 2021)

Overcoming diverse homologous recombinations and single chimeric guide RNA competitive inhibition enhances Cas9‐based cyclical multiple genes coediting in filamentous fungi - Youzhi Miao; Yanwei Xia; Yanqiong Kong; Han Zhu; Huiling Mei; Pan Li; Haichao Feng; Weibing Xun; Zhihui Xu; Nan Zhang; Dongyang Liu; Qirong Shen; et al. (Environmental Microbiology, 2021)
Summary Deciphering the complex cellular behaviours and advancing the biotechnology applications of filamentous fungi increase the requirement for genetically manipulating a large number of target genes. The current strategies cannot cyclically coedit multiple genes simultaneously. In this study, we firstly revealed the existence of diverse homologous recombination (HR) types in marker‐free editing of filamentous fungi, and then, demonstrated that sgRNA efficiency‐mediated competitive inhibition resulted in the low integration of multiple genetic sites during coediting, which are the two major obstacles to limit the efficiency of cyclically coediting of multiple genes. To overcome these obstacles, we developed a biased cutting strategy by Cas9 to greatly enhance the desired HR type and applied a new selection marker labelling strategy for multiple donor DNAs, in which only the donor DNA with the lowest sgRNA efficiency was labelled. Combined with these strategies, we successfully developed a convenient method for cyclically coediting multiple genes in different filamentous fungi. In addition, diverse HRs resulted in a useful and convenient one‐step approach for gene functional study combining both gene disruption and complementation. This research provided both a useful one‐step approach for gene functional study and an efficient strategy for cyclically coediting multiple genes in filamentous fungi.

Two novel diterpenes from the stems and leaves of tropical seagrass Enhalus acoroides in the South China sea - Xiao-Bing Wang; Zhong-Hao Sun; Li-Xia Fan; Yang-Yang Liu; Jian Feng; Guo-Xu Ma; De-Li Chen (Natural Product Research, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Distribution and Assessment of Cr, Pb, Ni and Cd in Topsoil of the Modern Yellow River Delta, China - Hongjun Yang; Jingkuan Sun; Jiangbao Xia; Zhanyong Fu; Shuai Cheng; Tian Li; Pengshuai Shao; Kaikai Dong; Jinzhao Ma; Lu Feng (Wetlands, 2021)

Polyamine oxidase (PAO)–mediated polyamine catabolism plays potential roles in peach (Prunus persica L.) fruit development and ripening - Wei Wang; Xianbo Zheng; Shihao Liu; Bin Tan; Jun Cheng; Xia Ye; Jidong Li; Jiancan Feng (Tree Genetics & Genomes, 2021)

Long-term Outcomes and Risk Factors Related to Hydrocephalus After Intracerebral Hemorrhage - Rong Hu; Chao Zhang; Jiesheng Xia; Hongfei Ge; Jun Zhong; Xuanyu Fang; Yongjie Zou; Chuan Lan; Lan Li; Hua Feng (Translational Stroke Research, 2021)

Construction and characterization of UAA-controlled recombinant Zika virus by genetic code expansion - Rong-Rong Zhang; Qing Ye; Xiao-Feng Li; Yong-Qiang Deng; Yan-Peng Xu; Xing-Yao Huang; Qing Xia; Cheng-Feng Qin (Science China Life Sciences, 2021)

A celery transcriptional repressor AgERF8 negatively modulates abscisic acid and salt tolerance - Jie-Xia Liu; Bei Wu; Kai Feng; Meng-Yao Li; Ao-Qi Duan; Di Shen; Lian Yin; Zhi-Sheng Xu; Ai-Sheng Xiong (Molecular Genetics and Genomics, 2021)

Association of ADH7 Gene Polymorphism with Schizophrenia in the Han Population of Northern China: a Case-Control Study - Kuo Zeng; Ya Li; Meng Gao; Yong-ping Liu; Feng-ling Xu; Xi Xia; Jun Yao; Bao-jie Wang (Journal of Molecular Neuroscience, 2020)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

Spatial–temporal evolutions of groundwater environment in prairie opencast coal mine area: a case study of Yimin Coal Mine, China - Shaogang Dong; Haibo Feng; Manhong Xia; Yi Li; Chao Wang; Lei Wang (Environmental Geochemistry and Health, 2020)

Depletion of florfenicol and florfenicol amine in eggs of laying hens and growing pullets after oral administration - Xia Li; Lu Chen; Hui Yue; Hua Feng; Enmin Xu; Xiuli Wei; Xiaoli Han; Ligang Deng; Zengmei Li (Food Additives & Contaminants: Part A, 2020)

Archaeobotanical evidence reveals the human–environment interactions during the 9th–13th centuries at Turpan, Xinjiang on the ancient Silk Road - Yi-Feng Yao; Xia Wang; Wu Guo; Hong-En Jiang; Min Li; David K. Ferguson; Yu-Fei Wang; Cheng-Sen Li (Vegetation History and Archaeobotany, 2020)

Comparative analysis of the transcriptome, methylome, and metabolome during pollen abortion of a seedless citrus mutant - Li-Xia Ye; Zhi-Meng Gan; Wen-Feng Wang; Xiao-Yan Ai; Zong-Zhou Xie; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology, 2020)

Tyrosine Hydroxylase Gene Polymorphisms Contribute to Opioid Dependence and Addiction by Affecting Promoter Region Function - Jun-lin Liu; Shao-qing Li; Feng Zhu; Yu-xiang Zhang; Ya-nan Wu; Jing-si Yang; Bao Zhang; Chun-xia Yan (NeuroMolecular Medicine, 2020)

Correction to: Long non-coding RNA H19 promotes osteogenic differentiation of renal interstitial fibroblasts through Wnt-β-catenin pathway - Zewu Zhu; Yu Cui; Fang Huang; Huimin Zeng; Weiping Xia; Feng Zeng; Cheng He; Jinbo Chen; Zhiyong Chen; Hequn Chen; Yang Li (Molecular and Cellular Biochemistry, 2020)

RETRACTED ARTICLE: Knockdown of long non-coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA-15a and repressing ROCK1 expression - Xia Li; Sheng-Wu Wang; Xi-Ling LI; Feng-Yuan Yu; Hai-Ming Cong (Inflammation Research, 2020)

Pentamidine sensitizes FDA-approved non-antibiotics for the inhibition of multidrug-resistant Gram-negative pathogens - Chenxuan Wu; Ling Xia; Wei Huang; Yangfan Xu; Yuanxin Gu; Chang Liu; Luting Ji; Wenyao Li; Yandong Wu; Kai Zhou; Xinxin Feng (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Retraction Note to: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng‑Jin Guo (Histochemistry and Cell Biology, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Benzophenone glycosides from the pericarps of Aquilaria yunnanensis S. C. Huang - Hui Sun; Yun-Feng Zhang; Hui-Xia Huo; Peng-Wei Guan; Chao-Chao Wang; Hui-Na Yao; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Long non-coding RNA H19 promotes osteogenic differentiation of renal interstitial fibroblasts through Wnt-β-catenin pathway - Zewu Zhu; Yu Cui; Fang Huang; Huimin Zeng; Weiping Xia; Feng Zeng; Cheng He; Jinbo Chen; Zhiyong Chen; Hequn Chen; Yang Li (Molecular and Cellular Biochemistry, 2020)

A novel hydrogel for highly efficient adsorption of Cu(II): synthesis, characterization, and mechanisms - Jun Wan; Lin Chen; Qiang Li; Yuxuan Ye; Xiaonan Feng; Aijiao Zhou; Xuejun Long; Dongsheng Xia; Tian C. Zhang (Environmental Science and Pollution Research, 2020)

Streptomyces taklimakanensis sp. nov., an actinomycete isolated from the Taklimakan desert - Lin-Lin Yuan; Li-Li Zhang; Xiao-Xia Luo; Zhan-Feng Xia; Bei-Bei Sun; Hong Zeng (Antonie van Leeuwenhoek, 2020)

Antifungal, anti-inflamatory and neuritogenic activity of newly-isolated compounds from Disporopsis aspersa - Fang-Li Gang; Feng Zhu; Chao-Fu Yang; Xiao-Ting Li; Hua Yang; Ming-Xia Sun; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2020)

Chemical constituents from the deep sea-derived Streptomyces xiamenensis MCCC 1A01570 and their effects on RXRα transcriptional regulation - Wei-Xiang Lin; Chun-Lan Xie; Mi Zhou; Man-Li Xia; Ting-Ting Zhou; Hai-Feng Chen; Xian-Wen Yang; Quan Yang (Natural Product Research, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Heat stress induces apoptosis through disruption of dynamic mitochondrial networks in dairy cow mammary epithelial cells - Kun-Lin Chen; Hui-Li Wang; Lin-Zheng Jiang; Yong Qian; Cai-Xia Yang; Wei-Wei Chang; Ji-Feng Zhong; Guang-Dong Xing (In Vitro Cellular & Developmental Biology - Animal, 2020)

Effect of Mechanical Damage on the Thermal Conductivity of Granite - Zheng-Wei Li; Xia-Ting Feng; Yan-Jun Zhang; Yan-Hua Gong; Guo-Qiang Zhu (Rock Mechanics and Rock Engineering, 2020)

Physical Model Experimental Study on Spalling Failure Around a Tunnel in Synthetic Marble - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Lian-Jie Fu; Yong-Run Xiong (Rock Mechanics and Rock Engineering, 2020)

Augmentation of danusertib’s anticancer activity against melanoma by blockage of autophagy - Yuan-Yuan Shang; Nan Yu; Li Xia; Ying-Yao Yu; Chun-mei Ma; Ya-Ning Jiao; Yun-feng Li; Yuan Wang; Jie Dang; Weichao Li (Drug Delivery and Translational Research, 2020)

Grain protein content comparison and proteomic analysis of foxtail millet (Setaria italica L.) seed response to different drought stress levels - Binqin Xu; Xiaoli Gao; Kongjun Dong; Xia Li; Pu Yang; Tianyu Yang; Baili Feng (Acta Physiologiae Plantarum, 2020)

An improved minimum bounding rectangle algorithm for regularized building boundary extraction from aerial LiDAR point clouds with partial occlusions - Maolin Feng; Tonggang Zhang; Shichao Li; Guoqing Jin; Yanjun Xia (International Journal of Remote Sensing, 2020)

MiR-506-3p suppresses the proliferation of ovarian cancer cells by negatively regulating the expression of MTMR6 - Yuan Wang; Xia Lei; Chengying Gao; Yanxia Xue; Xiaolin Li; Haiying Wang; Yan Feng (Journal of Biosciences, 2019)

Comparative transcript profiling and cytological observation of the newly bred recessive genic male sterility non-heading Chinese cabbage (Brassica rapa ssp. chinensis) line WS24-3A - Liping Song; Xia Li; Feng Zu; Changbin Gao; Bincai Wang; Chufa Lin; Jinxing Tu; Aihua Wang; Guolin Zhou (Genes & Genomics, 2019)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Antagonistic activity and protective effect of a Bacillus subtilis isolate against fish pathogen Edwardsiella piscicida - Xiaomeng Ren; Binbin Wu; Feng Zhao; Lingling Qi; Xianfeng Qiu; Ran Li; Sisi Yang; Fuguo Liu; Ganfeng Yi; Xuezhi Ding; Liqiu Xia; Yunjun Sun (Fisheries Science, 2019)

Genomic identification of AP2/ERF transcription factors and functional characterization of two cold resistance-related AP2/ERF genes in celery (Apium graveolens L.) - Meng-Yao Li; Jie-Xia Liu; Jian-Nan Hao; Kai Feng; Ao-Qi Duan; Qing-Qing Yang; Zhi-Sheng Xu; Ai-Sheng Xiong (Planta, 2019)

The prevalence and genetic diversity of porcine circovirus types 2 and 3 in Northeast China from 2015 to 2018 - Deli Xia; Liping Huang; Yongxing Xie; Xiaoqian Zhang; Yanwu Wei; Dan Liu; Hongzhen Zhu; Haiqiao Bian; Li Feng; Changming Liu (Archives of Virology, 2019)

The Microwave-Induced Fracturing of Hard Rock - Gao-Ming Lu; Xia-Ting Feng; Yuan-Hui Li; Xiwei Zhang (Rock Mechanics and Rock Engineering, 2019)

Cloning and Analysis of Genes Controlling Antibacterial Activities of Burkholderia pyrrocinia Strain Lyc2 - Xiaoqiang Wang; Dexin Chen; Jing Wang; Chao Feng; Wenjing Wang; Wei Zhang; Bin Li; Jiamin Yu; Bo Xia (Current Microbiology, 2019)

Experimental Investigation on the Effects of Microwave Treatment on Basalt Heating, Mechanical Strength, and Fragmentation - Gao-Ming Lu; Xia-Ting Feng; Yuan-Hui Li; Ferri Hassani; Xiwei Zhang (Rock Mechanics and Rock Engineering, 2019)

Development of a reverse genetics system for Japanese encephalitis virus strain SA14-14-2 - Guohua Li; Hongli Jin; Xin Nie; Yongkun Zhao; Na Feng; Zongxi Cao; Shuyi Tan; Bo Zhang; Weiwei Gai; Feihu Yan; Ling Li; Ying Zhang; et al. (Virus Genes, 2019)

Synergistic deletion of RGS1 and COS1 may reduce the pathogenicity of Magnaporthe oryzae - He Na; An Bang; Xie Qing-biao; Yan Xia; Feng Hui-min; Luo Hong-li; He Chao-zu (Archives of Microbiology, 2019)

Outline of the biosynthesis and regulation of ergosterol in yeast - Jun-Feng Liu; Jun-Jie Xia; Kai-Li Nie; Fang Wang; Li Deng (World Journal of Microbiology and Biotechnology, 2019)

The 3D-Printing Technology of Geological Models Using Rock-Like Materials - Xia-Ting Feng; Yan-Hua Gong; Yang-Yi Zhou; Zheng-Wei Li; Xu-Feng Liu (Rock Mechanics and Rock Engineering, 2019)

Experimental Study to Design an Analog Material for Jinping Marble with High Strength, High Brittleness and High Unit Weight and Ductility - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Cheng-Xiang Yang; Yao-Hui Gao (Rock Mechanics and Rock Engineering, 2019)

Inhibitor of ghrelin receptor reverses gefitinib resistance in lung cancer - Xiaoyou Li; Xia Zhao; Chenchen Li; Siwen Liu; Fei Yan; Yue Teng; Jifeng Feng; Dengshun Miao (Human Cell, 2019)

ISRM Suggested Method: Determining Deformation and Failure Characteristics of Rocks Subjected to True Triaxial Compression - Xia-Ting Feng; Bezalel Haimson; Xiaochun Li; Chandong Chang; Xiaodong Ma; Xiwei Zhang; Mathew Ingraham; Kenichiro Suzuki (Rock Mechanics and Rock Engineering, 2019)

Genome-wide identification of Ziziphus jujuba TCP transcription factors and their expression in response to infection with jujube witches’ broom phytoplasma - Peng Chen; Jidong Li; Xia Ye; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Huiyu Wang; Liyuan Gu; Jiancan Feng (Acta Physiologiae Plantarum, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

OsCDC48/48E complex is required for plant survival in rice (Oryza sativa L.) - Lei Shi; Xiao-bo Zhang; Yong-feng Shi; Xia Xu; Yuqing He; Guosheng Shao; Qi-na Huang; Jian-li Wu (Plant Molecular Biology, 2019)

Diltiazem used as a tacrolimus-sparing agent for treatment of pediatric patients with refractory nephrotic syndrome: a case report and retrospective analysis - Jie-Yu Sun; Ya-Hui Hu; Hong-Li Guo; Xia Jing; Ze-Jun Xu; Fang Sun; Hui-Lei Guo; Xuan-Sheng Ding; Feng Chen; Jing Xu (European Journal of Clinical Pharmacology, 2019)

The dominant role of the atmospheric component of coupled models in ENSO amplitude simulations - Yanli Tang; Lijuan Li; Bin Wang; Pengfei Lin; Lin Chen; Feng Xie; Wenjie Dong; Kun Xia (Climate Dynamics, 2019)

Emerging role of circadian rhythm in bone remodeling - Qian-Yuan Wu; Jian Wang; Xiao Tong; Jie Chen; Bei Wang; Zong-Ning Miao; Xia Li; Jun-Xing Ye; Feng-Lai Yuan (Journal of Molecular Medicine, 2019)

Effects of long-term coastal reclamation on suitable habitat and wintering population size of the endangered Red-crowned Crane, Grus japonensis - Ning Li; Zheng Wang; Lu Xia; Feng Yan; Ling-qian Xu; Ya-jun Qiao; Xin-hai Li; Shu-qing An; Shu-bo Fang (Hydrobiologia, 2019)

A case control study on the prevalence of enterovirus in children samples and its association with diarrhea - Xin-xin Shen; Fang-zhou Qiu; Gui-xia Li; Meng-chuan Zhao; Ji Wang; Chen Chen; Li Zhao; Ju-Ju Qi; Hong Liu; Yi Zhang; Xiao-zhou He; Le Wang; et al. (Archives of Virology, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Characteristic Stress Levels and Brittle Fracturing of Hard Rocks Subjected to True Triaxial Compression with Low Minimum Principal Stress - Yao-Hui Gao; Xia-Ting Feng; Xi-Wei Zhang; Guang-Liang Feng; Quan Jiang; Shi-Li Qiu (Rock Mechanics and Rock Engineering, 2018)

P2X4R promotes airway remodeling by acting on the phenotype switching of bronchial smooth muscle cells in rats - Li Wang; Xiaoqian Feng; Bing Hu; Qingqing Xia; Xiuqin Ni; Yinli Song (Purinergic Signalling, 2018)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Contourlet-based hippocampal magnetic resonance imaging texture features for multivariant classification and prediction of Alzheimer’s disease - Ni Gao; Li-Xin Tao; Jian Huang; Feng Zhang; Xia Li; Finbarr O’Sullivan; Si-Peng Chen; Si-Jia Tian; Gehendra Mahara; Yan-Xia Luo; Qi Gao; Xiang-Tong Liu; et al. (Metabolic Brain Disease, 2018)

Suboptimal health status and psychological symptoms among Chinese college students: a perspective of predictive, preventive and personalised health - Haifeng Hou; Xia Feng; Yuejin Li; Zixiu Meng; Dongmei Guo; Fang Wang; Zheng Guo; Yulu Zheng; Zhiqi Peng; Wangxin Zhang; Dong Li; Guoyong Ding; et al. (EPMA Journal, 2018)

Functional brain abnormalities in major depressive disorder using the Hilbert-Huang transform - Haibin Yu; Feng Li; Tong Wu; Rui Li; Li Yao; Chuanyue Wang; Xia Wu (Brain Imaging and Behavior, 2018)

Two new alkylated furan derivatives with antifungal and antibacterial activities from the plant endophytic fungus Emericella sp. XL029 - Xia Wu; Xue-Jiao Pang; Lu-Lin Xu; Ting Zhao; Xin-Yu Long; Qiong-Yin Zhang; Hai-Li Qin; Deng-Feng Yang; Xiao-Long Yang (Natural Product Research, 2018)

AgMYB2 transcription factor is involved in the regulation of anthocyanin biosynthesis in purple celery (Apium graveolens L.) - Kai Feng; Jie-Xia Liu; Ao-Qi Duan; Tong Li; Qing-Qing Yang; Zhi-Sheng Xu; Ai-Sheng Xiong (Planta, 2018)

A Bayesian modeling approach for phosphorus load apportionment in a reservoir with high water transfer disturbance - Xia Liu; Yuan Wang; Jianfeng Feng; Chunli Chu; Yu Qiu; Ze Xu; Zeli Li; Yuqiu Wang (Environmental Science and Pollution Research, 2018)

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study - Fei Wang; Li Wang; Ting-ting Jiang; Jian-jun Xia; Feng Xu; Li-juan Shen; Wen-hui Kang; Yong Ding; Li-xia Mei; Xue-feng Ju; Shan-you Hu; Xiao Wu (Neurotoxicity Research, 2018)

The complete chloroplast genome sequence of an endangered Orchidaceae species Dendrobium monilforme and its phylogenetic implications - Yan-xia Gao; Yu-yan Zhou; Ying Xie; Li Feng; Shi-gang Shen (Conservation Genetics Resources, 2018)

Feasibility Investigation of 3D Printing Technology for Geotechnical Physical Models: Study of Tunnels - Leibo Song; Quan Jiang; Ying-En Shi; Xia-Ting Feng; Yuanhui Li; Fangsheng Su; Chang Liu (Rock Mechanics and Rock Engineering, 2018)

Carotenoid Accumulation and Distinct Transcript Profiling of Structural Genes Involved in Carotenoid Biosynthesis in Celery - Jing-Wen Li; Jing Ma; Kai Feng; Jie-Xia Liu; Feng Que; Ai-Sheng Xiong (Plant Molecular Biology Reporter, 2018)

Neonatal Exposure to Low-Dose (1.2%) Sevoflurane Increases Rats’ Hippocampal Neurogenesis and Synaptic Plasticity in Later Life - Xi Chen; Xue Zhou; Lu Yang; Xu Miao; Di-Han Lu; Xiao-Yu Yang; Zhi-Bin Zhou; Wen-Bin Kang; Ke-Yu Chen; Li-Hua Zhou; Xia Feng (Neurotoxicity Research, 2018)

An environmental flow assessment of a river’s blocking effect on a lake in a river-lake system: application in the Yangtze-Poyang system - Feng Huang; Yao Wu; Bao Qian; Lidan Guo; Dayong Zhao; Li Ren; Ziqiang Xia (Environmental Monitoring and Assessment, 2018)

Active pharmacovigilance in China: recent development and future perspectives - Xinling Li; Haona Li; Jianxiong Deng; Feng Zhu; Ying Liu; Wenge Chen; Zhihua Yue; Xuequn Ren; Jielai Xia (European Journal of Clinical Pharmacology, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Isolation, purification, and characterization of AgUCGalT1, a galactosyltransferase involved in anthocyanin galactosylation in purple celery (Apium graveolens L.) - Kai Feng; Zhi-Sheng Xu; Jie-Xia Liu; Jing-Wen Li; Feng Wang; Ai-Sheng Xiong (Planta, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Ecological risk assessment of the Gannan Plateau, northeastern Tibetan Plateau - Dong-xia Yue; Jian-jun Zeng; Chao Yang; Ming-liang Zou; Kai Li; Guan-guang Chen; Jian-jun Guo; Xiao-feng Xu; Xing-min Meng (Journal of Mountain Science, 2018)

Chloroplast genome sequence of the endangered Orchidaceae species Dendrobium hancockii - Yan-xia Gao; Yu-yan Zhou; Ying Xie; Li Feng; Shi-gang Shen (Conservation Genetics Resources, 2018)

Complete plastid genome of Larix potaninii var. macrocarpa, an endangered conifer endemic to China - Dai-Yu Qiu; Jiao Yang; Li Feng; Ding-Wen Ni; Cai-Xia Huang; Zhong-Hu Li (Conservation Genetics Resources, 2018)

Sevoflurane Affects Oxidative Stress and Alters Apoptosis Status in Children and Cultured Neural Stem Cells - Xue Zhou; Dihan Lu; Wen-da Li; Xiao-hui Chen; Xiao-yu Yang; Xi Chen; Zhi-bin Zhou; Jiang-Hong Ye; Xia Feng (Neurotoxicity Research, 2018)

Gene expression profiling of human hepatocytes grown on differing substrate stiffness - Tingting Xia; Runze Zhao; Fan Feng; Yijiang Song; Yu Zhang; Lili Dong; Yonggang Lv; Li Yang (Biotechnology Letters, 2018)

In Situ Observation of Rock Spalling in the Deep Tunnels of the China Jinping Underground Laboratory (2400 m Depth) - Xia-Ting Feng; Hong Xu; Shi-Li Qiu; Shao-Jun Li; Cheng-Xiang Yang; Hao-Sen Guo; Yuan Cheng; Yao-Hui Gao (Rock Mechanics and Rock Engineering, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

Network analysis of microRNAs, transcription factors, and target genes involved in axon regeneration - Li-ning Su; Xiao-qing Song; Zhan-xia Xue; Chen-qing Zheng; Hai-feng Yin; Hui-ping Wei (Journal of Zhejiang University-SCIENCE B, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

The effects of rainfall regimes and terracing on runoff and erosion in the Three Gorges area, China - Qin-xue Xu; Pan Wu; Jun-feng Dai; Tian-wei Wang; Zhao-xia Li; Chong-fa Cai; Zhi-hua Shi (Environmental Science and Pollution Research, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

A new diarylheptanoid from Alpinia officinarum promotes the differentiation of 3T3-L1 preadipocytes - Xuguang Zhang; Xiaopo Zhang; Yong Wang; Feng Chen; Youbin Li; Yonghui Li; Yinfeng Tan; Jingwen Gong; Xia Zhong; Hailong Li; Junqing Zhang (Natural Product Research, 2018)

In Situ Observation of Hard Surrounding Rock Displacement at 2400-m-Deep Tunnels - Xia-Ting Feng; Zhi-Bin Yao; Shao-Jun Li; Shi-Yong Wu; Cheng-Xiang Yang; Hao-Sen Guo; Shan Zhong (Rock Mechanics and Rock Engineering, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Restoration of SMN expression in mesenchymal stem cells derived from gene-targeted patient-specific iPSCs - Mai Feng; Cong Liu; Yan Xia; Bo Liu; Miaojin Zhou; Zhuo Li; Qianru Sun; Zhiqing Hu; Yanchi Wang; Lingqian Wu; Xionghao Liu; Desheng Liang (Journal of Molecular Histology, 2018)

Dietary Iodine Affected the GSH-Px to Regulate the Thyroid Hormones in Thyroid Gland of Rex Rabbits - Feng Qin; Xiaoqing Pan; Jie Yang; Sheng Li; Le Shao; Xia Zhang; Beiyi Liu; Jian Li (Biological Trace Element Research, 2018)

Optimisation of steam distillation extraction oil from onion by response surface methodology and its chemical composition - Zhao Dan Wang; Li Hua Li; Hui Xia; Feng Wang; Li Gang Yang; Shao Kang Wang; Gui Ju Sun (Natural Product Research, 2018)

Integrated in silico–in vitro screening of ovarian cancer peroxisome proliferator-activated receptor-γ agonists against a biogenic compound library - Gui-Lian Zhang; Feng-Ying Liu; Jing Zhang; Li-Ping Wang; Er-Xia Jia; Shi-Ming Lv (Medicinal Chemistry Research, 2018)

C21 steroid derivatives from the Dai herbal medicine Dai-Bai-Jie, the dried roots of Marsdenia tenacissima, and their screening for anti-HIV activity - Xu Pang; Li-Ping Kang; Xiao-Mei Fang; He-Shui Yu; Li-Feng Han; Yang Zhao; Li-Xia Zhang; Li-Yan Yu; Bai-Ping Ma (Journal of Natural Medicines, 2018)

Release and kinetics of arsenic and plumbum in the Songhua River surficial sediments - Guang-Min Liu; Qing An; Li-Juan Wang; Xin Jia; Si-Hui Feng; Shu-Mei Xia; Yi-Ning Wu; Hong Qi (Environmental Science and Pollution Research, 2018)

Large-scale hatchery of the kelp Saccharina japonica: a case study experience at Lvshun in northern China - Li Su; Shao Jun Pang; Ti Feng Shan; Xia Li (Journal of Applied Phycology, 2017)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

RETRACTED ARTICLE: ISRM Suggested Method for Determining Stress–Strain Curves for Rocks Under True Triaxial Compression - Xiwei Zhang; Xia-Ting Feng; Xiaochun Li; Bezalel Haimson; Kenichiro Suzuki (Rock Mechanics and Rock Engineering, 2017)

Pterostilbene Attenuates Early Brain Injury Following Subarachnoid Hemorrhage via Inhibition of the NLRP3 Inflammasome and Nox2-Related Oxidative Stress - Haixiao Liu; Lei Zhao; Liang Yue; Bodong Wang; Xia Li; Hao Guo; Yihui Ma; Chen Yao; Li Gao; Jianping Deng; Lihong Li; Dayun Feng; et al. (Molecular Neurobiology, 2017)

Hsa_circ_0045714 regulates chondrocyte proliferation, apoptosis and extracellular matrix synthesis by promoting the expression of miR-193b target gene IGF1R - Bao-feng Li; Ying Zhang; Jin Xiao; Fei Wang; Mei Li; Xiao-ze Guo; Hui-bin Xie; Hong Xia; Bei Chen (Human Cell, 2017)

Farnesol, a synomone component between lantana (Lamiales: Verbenaceae) and the omnivorous predator, Campylomma chinensis Schuh (Hemiptera: Miridae) - Feng-Mei Ma; Li-Xia Zheng; Ze-Zheng Gao; Wei-Jian Wu (Arthropod-Plant Interactions, 2017)

Transcriptomic insights into the alternative splicing‐mediated adaptation of the entomopathogenic fungus Beauveria bassiana to host niches: autophagy‐related gene 8 as an example - Wei‐Xia Dong; Jin‐Li Ding; Yang Gao; Yue‐Jin Peng; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2017)
Summary Alternative splicing (AS) regulates various biological processes in fungi by extending the cellular proteome. However, comprehensive studies investigating AS in entomopathogenic fungi are lacking. Based on transcriptome data obtained via dual RNA‐seq, the first overview of AS events was developed for Beauveria bassiana growing in an insect haemocoel. The AS was demonstrated for 556 of 8840 expressed genes, accounting for 5.4% of the total genes in B. bassiana . Intron retention was the most abundant type of AS, accounting for 87.1% of all splicing events and exon skipping events were rare, only accounting for 2.0% of all events. Functional distribution analysis indicated an association between alternatively spliced genes and several physiological processes. Notably, B. bassiana autophagy‐related gene 8 ( BbATG8 ), an indispensable gene for autophagy, was spliced at an alternative 5′ splice site to generate two transcripts ( BbATG8‐α and BbATG8‐β ). The BbATG8‐α transcript was necessary for fungal autophagy and oxidation tolerance, while the BbATG8‐β transcript was not. These two transcripts differentially contributed to the formation of conidia or blastospores as well as fungal virulence. Thus, AS acts as a powerful post‐transcriptional regulatory strategy in insect mycopathogens and significantly mediates fungal transcriptional adaption to host niches.

Behavioral responses of the egg parasitoid Trissolcus japonicus to volatiles from adults of its stink bug host, Halyomorpha halys - Yong-Zhi Zhong; Jin-Ping Zhang; Li-Li Ren; Rui Tang; Hai-Xia Zhan; Guo-Hua Chen; Feng Zhang (Journal of Pest Science, 2017)

Deep Fracturing of the Hard Rock Surrounding a Large Underground Cavern Subjected to High Geostress: In Situ Observation and Mechanism Analysis - Xia-Ting Feng; Shu-Feng Pei; Quan Jiang; Yang-Yi Zhou; Shao-Jun Li; Zhi-Bin Yao (Rock Mechanics and Rock Engineering, 2017)

Overexpression of the nitrate transporter, OsNRT2.3b, improves rice phosphorus uptake and translocation - Huimin Feng; Bin Li; Yang Zhi; Jingguang Chen; Ran Li; Xiudong Xia; Guohua Xu; Xiaorong Fan (Plant Cell Reports, 2017)

Extracellular vesicles-mediated transfer of miR-208a/b exaggerate hypoxia/reoxygenation injury in cardiomyocytes by reducing QKI expression - Feng Wang; Yuxiang Yuan; Pirong Yang; Xia Li (Molecular and Cellular Biochemistry, 2017)

Synthesis and biological evaluation of novel anti-hepatitis C virus (HCV) agents: 2-hydroxylphenethyl sulfanyl-oxopyrimidines - Daochun Wu; Yue Feng; Hua Wang; Junfeng Yang; Xian Chen; Yueping Wang; Christopher Cong Lai; Yufang Zhang; Cong Li; Xueshan Xia; Yanping He (Medicinal Chemistry Research, 2017)

Paeonol protects against TNF-α-induced proliferation and cytokine release of rheumatoid arthritis fibroblast-like synoviocytes by upregulating FOXO3 through inhibition of miR-155 expression - Ning Liu; Xue Feng; Wenbo Wang; Xingkai Zhao; Xia Li (Inflammation Research, 2017)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

Evaluation of the Integrity of Deep Rock Masses Using Results of Digital Borehole Televiewers - Hao-Sen Guo; Xia-Ting Feng; Shao-Jun Li; Cheng-Xiang Yang; Zhi-Bin Yao (Rock Mechanics and Rock Engineering, 2017)

Contrasting impacts of two subtropical earthworm species on leaf litter carbon sequestration into soil aggregates - Jingtao Wu; Hanqing Li; Weixin Zhang; Feng Li; Jinhua Huang; Qifeng Mo; Hanping Xia (Journal of Soils and Sediments, 2017)

A new phenol glycoside from Physalis angulata - Cheng-Peng Sun; Xiu-Fang Nie; Ning Kang; Feng Zhao; Li-Xia Chen; Feng Qiu (Natural Product Research, 2017)

Skeletonema cf. costatum biogenic silica production rate determinated by PDMPO method - Guicheng Zhang; Xiaoyun Leng; Yuanyuan Feng; Xia Li; Jun Sun (Journal of Ocean University of China, 2017)

Sesquiterpenes from Curcuma wenyujin with their inhibitory activities on nitric oxide production in RAW 264.7 cells - Suyu Gao; Guiyang Xia; Liqing Wang; Li Zhou; Feng Zhao; Jian Huang; Lixia Chen (Natural Product Research, 2017)

Activation of group I metabotropic glutamate receptors regulates the excitability of rat retinal ganglion cells by suppressing Kir and I h - Qian Li; Peng Cui; Yanying Miao; Feng Gao; Xue-Yan Li; Wen-Jing Qian; Shu-Xia Jiang; Na Wu; Xing-Huai Sun; Zhongfeng Wang (Brain Structure and Function, 2017)

Genomewide association study for seeding emergence and tiller number using SNP markers in an elite winter wheat population - GUANG FENG CHEN; RU GANG WU; DONG MEI LI; HAI XIA YU; ZHIYING DENG; JI CHUN TIAN (Journal of Genetics, 2017)

Performance improvement of raw water pretreatment process with pre-inoculation biofilm: feasibility and limiting factors - Guang-feng Yang; Li-juan Feng; Cai-rong Guo; Tian Xia; Xiang-yang Xu; Liang Zhu (Biodegradation, 2017)

Organic carbon isotope and pollen evidence for mangrove development and response to human activity in Guangxi (Southwest China) over the last 140 years - Peng Xia; Xianwei Meng; Zhen Li; Aiping Feng (Acta Oceanologica Sinica, 2017)

The prevalence and genotype distribution of rotavirus A infection among children with acute gastroenteritis in Kunming, China - Ziqin Dian; Mao Fan; Binghui Wang; Yue Feng; Hao Ji; Shuwei Dong; A-Mei Zhang; Li Liu; Hua Niu; Xueshan Xia (Archives of Virology, 2017)

Rhizobium hidalgonense sp. nov., a nodule endophytic bacterium of Phaseolus vulgaris in acid soil - Jun Yan; Hui Yan; Li Xue Liu; Wen Feng Chen; Xiao Xia Zhang; Myrthala M. Verástegui-Valdés; En Tao Wang; Xiao Zeng Han (Archives of Microbiology, 2017)

Identification of a nuclear-recessive gene locus for male sterility on A2 chromosome using the Brassica 60 K SNP array in non-heading Chinese cabbage - Xia Li; Aihua Wang; Feng Zu; Zhenhua Hu; Jiazao Lin; Guolin Zhou; Jinxing Tu (Genes & Genomics, 2016)

High-performance size-exclusion chromatography studies on the formation and distribution of polar compounds in camellia seed oil during heating - Hong-xia Feng; Rokayya Sam; Lian-zhou Jiang; Yang Li; Wen-ming Cao (Journal of Zhejiang University-SCIENCE B, 2016)

A new flavonoid glycoside from Elsholtzia bodinieri - Jin-Dong Zhong; Yue Feng; Hong-Mei Li; Xue-Shan Xia; Rong-Tao Li (Natural Product Research, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Clitocine potentiates TRAIL-mediated apoptosis in human colon cancer cells by promoting Mcl-1 degradation - Jian-guo Sun; Feng Ruan; Xue-li Zeng; Jun Xiang; Xia Li; Ping Wu; Kwok Pui Fung; Fei-yan Liu (Apoptosis, 2016)

Arctigenin Confers Neuroprotection Against Mechanical Trauma Injury in Human Neuroblastoma SH-SY5Y Cells by Regulating miRNA-16 and miRNA-199a Expression to Alleviate Inflammation - Jie Song; Na Li; Yang Xia; Zhong Gao; Sa-Feng Zou; Yu-Hui Yan; Shao-Heng Li; Yue Wang; Ya-Kun Meng; Jing-Xian Yang; Ting-Guo Kang (Journal of Molecular Neuroscience, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Rock Cracking Indices for Improved Tunnel Support Design: A Case Study for Columnar Jointed Rock Masses - Xia-Ting Feng; Xian-Jie Hao; Quan Jiang; Shao-jun Li; John A. Hudson (Rock Mechanics and Rock Engineering, 2016)

The proteome and phosphoproteome of maize pollen uncovers fertility candidate proteins - Qing Chao; Zhi-fang Gao; Yue-feng Wang; Zhe Li; Xia-he Huang; Ying-chun Wang; Ying-chang Mei; Biligen-gaowa Zhao; Liang Li; Yu-bo Jiang; Bai-chen Wang (Plant Molecular Biology, 2016)

Characterization of β-glucosidase from Aspergillus terreus and its application in the hydrolysis of soybean isoflavones - Feng-ying Yan; Wei Xia; Xiao-xu Zhang; Sha Chen; Xin-zheng Nie; Li-chun Qian (Journal of Zhejiang University-SCIENCE B, 2016)

Reactivation of HSV-1 following explant of tree shrew brain - Lihong Li; Zhuoran Li; Xin Li; Erlin Wang; Fengchao Lang; Yujie Xia; Nigel W. Fraser; Feng Gao; Jumin Zhou (Journal of NeuroVirology, 2016)

Sedimentary records of mangrove evolution during the past one hundred years based on stable carbon isotope and pollen evidences in Maowei, SW China - Peng Xia; Xianwei Meng; Zhen Li; Aiping Feng (Journal of Ocean University of China, 2016)

Interferon-inducible GTPase: a novel viral response protein involved in rabies virus infection - Ling Li; Hualei Wang; Hongli Jin; Zengguo Cao; Na Feng; Yongkun Zhao; Xuexing Zheng; Jianzhong Wang; Qian Li; Guoxing Zhao; Feihu Yan; Lina Wang; et al. (Archives of Virology, 2016)

Visual detection of Ebola virus using reverse transcription loop-mediated isothermal amplification combined with nucleic acid strip detection - Changping Xu; Hualei Wang; Hongli Jin; Na Feng; Xuexing Zheng; Zengguo Cao; Ling Li; Jianzhong Wang; Feihu Yan; Lina Wang; Hang Chi; Weiwei Gai; et al. (Archives of Virology, 2016)

Analysis of EDZ Development of Columnar Jointed Rock Mass in the Baihetan Diversion Tunnel - Xian-Jie Hao; Xia-Ting Feng; Cheng-Xiang Yang; Quan Jiang; Shao-Jun Li (Rock Mechanics and Rock Engineering, 2016)

Elevated expression of NLRP3 in patients with immune thrombocytopenia - Jianlin Qiao; Yun Liu; Xiaoqian Li; Yuan Xia; Yulu Wu; Depeng Li; Hongchun Li; Ping Ma; Feng Zhu; Zhenyu Li; Kailin Xu; Lingyu Zeng (Immunologic Research, 2016)

The pseudorabies virus DNA polymerase processivity factor UL42 exists as a monomer in vitro and in vivo - Yi-Ping Wang; Li-Ping Huang; Wen-Juan Du; Yan-Wu Wei; De-Li Xia; Hong-Li Wu; Li Feng; Chang-Ming Liu (Archives of Virology, 2016)

A translationally controlled tumor protein gene Rpf41 is required for the nodulation of Robinia pseudoacacia - Minxia Chou; Congcong Xia; Zhao Feng; Yali Sun; Dehui Zhang; Mingzhe Zhang; Li Wang; Gehong Wei (Plant Molecular Biology, 2016)

Serum amyloid A stimulates vascular endothelial growth factor receptor 2 expression and angiogenesis - Mei Lv; Yan-fei Xia; Bo Li; Hui Liu; Jin-yu Pan; Bei-bei Li; Cheng Zhang; Feng-shuang An (Journal of Physiology and Biochemistry, 2016)

Cyanobacteria in the complex river-connected Poyang Lake: horizontal distribution and transport - Xia Liu; Yun-Liang Li; Bao-Gui Liu; Kui-Mei Qian; Yu-Wei Chen; Jun-Feng Gao (Hydrobiologia, 2016)

Isolation and sequence analysis of the complete NS1 and VP2 genes of canine parvovirus from domestic dogs in 2013 and 2014 in China - Hualei Wang; Hongli Jin; Qian Li; Guoxing Zhao; Nan Cheng; Na Feng; Xuexing Zheng; Jianzhong Wang; Yongkun Zhao; Ling Li; Zengguo Cao; Feihu Yan; et al. (Archives of Virology, 2016)

Geochronology, geochemistry, and Sr–Nd–Pb isotopes of Cretaceous granitoids from western Tibet: petrogenesis and tectonic implications for the evolution of the Bangong Meso-Tethys - Qiang-Tai Huang; Zhou-Rong Cai; Bin Xia; Jian-Feng Li; Lian-Ze Xia; Hui-Chuan Liu (International Geology Review, 2016)

Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

Dengue virus infection induces formation of G3BP1 granules in human lung epithelial cells - Jun Xia; Xiaoyan Chen; Feng Xu; Yi Wang; Yongxia Shi; Yuye Li; Junfang He; Ping Zhang (Archives of Virology, 2015)

Molecular mapping and markers for leaf rust resistance gene Lr24 in CIMMYT wheat line 19HRWSN-122 - Ai-yong Qi; Pei-pei Zhang; Xian-chun Xia; Zhong-hu He; Julio Huerta-Espino; Zai-feng Li; Da-qun Liu (Euphytica, 2015)

Mutations in human IFT140 cause non-syndromic retinal degeneration - Mingchu Xu; Lizhu Yang; Feng Wang; Huajin Li; Xia Wang; Weichen Wang; Zhongqi Ge; Keqing Wang; Li Zhao; Hui Li; Yumei Li; Ruifang Sui; et al. (Human Genetics, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Generation and characterization of Brassica rapa ssp. pekinensis – B. oleracea var. capitata monosomic and disomic alien addition lines - AI XIA GU; SHU XING SHEN; YAN HUA WANG; JIAN JUN ZHAO; SHU XIN XUAN; XUE PING CHEN; XIAO FENG LI; SHUANG XIA LUO; YU JING ZHAO (Journal of Genetics, 2015)

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

Alantolactone induces G1 phase arrest and apoptosis of multiple myeloma cells and overcomes bortezomib resistance - Yao Yao; Dandan Xia; Yueping Bian; Yueyue Sun; Feng Zhu; Bin Pan; Mingshan Niu; Kai Zhao; Qingyun Wu; Jianlin Qiao; Chunling Fu; Zhenyu Li; et al. (Apoptosis, 2015)

A soluble receptor for advanced glycation end-products inhibits myocardial apoptosis induced by ischemia/reperfusion via the JAK2/STAT3 pathway - Xue Jiang; Cai-xia Guo; Xiang-jun Zeng; Hui-hua Li; Bu-xing Chen; Feng-he Du (Apoptosis, 2015)

Spectral–spatial based sub-pixel mapping of remotely sensed imagery with multi-scale spatial dependence - Yihang Zhang; Yun Du; Feng Ling; Xia Wang; Xiaodong Li (International Journal of Remote Sensing, 2015)

Thyroid hormone responsive protein spot 14 enhances lipogenesis in bovine mammary epithelial cells - Yingjun Cui; Zhiyu Liu; Xia Sun; Xiaoming Hou; Bo Qu; Feng Zhao; Xuejun Gao; Zhe Sun; Qingzhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Establishment and characterization of a gonad cell line from half-smooth tongue sole Cynoglossus semilaevis pseudomale - Ai Sun; Song-Lin Chen; Feng-Tao Gao; Hai-Long Li; Xiao-Feng Liu; Na Wang; Zhen-Xia Sha (Fish Physiology and Biochemistry, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Sevoflurane-Induced Down-regulation of Hippocampal Oxytocin and Arginine Vasopressin Impairs Juvenile Social Behavioral Abilities - Zhi-Bin Zhou; Xiao-Yu Yang; Bao-Long Yuan; Li-Jun Niu; Xue Zhou; Wen-Qi Huang; Xia Feng; Li-Hua Zhou (Journal of Molecular Neuroscience, 2015)

Rapid emergence of a PB2-E627K substitution confers a virulent phenotype to an H9N2 avian influenza virus during adaption in mice - Xiaoyu Sang; Airong Wang; Tongjie Chai; Xijun He; Jie Ding; Xiaolong Gao; Yuanguo Li; Kun Zhang; Zhiguang Ren; Lin Li; Zhijun Yu; Tiecheng Wang; et al. (Archives of Virology, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

De novo transcriptome analysis of the gametophyte of Undaria pinnatifida (Phaeophyceae) - Ti Feng Shan; Shao Jun Pang; Jing Li; Xia Li (Journal of Applied Phycology, 2015)

Using rabies virus vaccine strain SRV9 as viral vector to express exogenous gene - Hualei Wang; Hongli Jin; Na Feng; Xuexing Zheng; Ling Li; Yinglin Qi; Meng Liang; Yongkun Zhao; Tiecheng Wang; Yuwei Gao; Changchun Tu; Ningyi Jin; et al. (Virus Genes, 2015)

Failure Mechanism of Unbonded Prestressed Thru-Anchor Cables: In Situ Investigation in Large Underground Caverns - Quan Jiang; Xia-Ting Feng; Jie Cui; Shao-Jun Li (Rock Mechanics and Rock Engineering, 2015)

Optimization of Astragalus membranaceus hairy roots induction and culture conditions for augmentation production of astragalosides - Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Wei Ma; Li-Ping Yao; Chen Feng; Xin-Xin Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Complete mitochondrial genome of the brown alga Sargassum horneri (Sargassaceae, Phaeophyceae): genome organization and phylogenetic analyses - Feng Liu; Shaojun Pang; Xia Li; Jing Li (Journal of Applied Phycology, 2015)

High-efficiency catalytic degradation of phenol based on the peroxidase-like activity of cupric oxide nanoparticles - Y.-B. Feng; L. Hong; A.-L. Liu; W.-D. Chen; G.-W. Li; W. Chen; X.-H. Xia (International Journal of Environmental Science and Technology, 2015)

Rock Burst Intensity Classification Based on the Radiated Energy with Damage Intensity at Jinping II Hydropower Station, China - Bing-Rui Chen; Xia-Ting Feng; Qing-Peng Li; Ru-Zhou Luo; Shaojun Li (Rock Mechanics and Rock Engineering, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Isolation and genetic characterization of avian influenza virus H4N6 from ducks in China - Xiao-yuan Yuan; You-ling Wang; Ke-Xiang Yu; Yu-xia Zhang; Huai-ying Xu; Jin-xing Yang; Feng Li; Min-xun Song (Archives of Virology, 2015)

RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Microseismic monitoring of columnar jointed basalt fracture activity: a trial at the Baihetan Hydropower Station, China - Bing-Rui Chen; Qing-Peng Li; Xia-Ting Feng; Ya-Xun Xiao; Guang-Liang Feng; Lian-Xing Hu (Journal of Seismology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

DNA Methylation: Roles in Rheumatoid Arthritis - Feng-Lai Yuan; Xia Li; Rui-Sheng Xu; Dong-Lin Jiang; Xiao-Gang Zhou (Cell Biochemistry and Biophysics, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

Genetic characterization of an isolate of canine distemper virus from a Tibetan Mastiff in China - Weike Li; Tiansong Li; Yuxiu Liu; Yuwei Gao; Songtao Yang; Na Feng; Heting Sun; Shengle Wang; Lei Wang; Zhigao Bu; Xianzhu Xia (Virus Genes, 2014)

Evidence for natural Borna disease virus infection in healthy domestic animals in three areas of western China - Liang Zhang; Xiao Wang; Qunling Zhan; Zhenhai Wang; Mingming Xu; Dan Zhu; Feng He; Xia Liu; Rongzhong Huang; Dan Li; Yang Lei; Peng Xie (Archives of Virology, 2014)

Haemocyte Apoptosis of the Tiger Shrimp Penaeus monodon Exposed to Cadmium - Jian-An Xian; Bin Li; Hui Guo; Yu-Tao Miao; Jian-Min Ye; Li-Na Feng; Chao-Xia Ye; Xun-Bin Pan; An-Li Wang; Xuan-Ming Hao (Bulletin of Environmental Contamination and Toxicology, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

Effects of lipopolysaccharide-induced inflammation on the interstitial cells of Cajal - Jia Wei; Ning Li; Xue Xia; Xuyong Chen; Fei Peng; Gail E. Besner; Jiexiong Feng (Cell and Tissue Research, 2014)

Age and composition of the Rebang Co and Julu ophiolites, central Tibet: implications for the evolution of the Bangong Meso-Tethys - Wei-Liang Liu; Bin Xia; Yun Zhong; Jian-Xin Cai; Jian-Feng Li; Hong-Fei Liu; Zhou-Rong Cai; Zhi-Lei Sun (International Geology Review, 2014)

An Experimental Study on the Pre-Peak Unloading Damage Evolution of Marble - Shi-Li Qiu; Xia-Ting Feng; Jian-Qing Xiao; Chuan-Qing Zhang (Rock Mechanics and Rock Engineering, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Multimineral optimization processing method based on elemental capture spectroscopy logging - Zhou Feng; Xin-Tong Li; Hong-Liang Wu; Shou-Ji Xia; Ying-Ming Liu (Applied Geophysics, 2014)

A new flavonoid from the aerial parts of Andrographis paniculata - Li-Xia Chen; Hao He; Gui-Yang Xia; Kai-Lan Zhou; Feng Qiu (Natural Product Research, 2014)

Protection of MES23.5 dopaminergic cells by obestatin is mediated by proliferative rather than anti-apoptotic action - Xiao-Li Shen; Feng-Ju Jia; Ning Song; Jun-Xia Xie; Hong Jiang (Neuroscience Bulletin, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Cell-penetrating fusion peptides OD1 and OD2 interact with Bcr–Abl and influence the growth and apoptosis of K562 cells - Hai-xia Wang; Heng Xiao; Liang Zhong; Kun Tao; Ya-juan Li; Shi-feng Huang; Jian-ping Wen; Wen-li Feng (Molecular and Cellular Biochemistry, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Development, characterization, genetic diversity and cross-species/genera transferability of ILP markers in rubber tree (Hevea brasiliensis) - Dejun Li; Zhihui Xia; Zhi Deng; Xianghong Liu; Fuying Feng (Genes & Genomics, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Elevated risk of opportunistic viral infection in patients with Crohn’s disease during biological therapies: a meta analysis of randomized controlled trials - Xiaobing Wang; Feng Zhou; Junzhang Zhao; Rui Zhou; Meifang Huang; Jin Li; Wei Wang; Shufang Xu; Bing Xia (European Journal of Clinical Pharmacology, 2013)

MK-2206 induces cell cycle arrest and apoptosis in HepG2 cells and sensitizes TRAIL-mediated cell death - Peng Jiao; Yun-Sheng Zhou; Juan-Xia Yang; Ya-Li Zhao; Qiang-Qiang Liu; Chuang Yuan; Feng-Ze Wang (Molecular and Cellular Biochemistry, 2013)

Marker-assisted breeding for rf1, a nuclear gene controlling A1 CMS in sorghum (Sorghum bicolor L. Moench) - Jianming Gao; Buxian Xia; Feng Luo; Shoujun Sun; Zhongyou Pei; Zhi Gui; Qinghua Yuan; Xianglin Li (Euphytica, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Erratum to: Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Anatomical studies of ovule development in the post-bloom pistils of the ‘Zuili’ plum (Prunus salicina Lindl.) - Hui-juan Jia; Xia Yang; Feng-jie He; Bin Li (Journal of Zhejiang University-SCIENCE B, 2013)

Salegentibacter echinorum sp. nov., isolated from the sea urchin Hemicentrotus pulcherrimus - Hai-Feng Xia; Xiao-Li Li; Qian-Qian Liu; Ting-Ting Miao; Zong-Jun Du; Guan-Jun Chen (Antonie van Leeuwenhoek, 2013)

Cotton PRP5 gene encoding a proline-rich protein is involved in fiber development - Wen-Liang Xu; De-Jing Zhang; Yan-Feng Wu; Li-Xia Qin; Geng-Qing Huang; Juan Li; Long Li; Xue-Bao Li (Plant Molecular Biology, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

An integrative analysis of four CESA isoforms specific for fiber cellulose production between Gossypium hirsutum and Gossypium barbadense - Ao Li; Tao Xia; Wen Xu; Tingting Chen; Xianliang Li; Jian Fan; Ruyi Wang; Shengqiu Feng; Yanting Wang; Bingrui Wang; Liangcai Peng (Planta, 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Oxidative decarboxylation of mandelic acid derivative by recombinant Escherichia coli: a novel method of ethyl vanillin synthesis - Xiao-xia Pan; Jing-jing Li; Mei-gui Wang; Wen-sen He; Cheng-sheng Jia; Xiao-ming Zhang; Biao Feng; Da-li Li; Zeng Zeng (Biotechnology Letters, 2013)

ISRM Suggested Method for Measuring Rock Mass Displacement Using a Sliding Micrometer - S. J. Li; Xia-Ting Feng; J. A. Hudson (Rock Mechanics and Rock Engineering, 2013)

ISRM Suggested Method for Rock Fractures Observations Using a Borehole Digital Optical Televiewer - S. J. Li; Xia-Ting Feng; C. Y. Wang; J. A. Hudson (Rock Mechanics and Rock Engineering, 2013)

Hippocampal CLOCK protein participates in the persistence of depressive-like behavior induced by chronic unpredictable stress - Wen-Gao Jiang; Su-Xia Li; Jian-Feng Liu; Yan Sun; Shuang-Jiang Zhou; Wei-Li Zhu; Jie Shi; Lin Lu (Psychopharmacology, 2013)

Potential Prevention and Treatment of Maifanite for Alzheimer's Disease Based on Behavior Test, Oxidative Stress Assay, and Trace Element Analysis in Hippocampus of Aβ(25–35)-Induced AD Rats - Ling-Feng Jiang; Hai-Lin Liao; Hong-Miao Huang; Li-Xia Zhou; Ling Li; Shi-Xian Cheng; Cheng-Zhi Du (Biological Trace Element Research, 2013)

A new flavonol from Oxytropis ochrocephala Bunge - Xia Li; Shou-De Zhang; Hui-Zi Jin; Feng Dong; Lei Shan; Wei-Dong Zhang (Natural Product Research, 2013)

Improved antifouling properties of PVDF membranes modified with oppositely charged copolymer - Xiang Shen; Yiping Zhao; Xia Feng; Sixin Bi; Wenbin Ding; Li Chen (Biofouling, 2013)

Molecular and analysis of a phenylalanine ammonia-lyase gene (LrPAL2) from Lycoris radiata - Yumei Jiang; Bing Xia; Lijian Liang; Xiaodan Li; Sheng Xu; Feng Peng; Ren Wang (Molecular Biology Reports, 2013)

A non-synonymous SNP in the NOS2 associated with septic shock in patients with sepsis in Chinese populations - Zhifu Wang; Kai Feng; Maoxing Yue; Xiaoguang Lu; Qihan Zheng; Hongxing Zhang; Yun Zhai; Peiyao Li; Lixia Yu; Mi Cai; Xiumei Zhang; Xin Kang; et al. (Human Genetics, 2013)

Erratum to: Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2013)

Molecular cloning and characterization of S-adenosylmethionine synthetase gene from Lycoris radiata - Xiao-Dan Li; Bing Xia; Ren Wang; Sheng Xu; Yu-Mei Jiang; Fang-Bo Yu; Feng Peng (Molecular Biology Reports, 2013)

Plant-Soil Feedbacks and Soil Sickness: From Mechanisms to Application in Agriculture - Li-Feng Huang; Liu-Xia Song; Xiao-Jian Xia; Wei-Hua Mao; Kai Shi; Yan-Hong Zhou; Jing-Quan Yu (Journal of Chemical Ecology, 2013)

Association of CASP9, CASP10 gene polymorphisms and tea drinking with colorectal cancer risk in the Han Chinese population - He Liu; Xia Jiang; Ming-wu Zhang; Yi-feng Pan; Yun-xian Yu; Shan-chun Zhang; Xin-yuan Ma; Qi-long Li; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Candida sanyaensis sp. nov., an ascomycetous yeast species isolated from soil - Feng-Li Hui; Qiu-Hong Niu; Tao Ke; Ying-Xia Li; Ching-Fu Lee (Antonie van Leeuwenhoek, 2013)

Association between the OGG1 Ser326Cys and APEX1 Asp148Glu polymorphisms and lung cancer risk: a meta-analysis - Wu Wei; Xiao-Feng He; Jiang-Bo Qin; Jiao Su; Shao-Xia Li; Yi Liu; Ying Zhang; Wei Wang (Molecular Biology Reports, 2012)

Cryptococcus nanyangensis sp. nov., A New Basidiomycetous Yeast Isolated from the Gut of Wood-Boring Larvae - Feng-Li Hui; Qiu-Hong Niu; Tao Ke; Ying-Xia Li (Current Microbiology, 2012)

Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2012)

Association study of ACE polymorphisms and systemic lupus erythematosus in Northern Chinese Han population - Ai-min Gong; Xin-yuan Li; Yi-qin Wang; Hai-xia Yan; Zhao-xia Xu; Zhao Feng; Yi-qiang Xie; De-hui Yin; Shi-zhong Yang (Molecular Biology Reports, 2012)

Differential expression of aging biomarkers at different life stages of the annual fish Nothobranchius guentheri - Changshui Liu; Xia Wang; Wenrong Feng; Guorong Li; Feng Su; Shicui Zhang (Biogerontology, 2012)

Hydrological Changes of the Irtysh River and the Possible Causes - Feng Huang; Ziqiang Xia; Fan Li; Lidan Guo; Fucheng Yang (Water Resources Management, 2012)

Anatomical observations of adventitious bud regeneration from leaf explants of Ziziphus jujube Mill. ‘Huizao’ - Chunhua Ma; Xia Ye; Yanhui Chen; Jiancan Feng; Xiaoli Shang; Jidong Li; Yingxia Wu; Jianbin Hu (Horticulture, Environment, and Biotechnology, 2012)

Migration of natural estrogens around a concentrated dairy-feeding operation - Yan-xia Li; Wei Han; Ming Yang; Cheng-hong Feng; Xiao-fei Lu; Feng-song Zhang (Environmental Monitoring and Assessment, 2012)

PDTC attenuate LPS-induced kidney injury in systemic lupus erythematosus-prone MRL/lpr Mice - Jin-Xia Zhai; Zhao-Xiang Zhang; Ya-Juan Feng; Shu-Shu Ding; Xing-Hua Wang; Li-Wei Zou; Dong-Qing Ye (Molecular Biology Reports, 2012)

Association between the COMT Val158Met polymorphism and breast cancer risk: a meta-analysis of 30,199 cases and 38,922 controls - Xiao-Feng He; Wu Wei; Shao-Xia Li; Jiao Su; Ying Zhang; Xiang-Hua Ye; Yi Liu; Wei Wang (Molecular Biology Reports, 2012)

Pt and Pd in sediments from the Pearl River Estuary, South China: background levels, distribution, and source - Li-feng Zhong; Wen Yan; Jie Li; Xiang-lin Tu; Bao-ming Liu; Zhen Xia (Environmental Science and Pollution Research, 2012)

Genetic polymorphism analysis of killer cell immunoglobulin-like receptor genes in the Chinese Uygur population - Hong-dan Wang; Bo-feng Zhu; Chun-mei Shen; Guo-lian Yuan; Guang Yang; Juan-ning Guo; Jiang-wei Yan; Hai-xia Qin; Jian-xin Guo; Li-ping Zhang; Xiao-qin Jia; Rudolf Lucas (Molecular Biology Reports, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Construction of Gene Library of 20 kb DNAs from Parasporal Crystal in Bacillus thuringiensis Strain 4.0718: Phylogenetic Analysis and Molecular Docking - Feng Wu; Xinmin Zhao; Yunjun Sun; Wenping Li; Liqiu Xia; Xuezhi Ding; Jia Yin; Shengbiao Hu; Ziquan Yu; Ying Tang (Current Microbiology, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

Precise mapping Fhb5, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Mingzhi Tang; Yan Zhou; Guoqiang Li; Xia An; Feng Lin; Haibin Xu; Haiyan Jia; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2011)

Effects of allitridin on acute and chronic mouse cytomegalovirus infection - Xing-lou Liu; Hui Wang; Ya-nan Li; Hai-xia Ge; Sai-nan Shu; Feng Fang (Archives of Virology, 2011)

Over-expression of mango (Mangifera indica L.) MiARF2 inhibits root and hypocotyl growth of Arabidopsis - Bei Wu; Yun-He Li; Jian-Yong Wu; Qi-Zhu Chen; Xia Huang; Yun-Feng Chen; Xue-Lin Huang (Molecular Biology Reports, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Rice Gene OsDSR-1 Promotes Lateral Root Development in Arabidopsis Under High-Potassium Conditions - Xu Ming Yin; Pedro S. C. F. Rocha; Man Ling Wang; Yu Xin Zhu; Luo Ye Li; Shu Feng Song; Xinjie Xia (Journal of Plant Biology, 2011)

Glycomyces halotolerans sp. nov., a novel actinomycete isolated from a hypersaline habitat in Xinjiang, China - Tong-Wei Guan; Zhan-Feng Xia; Jing Xiao; Nan Wu; Zheng-Jun Chen; Li-Li Zhang; Xiao-Ping Zhang (Antonie van Leeuwenhoek, 2011)

Saccharopolyspora lacisalsi sp. nov., a novel halophilic actinomycete isolated from a salt lake in Xinjiang, China - Tong-Wei Guan; Nan Wu; Zhan-Feng Xia; Ji-Sheng Ruan; Xiao-Ping Zhang; Ying Huang; Li-Li Zhang (Extremophiles, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Effects of palmitic acid on lipid metabolism homeostasis and apoptosis in goose primary hepatocytes - Zhixiong Pan; Jiwen Wang; Hui Tang; Liang Li; Jia Lv; Lu Xia; Chunchun Han; Feng Xu; Hua He; Hengyong Xu; Bo Kang (Molecular and Cellular Biochemistry, 2011)

Molecular cloning and characterization of a phenylalanine ammonia-lyase gene (LrPAL) from Lycoris radiata - Yumei Jiang; Nan Xia; Xiaodan Li; Wenbiao Shen; Lijian Liang; Chunyan Wang; Ren Wang; Feng Peng; Bing Xia (Molecular Biology Reports, 2011)

Targeting interleukin-21 in rheumatoid arthritis - Feng-Lai Yuan; Wei Hu; Wei-Guo Lu; Xia Li; Jian-Ping Li; Rui-Sheng Xu; Cheng-Wan Li; Fei-Hu Chen; Cheng Jin (Molecular Biology Reports, 2011)

Polymorphism of prion protein gene in sheep of Inner Mongolian, China - Cai-Xia Han; Hong-Xiang Liu; Yi-Xin Lu; Ming-Xin Song; De-Ming Zhao; Xiang-Mei Zhou; Li-Feng Yang; Xiao-Yun Li (Virus Genes, 2011)

Population genetic analysis of 15 autosomal STR loci in the Russian population of northeastern Inner-Mongolia, China - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shuan-liang Fan; Li-bin Deng; Feng Chen; Li-ping Chen; Hong-dan Wang; Zhen-yuan Wang; Rudolf Lucas; Zhen-min Lian (Molecular Biology Reports, 2010)

The effect of the expression of angiotensin II on extracellular matrix metalloproteinase inducer (EMMPRIN) in macrophages is mediated via the AT1/COX-2/PGE2 pathway - Li-xia Yang; Jin-shan Ye; Rui-wei Guo; Hong Liu; Xian-mei Wang; Feng Qi; Chuanming Guo (Inflammation Research, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Time-trajectory of mean component weight and density in self-thinning Pinus densiflora stands - Li Xue; Hui-fang Feng; Feng-xia Chen (European Journal of Forest Research, 2010)

The vacuolar ATPase in bone cells: a potential therapeutic target in osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Cheng-Wan Li; Jian-Ping Li; Yu Wang (Molecular Biology Reports, 2010)

Acid-sensing ion channels 3: a potential therapeutic target for pain treatment in arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li (Molecular Biology Reports, 2010)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Fine mapping Fhb4, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Guoqiang Li; Haiyan Jia; Feng Xu; Feng Lin; Mingzhi Tang; Yao Wang; Xia An; Haibin Xu; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2010)

The design and preparation of a flexible bio-chip for use as a visual prosthesis, and evaluation of its biological features - Li-Feng Chen; Ning Hu; Na Liu; Bingbing Guo; Junping Yao; Lu Xia; Xiaolin Zheng; Wensheng Hou; Zheng Qin Yin (Cell and Tissue Research, 2010)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

Phosphoproteomic identification and phylogenetic analysis of ribosomal P-proteins in Populus dormant terminal buds - Chang-Cai Liu; Tian-Cong Lu; Hua-Hua Li; Hong-Xia Wang; Gui-Feng Liu; Ling Ma; Chuan-Ping Yang; Bai-Chen Wang (Planta, 2010)

A new pathogenesis-related protein, LrPR4, from Lycoris radiata, and its antifungal activity against Magnaporthe grisea - Xiaodan Li; Bing Xia; Yumei Jiang; Qingsong Wu; Chunyan Wang; Lisi He; Feng Peng; Ren Wang (Molecular Biology Reports, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Brassinosteroids promote photosynthesis and growth by enhancing activation of Rubisco and expression of photosynthetic genes in Cucumis sativus - Xiao-Jian Xia; Li-Feng Huang; Yan-Hong Zhou; Wei-Hua Mao; Kai Shi; Jian-Xiang Wu; Tadao Asami; Zhixiang Chen; Jing-Quan Yu (Planta, 2009)

Saponin fraction from Astragalus membranaceus roots protects mice against polymicrobial sepsis induced by cecal ligation and puncture by inhibiting inflammation and upregulating protein C pathway - Xing-hua Gao; Xian-xiang Xu; Rong Pan; Ying Li; Yu-bin Luo; Yu-feng Xia; Kazuya Murata; Hideaki Matsuda; Yue Dai (Journal of Natural Medicines, 2009)

Adsorption of lead(II) from aqueous solution onto Hydrilla verticillata - Ling-zhi Huang; Guang-ming Zeng; Dan-lian Huang; Li-feng Li; Peng-mian Huang; Chang-bin Xia (Biodegradation, 2009)

Multi-core structure of the Kuroshio in the East China Sea from long-term transect observations - Hong-Xia Chen; Fang-Li Qiao; Tal Ezer; Ye-Li Yuan; Feng Hua (Ocean Dynamics, 2009)

Molecular cloning and recombinant expression of a gene encoding a fungal immunomodulatory protein from Ganoderma lucidum in Pichia pastoris - Jing-Wei Lin; Li-Xia Hao; Gui-Xue Xu; Fei Sun; Feng Gao; Ren Zhang; Li-Xia Liu (World Journal of Microbiology and Biotechnology, 2009)

Molecular cloning, chromosomal location and expression pattern of porcine CIDEa and CIDEc - Y. H. Li; T. Lei; X. D. Chen; T. Xia; Y. Peng; Q. Q. Long; J. Zhang; S. Q. Feng; L. Zhou; Z. Q. Yang (Molecular Biology Reports, 2009)

Effects of Low-Molecular-Weight Organic Acids on Gadolinium Accumulation and Transportation in Tomato Plants - Hui-Juan Zhang; Zheng-Gui Wei; Hai-Yan Zhao; Hong-Xia Yang; Hui-Xin Li; Feng Hu (Biological Trace Element Research, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Proteomic identification of differently expressed proteins responsible for osteoblast differentiation from human mesenchymal stem cells - Ai-Xia Zhang; Wei-Hua Yu; Bao-Feng Ma; Xin-Bing Yu; Frank Fuxiang Mao; Wei Liu; Jia-Qing Zhang; Xiu-Ming Zhang; Shu-Nong Li; Ming-Tao Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2007)

Highly efficient Agrobacterium-mediated transformation of embryogenic cell suspensions of Musa acuminata cv. Mas (AA) via a liquid co-cultivation system - Xia Huang; Xue-Lin Huang; Wang Xiao; Jie-Tang Zhao; Xue-Mei Dai; Yun-Feng Chen; Xiao-Ju Li (Plant Cell Reports, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Long-term aerobic exercise protects the heart against ischemia/reperfusion injury via PI3 kinase-dependent and Akt-mediated mechanism - Kun-Ru Zhang; Hai-Tao Liu; Hai-Feng Zhang; Quan-Jiang Zhang; Qiu-Xia Li; Qiu-Jun Yu; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2007)

Effect of earthworms on the phytoremediation of zinc-polluted soil by ryegrass and Indian mustard - Dandan Wang; Huixin Li; Zhenggui Wei; Xia Wang; Feng Hu (Biology and Fertility of Soils, 2006)

Cloning, comparative characterization of porcine SCAP gene, and identification of its two splice variants - Huan Qiu; Tao Xia; Xiaodong Chen; Xuelian Zhao; Li Gan; Shengqiu Feng; Ting Lei; Zaiqing Yang (Molecular Genetics and Genomics, 2006)

Hypoxic postconditioning enhances the survival and inhibits apoptosis of cardiomyocytes following reoxygenation: role of peroxynitrite formation - Hai-Chang Wang; Hai-Feng Zhang; Wen-Yi Guo; Hui Su; Kun-Ru Zhang; Qiu-Xia Li; Wenli Yan; Xin L. Ma; Bernard L. Lopez; Theodore A. Christopher; Feng Gao (Apoptosis, 2006)

Expression analysis of the NDRG2 gene in mouse embryonic and adult tissues - Xiao-Lan Hu; Xin-Ping Liu; Yan-Chun Deng; Shu-Xin Lin; Lin Wu; Jian Zhang; Li-Feng Wang; Xiao-Bin Wang; Xia Li; Lan Shen; Yuan-Qiang Zhang; Li-Bo Yao (Cell and Tissue Research, 2006)

Purification, enzymatic properties of a recombinant d-hydantoinase and its dissociation by zinc ion - Ya-Wei Shi; Li-Xi Niu; Xia Feng; Jing-Ming Yuan (World Journal of Microbiology and Biotechnology, 2006)

Contribution of earthworm activity to the infiltration of nitrogen in a wheat agroecosystem - Xia Wang; Feng Hu; Hui-Xin Li (Biology and Fertility of Soils, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)